Asymptotic solutions of transient waves generated by a wavemaker in water of uniform depth - Haiqi Fang; Peter H.-Y. Lo; Pengzhi Lin; Philip L.-F. Liu (Wave Motion, 2027)

Combined targeting poly (ADP-ribose) polymerase and receptor tyrosine kinase inhibits ovarian clear cell carcinoma progression through disrupted ribosome biogenesis - Chiao-Yun Lin; An-Shine Chao; Angel Chao; Ren-Chin Wu; Alice L. Yu; Chiung-Hui Fu; Yu-Chuan Teng; Ruby Yun-Ju Huang; Chyong-Huey Lai (Journal of Molecular Medicine, 2026)

Revisiting ecoenzymatic stoichiometry models for improved understanding of microbial resource limitations - Lifei Sun; Ji Chen; Yanci Qiao; Daryl L. Moorhead; Wolfgang Wanek; Raúl Ochoa-Hueso; Yongxin Lin (Soil Biology and Biochemistry, 2026)

Exact phylodynamic likelihood via structured Markov genealogy processes - Aaron A. King; Qianying Lin; Edward L. Ionides (Theoretical Population Biology, 2026)

3-OH-FA- and branched GDGT-based temperature calibrations from a transect of lakes in the eastern USA - Changhai Hou; Michael L. Griffiths; Alice Hardman; Osamu Seki; Aifeng Zhou; Sarah Greene; Elizabeth W. Patterson; Roland Indriksons; Sabrina Ryan; Michael DaSilva; Matthew Allison; Lin Chen; et al. (Organic Geochemistry, 2026)

Synergistic co-culture of Rhizopus oryzae and Rhodotorula babjevae transforms faba bean and oat into nutrient-rich tempeh-like foods - Laura Alejandra Fernandez Castaneda; Galia Zamaratskaia; Su-lin L. Leong; Volkmar Passoth; Chiara Viretto; Ali Zein Alabiden Tlais; Raffaella Di Cagno; Fabio Tuccillo; Minnamari Edelmann; Kati Katina; Olivia Zehnder-Wyss; Laura Nyström; et al. (Food Research International, 2026)

Compartmentalized hydrogel-based in situ fibrous bed bioreactor (isFBB) for spatially controlled multi-strain anaerobic human gut microbial growth - Zubeen J. Hathi; James M.W.R. McElhinney; Ramachandran Chelliah; Manideep Pabba; Blaise L. Tardy; Anshu Priya; Carol Sze Ki Lin; Srinivas Mettu (Chemical Engineering Journal, 2026)

Flux-dominated crustal helium enrichment beyond Cratonic Basins: Evidence from geothermal fluids in the Cathaysia Block, South China - Xuelian Huang; Shuai Wang; Yunkai Lei; Xueqing Wu; Jingyu Lin; Xiangxian Ma; Wenjing Lin; Daniele L. Pinti; Guodong Zheng; Shihua Qi (Chemical Geology, 2026)

Association of the Pea Crab Arcotheres similis with the Invasive Charru Mussel Mytella strigata in Panguil Bay, Philippines - Mark L. Arcilla; Gaudioso Pates; Mercedes Maceren-Pates; Fe Dolores Parado-Estepa; Peter Ng Kee Lin; Alleia Pajuta; Princess Earl Potente (Regional Studies in Marine Science, 2026)

Extreme weather salience as a climate crisis signal: Examining the role of extreme weather fear in adaptive and maladaptive responses to eco-anxiety - Sam S.S. Lau; Jason W.L. Fong; Emma L. Lawrance; Angel W.L. Chui; Wangjian Zhang; Shao Lin; Bahtiyar Yıldız; Andras N. Zsido (Global Environmental Change, 2026)

Assisted natural regeneration promotes soil carbon stabilization through fungal residue pathways in subtropical forests - Xiangbiao Chen; Zhijie Yang; Teng-chiu Lin; Robin L. Chazdon; Xiaofei Liu; Decheng Xiong; Chao Xu; Shidong Chen; Chengfang Lin; Miaohua Jiang; Yusheng Yang (Forest Ecology and Management, 2026)

Air pollution and autism-like traits: Sensitive periods and joint effects of exposure to sources and constituents of fine particulate matter - Lydia Lichtiger; Edwina Yeung; Tzu-Chun Lin; Diane L. Putnick; Rajeshwari Sundaram; Erin M. Bell; Md Mostafijur Rahman; George D. Thurston; Yuyan Wang; Akhgar Ghassabian (Environmental Research, 2026)

Processes affecting pollution fluxes during the coastal erosion of legacy colliery wastes - Ian T. Burke; Sebastian J. Pitman; James Hodson; Lin Niu; Fatmah Mohammed; Jenni Ilari Skakunova; Alex L. Riley; Catherine J. Gandy; Elliot Whitehead; Karen A. Hudson-Edwards; Elin Jennings; Helen Jay; et al. (Applied Geochemistry, 2026)

Long-term exposure to PM2.5-bound metals and female breast cancer incidence in New Mexico, USA - Yanhong Huang; Charles L. Wiggins; Angela L. W. Meisner; Yan Lin; Li Luo; Xi Gong (Air Quality, Atmosphere & Health, 2026)
Female breast cancer (FBC) is the most commonly diagnosed malignant cancer and the second leading cancer cause of death among women in the United States. Environmental exposures, particularly PM 2.5 -bound metals, have been increasingly associated with breast cancer incidence. We evaluated associations between long-term residential exposure to PM 2.5 -bound metals and age-adjusted FBC incidence rate at the census tract level in New Mexico from 1997 to 2019. FBC records were obtained from the New Mexico Tumor Registry. Annual metal exposure intensities for chromium, cobalt, copper, manganese, and mercury were estimated using a calibrated Emission Weighted Proximity Model (EWPM) over a 10-year pre-diagnosis window. Generalized Estimating Equations (GEE) with Gaussian estimation was used to estimate rate ratio (RR) for the association between PM 2.5 -bound metal exposure and FBC incidence in New Mexico. Exposure to PM 2.5 -bound chromium (adjusted RR 1.07, 95% CI: 1.05, 1.08), cobalt (adjusted RR 1.08, 95% CI: 1.05, 1.11), copper (adjusted RR 1.06, 95% CI: 1.04, 1.07), manganese (adjusted RR 1.05, 95% CI: 1.02, 1.08), and mercury (adjusted RR 1.05, 95% CI: 1.03, 1.07) show significant associations with increased FBC incidence rate. When exposure was categorized as unexposed, low, medium, and high groups, a significant increasing trend was observed across all five metals. Long-term exposure to multiple PM 2.5 -bound metals is associated with elevated FBC incidence rate in New Mexico. These findings highlight the need for further research and to biologically validate the observed associations and clarify potential mechanisms linking PM 2.5 -bound metal exposure to FBC incidence risk.

Toward improved conservation risk assessments in the marine aquarium fish trade: Reply to Biondo and Calado (2026) - Bing Lin; Andrew L. Rhyne; Michael Tlusty; Yiwen Zeng; Bryan To; Robert J. Holmberg; David S. Wilcove (Conservation Biology, 2026)

The Response of Soil Enzyme Activities to Functionally-Diverse Cover Crop Mixtures in Citrus Orchards Depends on Cover Crop Duration in Sandy Soils - Kendall Mackin; Sarah L. Strauss; Yang Lin; Yaslin Gonzalez; James Colee; Gabriel Maltais-Landry (Journal of Soil Science and Plant Nutrition, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Dietary Patterns Associated With Weight Loss Among Patients With Colorectal Cancer During the First 6 Months After Diagnosis: A Cross-Sectional Analysis From the ColoCare Study - Rachel Hoobler; Fred K. Tabung; Tengda Lin; Biljana Gigic; Kristen S. Smith; Kary Woodruff; Sylvia L. Crowder; Sheetal Hardikar; Doratha A. Byrd; Adriana M. Coletta; Alejandro Sanchez; Amandine Chaix; et al. (Journal of the Academy of Nutrition and Dietetics, 2026)

Salt-assisted liquid-liquid extraction for valorization of hydrothermal carbonization process water - San Lin Htun; Shivani Parmar; Matteo Pecchi; Jillian L. Goldfarb (Journal of Cleaner Production, 2026)

Proteomic comparison of human neural cell-derived extracellular vesicles and parental cells from Alzheimer’s disease and cognitively normal individuals - Jia-Yan Xin; Jie Liu; Hao-Min Dong; Hai-Lun Yu; Zhong-Song Xiao; Jian-Ni Hu; Qiu Jiang; Yu-Peng Zhu; Lin Feng; Yun Feng; Yu-Juan Jia; Zi-Yu Yuan; et al. (Science China Life Sciences, 2026)

Not the same plastics: Comparing abundance and composition of marine macro-litter in mangroves and beaches in Southeast Asia - Jenny Fong; Ashwini Suresh Kumar; Cheng Ling Lim; Muhammad Reza Cordova; Pham T. Hoa; Deo Florence L. Onda; Kim John N. Balboa; Norchel Corcia F. Gomez; Mochamad Riza Iskandar; Muhammad Taufik Kaisupy; Swietenia Puspa Lestari; Pham Ngoc; et al. (Journal of Environmental Management, 2026)

Correction: The potent human CAR activator CITCO is a non-genotoxic hepatic tumour-promoting agent in humanised constitutive androstane receptor mice but not in wild-type animals - C. J. Henderson; A. W. McLaren; A. K. MacLeod; D. Lin; A. R. Cameron; L. R. Chatham; J. Moggs; F. Inesta‑Vaquera; John P. Thomson; Richard R. Meehan; P. Chakravarty; M. Schwarz; et al. (Archives of Toxicology, 2026)

Computational approaches for identifying quorum sensing inhibitors - Lin Zhong; Shwetlaxmi Patil; B. Lakshmi; Pratibha Singh; Satish Kumar Rajasekharan; S. L. Rath; Vinothkannan Ravichandran (Molecular Diversity, 2026)

Synergistic activation of lithium slag using solid-waste-derived alkali and sodium sulfate: Towards high-performance low-carbon cementitious materials - Yannian Zhang; Lin Zhang; Qingjie Wang; Moncef L. Nehdi; Zhijun Li; Baoyuan Wang; Yunzhi Shang; Xinyu Dong (Sustainable Chemistry and Pharmacy, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Stable neodymium isotopic composition of the upper continental crust through time from ancient glacial diamictites and Holocene marine sediments - Xiaoxiao Yu; Jianghao Bai; Gangjian Wei; Mang Lin; Roberta L. Rudnick (Geochimica et Cosmochimica Acta, 2026)

Assessing Potential Data Sources for Landscape-scale Terrestrial Biodiversity Indicators - Tom Bradfer-Lawrence; Meriel Harrison; Adham Ashton-Butt; Sophie Bennett; Robin J. Boyd; Ella Browning; Graeme Buchanan; Adam Fraser; Sian E. Green; Robert Hawkes; Becky E. Heath; Pen-Yuan Hsing; et al. (Environmental Management, 2026)

Industrial air pollution and lung and bronchus cancer survival in New Mexico, USA - Xi Gong; Yanhong Huang; Charles L. Wiggins; Angela L. W. Meisner; Yan Lin; Li Luo (Cancer Causes & Control, 2026)
Purpose Lung and bronchus cancer (LBC) is the leading cause of cancer-related deaths. This study examines the relationship between exposure to industrial air pollution and lung and bronchus cancer survival (LBCS) in New Mexico, USA, from 1990 to 2019. Methods This retrospective cohort study included data from 18, 273 lung and bronchus cancer patients. Residential exposure to nine industrial air pollutants was estimated for each patient using the Emission Weighted Proximity Model (EWPM), which integrates industrial air emission data and air quality monitoring data form the U.S. Environmental Protection Agency’s (EPA). Cox proportional hazards modeling was applied to identify industrial air pollutants as decreased LBCS risk factors, adjusting for age at diagnosis, gender, cancer stage, race/ethnicity, smoking prevalence, and urbanization of residential address. Results Results show that residential exposure to 1,1,1-trichloroethane and cobalt during the survival period was significantly associated with decreased LBCS (adjusted hazard ratio [adjHR] for 1,1,1-trichloroethane: 1.06, 95% CI: 1.04, 1.09 and adjHR for cobalt: 1.06, 95% CI: 1.03, 1.09) compared to those unexposed among all patients. When exposure levels were categorized into four groups (unexposed, low, medium, high) based on annual average exposure during the survival period, the associations remained consistent. Conclusion This study underscores the negative influence of industrial air pollution on LBCS and emphasizes the need for targeted public health interventions in high-exposure areas.

Building trust in the integration of artificial intelligence into chemical risk assessment: findings from the 2024 ECETOC workshop - Timothy W. Gant; Alistair Boxall; Daniel Burgwinkel; Maryam Zare Jeddi; Ivo Djidrovski; Steffi Friedrichs; Barry Hardy; Thomas Hartung; Daniela Holland; Andreas Karwath; Anne Kienhuis; Nicole Kleinstreuer; et al. (Archives of Toxicology, 2026)
Artificial Intelligence (AI) is increasingly influencing chemical risk assessment, enabling faster, more comprehensive, and potentially more ethical assessments. The application of AI in chemical risk assessment refers to both generative and predictive algorithms encompassing machine learning, to analyse complex chemical, biological, and environmental data and provide insights into adverse effect potential for humans and ecosystems. AI systems support the prediction of chemical hazards, exposure levels, and adverse effects by learning from experimental results, mechanistic models, and regulatory datasets, thereby enhancing the efficiency of safety evaluations. In October 2024, ECETOC held an international workshop, with experts from academia, industry, and regulatory bodies, to reflect upon the historical challenges in integrating multidimensional omics technologies into chemical regulation and explore the current capabilities and future potential of AI in toxicology and regulatory science. Discussions emphasised that implementation of Findable, Accessible, Interoperable, and Reusable (FAIR) data principles is not just a best practice but rather a prerequisite for building transparent, reliable, and unbiased AI systems. The reliability of AI in producing scientifically valid and socially responsible outcomes depends fundamentally on the availability of FAIR data. However, ensuring trustworthiness also requires robust governance frameworks that go beyond data and human oversight. Critical enablers of responsible AI in chemical risk assessment are rigorous governance, explainability, fit-for-purpose applications, and human oversight. ECETOC supports the development of flexible and iterative frameworks advancing development, validation, transparency, accountability, and trust in AI applications in chemicals regulation.

Host and Environmental Drivers of Gut Microbiome Variation in Wild Anolis Lizards - Yanileth F. López Tacoaman; Maria Alcivar; Karla Alujević; Leah Bakewell; John David Curlis; Anabarbara Gonzalez; Noah D. Gripshover; Samir Gulati; Renata M. Pirani; Noa Ratia; Daniel Romero; Kelly Lin Wuthrich; et al. (Molecular Ecology, 2026)
Animals maintain close associations with diverse microbiota that inhabit their digestive tracts, and these associations can profoundly affect host physiology and fitness. Gut microbiome composition is shaped by both host traits and environmental factors, yet the relative importance of these forces remains unclear in many taxa, including squamate reptiles (lizards and snakes). To address this gap, we analysed the gut microbiomes of seven species of Anolis lizards in the lowland tropical rainforest of central Panama. We sought to determine how environmental and host species characteristics shaped gut microbiome composition. Specifically, we examined (1) interspecific variation in the anole gut microbiome, (2) the relative roles of environment and host species in shaping gut microbiomes across two study locations, and (3) patterns of phylosymbiosis. We found that host‐related factors (species identity, body size, and phylogenetic distance) were significant predictors of the composition of Anolis gut microbiomes. However, environmental factors, including locality and year of sampling (associated with temperature, humidity, and precipitation), also exerted significant effects. We detected evidence of phylosymbiosis, but this pattern was moderate, possibly due to the strong effect of environmental variation. Our work contributes to the growing body of literature on lizard gut microbiomes by using comparative observations across habitats and species to identify the factors that shape these communities in the wild.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Contrasting behaviour in geogenic degassing along an active segment of the East Anatolian fault zone (Türkiye) - G. Yüce; W. D'Alessandro; C.C. Fu; F. Italiano; M. İçhedef; H. Elmacı; B. Kürkcüoğlu; B. Kahraman; A. Demirtaş; L.H. Lin; D. Yasin; Ş. Gürboğa; et al. (Applied Geochemistry, 2026)

Full Manure Recycling Risks an 18% Rise in China's Cropland N 2 O Emissions Without Improved Management - Shidi Ba; Zhaohai Bai; Lin Ma; Davey L. Jones; David R. Chadwick (Global Change Biology, 2026)
Cropland fertilization is the largest anthropogenic source of nitrous oxide (N 2 O‐N) emissions in China and could be mitigated through manure substitution. However, accurate quantification of N 2 O‐N losses under different combinations of manure and chemical fertilizer applications remains challenging due to limited national data, oversimplified methods of estimation, and neglect of the nitrogen (N) source (chemical‐N and manure‐N) interaction effects under mixed fertilization on N 2 O‐N production processes. Using a dataset consisting of 2186 observations across China, we developed N 2 O‐N models for fertilized (chemical fertilizer and manures) croplands incorporating climate, soil, fertilization and cropping variables, with particular emphasis on the manure component, through machine‐learning approaches. Model simulations estimated a median N 2 O‐N flux of 1.1 kg ha −1 and a total national N 2 O‐N loss of 243.7 Gg in 2019, with a hotspot in Northcentral China. During 2000–2019, N 2 O‐N losses were driven mainly by annual total N input. By 2050, merely pursuing 100% manure recycling without considering improved manure‐N use efficiency could lead to an 18% increase in N 2 O‐N losses compared with 2019. Hence, this study provides a high‐resolution modeling framework to predict how developments in manure substitution will affect the magnitude and spatial distribution of N 2 O‐N losses. We also demonstrate that future manure substitution policies will need to promote improved manure nutrient management at the same time as greater manure recycling rates.

Lagging theory for periodic hydraulic head signals in aquifers - Ying-Fan Lin; Barret L. Kurylyk (Journal of Hydrology, 2026)

Promotion of CeO2 in Mn3O4-CeO2 composite towards the catalytic oxidation of Butyl acetate - Fuding Tan; Peng Liu; Yahao Liu; Shiling Yang; Xiaoju Lin; Xiaoliang Liang; Steven L. Suib; Daiqi Ye (Journal of Environmental Sciences, 2026)

The high oxygen fugacity of the Chang’e-5 lunar basalt: Implications for redox stratification of the lunar mantle - Jintuan Wang; Hongluo L. Zhang; Le Zhang; Yonghua Cao; Zhendun Qi; Pengli He; Mang Lin; Yi-Gang Xu (Geochimica et Cosmochimica Acta, 2026)

Prenatal urinary biomarkers of metal and metalloid exposure and child neurodevelopmental outcomes in Puerto Rico - Savannah M. Sturla Irizarry; Amber L. Cathey; Emily Zimmerman; Wei Hao; Yi-Ting Lin; Bhramar Mukherjee; Zaira Y. Rosario Pabón; Gredia Huerta Montañez; Carmen M. Vélez Vega; Akram N. Alshawabkeh; José F. Cordero; John D. Meeker; et al. (Environmental Research, 2026)

Microbial synthesis of picolinic acid via retro-biosynthetic pathway engineering - Cui Guo; Nguyen N.T. Luu; Ashley Tseng; Maryem M. Adwer; Abdul L. Khan; Eunhae Kwon; Yuheng Lin (Chemical Engineering Journal, 2026)

Calcite TLM as a new natural reference material for in situ U-Pb geochronology and its geological implications - Tianyi Li; Ranran Chen; Shitou Wu; Rolf L. Romer; Nick M.W. Roberts; Kerstin Drost; David Chew; Marcel Guillong; Qian Ma; Yahui Yue; Shuangjian Li; Bohang Xie; et al. (Chemical Geology, 2026)

Quantifying situation-dependent uncertainty in tropical cyclone track forecasts with a recurrent neural network approach - Hsiao-Chung Tsai; Fang-Yi Lin; Yung-Lan Lin; Nai-Ning Hsu; Treng-Shi Huang; Russell L. Elsberry (Natural Hazards, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Price transmission and long-term effects of avian influenza on Taiwan’s egg market - Ning Chen; Dustin L. Pendell; Chia-Lin Chang (Preventive Veterinary Medicine, 2026)

Artificial neural network modeling for adsorption processes in carbon capture from wet flue gas - H. Si; J.K. Wu; S. Chen; J.Y. Yong; X.J. Lin; M.X. Fang; L. Jiang (Gas Science and Engineering, 2026)

Resistance of shallow soil carbon to both short-term isolated and recurrent droughts in two semi-arid grasslands - Taofeek O. Muraina; Niwu Te; Saheed O. Jimoh; Robert Griffin-Nolan; Lin Song; Jiaqi Chen; Yuan Shi; Ahmed A. Amisu; Tilak Chaudhary; Qiang Yu; Melinda D. Smith; Alan K. Knapp; et al. (Oecologia, 2026)

Extent of threats to marine fish from the online aquarium trade in the United States - Bing Lin; Yiwen Zeng; Bryan To; Robert J. Holmberg; Andrew L. Rhyne; Michael Tlusty; David S. Wilcove (Conservation Biology, 2026)
The global marine aquarium hobby is a multibillion‐dollar industry, largely driven by demand from the United States. Much of this trade occurs online. We web scraped 4 major US‐based e‐commerce platforms selling marine aquarium fish to determine the retail price and source (wild capture, aquaculture, or both) of 13 families of ray‐finned marine fish ( Actinopterygii ). We supplemented this with ecological and economic trait data from FishBase and the International Union for Conservation of Nature (IUCN). Across all platforms and 13 popular fish taxonomic families, we found 734 unique species for sale, 89.2% (655 species) of which were sourced exclusively from the wild. A total of 45 species were of conservation concern (20 threatened species and 25 additional species with decreasing population trends), 38 of which were sourced solely from the wild. Retail price was significantly correlated with source, body length, minimum occupied depth, and schooling behavior. A further 100 species for sale were not listed as being in the aquarium trade in FishBase or by the IUCN, indicating incomplete information on this fishery in 2 important databases. For 58 species (encompassing 71 variants) with both wild‐caught and captive‐bred individuals for sale, aquaculture fish were a mean 28.1% (95% confidence interval 15.3) cheaper than their wild‐caught counterparts.

An in vitro-in silico workflow for predicting renal clearance of environmental chemicals and drugs - Courtney Sakolish; Hsing-Chieh Lin; Haley L. Moyer; Lucie C. Ford; Charles H. Christen; Barbara A. Wetmore; Michael J. DeVito; Philip Hewitt; Stephen S. Ferguson; Farah Raad; Ivan Rusyn; Weihsueh A. Chiu (Toxicology, 2026)

Hydrophobic neutral and basic fractions of organic fertilizer-derived dissolved organic matter promote phosphorus mobilization in paddy soils - Haibo Wang; Xipeng Liu; Songcan Chen; Chengliang Sun; David R. Chadwick; Davey L. Jones; Xianyong Lin (Soil and Tillage Research, 2026)

Plasticity and regional heterothermy of upper thermal tolerance in the ring-necked snake - Christian L. Cox; Kelly Lin Wuthrich; Dareen Aloudeh; Samuel J. Baker; Anna G. Climo; Alexa F. Gross; Christian W. Kizer; Zoe M. Korff; Oscar Melendez Vera; Veronica Y. Silva; Alexis M. Spans; Grace R. Thilenius; et al. (Journal of Thermal Biology, 2026)

A new model for the global patterning of spores and pollen grains - Kun L. Yang; Zhu L. Yang; Yang Luo; Jia Y. Lin; Hong Wang; Pan Meng Wang (Protoplasma, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

Association between prenatal exposures to per- and polyfluoroalkyl substances and early language development in the ECHO cohort - Patricia Cintora; Lesliam Quirós-Alcalá; Adaeze W. Nzegwu; Sudhi Upadhyaya; Megan Woodbury; Sarah Dee Geiger; Rachel Morello-Frosch; Anne L. Dunlop; Theresa M. Bastain; Anne P. Starling; Dana Dabelea; Carlos A. Camargo; et al. (NeuroToxicology, 2025)

Transforming gastrointestinal health with probiotic fermented milk: a systematic review and meta-analysis - Ngan Thi Kim Nguyen; Yu-Hsin Chang; Lee-Yuan Lin; Philippe Noirez; Roma Panwar; Tzu-Wen L. Cross; Nguyen-Phong Vo; Shyh-Hsiang Lin (International Dairy Journal, 2025)

Microbial, genetic, and urban drivers of ant invasions - Wei-Jiun Lin; Po-Wei Hsu; Edward L Vargo; Chin-Cheng Scotty Yang (Current Opinion in Insect Science, 2025)

A major and stable QTL confers impatiens necrotic spot virus resistance in lettuce cv. Eruption - Santosh Nayak; Kelley L. Richardson; Renée L. Eriksen; Daniel K. Hasegawa; William M. Wintermantel; Manoj Sapkota; Xuemei Tang; Shufen Chen; Meng Lin; Dongyan Zhao; Craig T. Beil; Moira J. Sheehan; et al. (Theoretical and Applied Genetics, 2025)
Key message A large effect and environmentally stable QTL was identified on LG2 that confers high levels of INSV resistance in lettuce cultivar Eruption. Abstract Impatiens necrotic spot virus (INSV) has recently emerged as a major threat to lettuce production in the Salinas Valley of California, the region which contributes over 60% of the US national supply. This thrips-transmitted virus can infect lettuce plants at any growth stage, causing premature death or a total loss of marketability. Both INSV and its thrips vector have broad host ranges, which complicate disease management. Utilizing genetic resistance is the most sustainable approach; however, complete immunity has not been identified and the genetic basis of resistance to INSV in lettuce remains poorly understood. This study aimed to identify quantitative trait loci (QTL) and elucidate the underlying mechanism of INSV resistance in ‘Eruption,’ a lettuce cultivar exhibiting highly stable partial resistance across environments. Using 162 F 6:8 recombinant inbred lines (RILs) developed from a cross between moderately susceptible ‘Reine des Glaces’ and ‘Eruption,’ and a genetic linkage map comprising 1598 single nucleotide polymorphism (SNP) markers, phenotypic data collected from field and greenhouse experiments consistently revealed a highly significant, major QTL on linkage group 2. This QTL exhibited partial dominance with additive effects, explaining up to 61% of the total phenotypic variation for INSV disease severity. Furthermore, INSV resistance was found to be highly heritable, with heritability estimates of up to 0.89, indicating strong genetic control. Results of this study are crucial for fine mapping and the development of marker-assisted selection assays to accelerate the breeding of more advanced INSV-resistant lettuce cultivars.

Pre-surgery gut microbial diversity and abundance are associated with post-surgery onset of cachexia in colorectal cancer patients: the ColoCare Study - Mmadili N. Ilozumba; Maria F. Gomez; Tengda Lin; Caroline Himbert; June L. Round; W. Zac Stephens; Christy A. Warby; Sheetal Hardikar; Christopher I. Li; Jane C. Figueiredo; Victoria Damerell; Gary C. Fillmore; et al. (Cancer Causes & Control, 2025)
Background Cachexia accounts for about 20% of all cancer-related deaths and it is indicative of poor prognosis and progressive functional impairment. The role of the gut microbiome in the development of cachexia in colorectal cancer (CRC) patients has not been established. Methods Pre-surgical stool samples from n = 103 stage I–III CRC patients in the ColoCare Study were analyzed using 16S rRNA gene sequencing (Illumina) to characterize fecal bacteria. We calculated estimates of alpha- and beta-diversity and a priori- and exploratory-selected bacterial relative abundance. Using Fearon criteria, cachexia onset at 6 months post-surgery was defined as > 5% weight loss over the past 6 months and/or body mass index (BMI) of < 20 kg/m 2 and weight loss of > 2%. Associations of microbial metrics with cachexia onset were estimated using multivariable logistic regression models. Results Higher alpha-diversity was positively associated with cachexia onset, with stronger associations in females, patients < 65 years, those receiving adjuvant treatment, consuming high fiber, or with energy intake outside USDA recommendations ( p < 0.05). Porphyromonas (OR = 0.51, 95% CI 0.26–0.89, p = 0.03) and Actinomyces (OR = 0.72, 95% CI 0.48–1.03, p = 0.08) were inversely associated with cachexia, although the association for Actinomyces did not reach statistical significance. Stratified analyses revealed a stronger inverse association between Porphyromonas and cachexia onset in males, patients with rectal or stage III tumors, those receiving neoadjuvant treatment, physically inactive individuals, and those consuming low fiber. However, these associations did not reach statistical significance (0.05 ≤ p < 0.10). Conclusion Higher gut microbial alpha-diversity and lower relative abundances of the genera Porphyromonas and Actinomyces in pre-surgery stool samples were associated with onset of cachexia in CRC patients six months post-surgery. This is the first study to explore a link between the gut microbiome and cachexia in CRC patients, providing novel insights into the biology of cachexia and potential clinical interventions.

Hydrogen, single-carbon compounds, and thermal regime in the oceanic ultramafic-dominated lithosphere: insights from a deep borehole on the Atlantis Massif - Susan Q. Lang; C. Geoffrey Wheat; Kristin L. Dickerson; Mark K. Reagan; Ivan P. Savov; Jordyn A. Robare; William J. Brazelton; Johanna Suhonen; Oscar Cavazos; Andrew McCaig; Peter Blum; Natsue Abe; et al. (Geochimica et Cosmochimica Acta, 2025)

Fetal response to maternal exposures of environmental chemicals: Utility of a four-cell human feto-maternal interface organ-on-chip - Haley L. Moyer; SungJin Kim; Bowie P. Lam; Lauren S. Richardson; Han-Hsuan D. Tsai; Lucie C. Ford; Hsing-Chieh C. Lin; Weihsueh A. Chiu; Ramkumar Menon; Arum Han; Ivan Rusyn (Chemico-Biological Interactions, 2025)

Metallogenic age and geological significance of the Jiazishan Mo deposit, Inner Mongolia, China - Z. L. Wang; J. Z. Yang; K. Q. Zhao; Y. G. Fu; J. W. Gao; Y. M. Deng; L. J. Lin; Z. Duan (Australian Journal of Earth Sciences, 2025)

Associations between brominated and organophosphate flame retardant levels and inflammatory biomarkers in maternal blood, cord blood, and placental tissue at mid-gestation - Vince Nguyen; Neha Sehgal; Lin Li; Dana E. Goin; Rachel Morello-Frosch; Tracey J. Woodruff; Julia Varshavsky; June-Soo Park; Stephanie L. Gaw; Joshua F. Robinson; Stephanie M. Eick (Science of The Total Environment, 2025)

Insufficient telomeric DNA damage response promotes chromosomal instability in aged oocytes - Tianqi Cao; Simiao Liu; Fang Wang; Min Gao; Wenlian Wu; Yanling Qiu; Ming Mu; Tengteng Xu; Jinkun Wen; Yuxi Chen; Haiying Liu; Xiqian Zhang; et al. (Science Bulletin, 2025)

Identification of a Potent Antibiotic Compound from Geodermatophilus Bacteria - Sunmin Woo; Brendan Lin; Paul M. Dunman; Cassandra L. Quave (Phytochemistry Letters, 2025)

Fine root trait dynamics and their relationships with productivity across grasslands under extreme drought - Yuan Shi; Taofeek O. Muraina; Saheed O. Jimoh; Niwu Te; Lin Song; Jiaqi Chen; Hongqiang Wang; Qiang Yu; Xiaoan Zuo; Xingguo Han; Wentao Luo; Scott L. Collins (Oecologia, 2025)

Molecular evidence for microbial methane oxidation associated with complete ammonia oxidizers in paddy soils - Zongjing Kang; Shuling Wang; Lu Lu; Xia Zhu-Barker; Junji Yuan; Yongxin Lin; Zhongjun Jia; Alan L. Wright; Andreas Kappler; Sara Kleindienst; Xianjun Jiang (Soil Biology and Biochemistry, 2025)

Toward more accurate quantification: A review of global large river basin management policies - Yi-Lin Zhao; Han-Jun Sun; Jie Ding; Zhen Hong; Ji-Wei Pang; Guene L. Razack; Nan-Qi Ren; Shan-Shan Yang (Journal of Environmental Management, 2025)

Assessing the relationship between digital service trade and carbon emissions: evidence from RCEP countries - H. Liu; L. Liu; L. Lin (International Journal of Environmental Science and Technology, 2025)

Variation in uptake of sodium glucose cotransporter 2 inhibitors and glucagon-like peptide-1 receptor analogues in adults with type 2 diabetes at high cardiovascular risk - Juliana de Oliveira Costa; Jialing Lin; Tamara Y. Milder; Alys Havard; Jerry R. Greenfield; Richard O. Day; Brendon L. Neuen; Alice A. Gibson; Jedidiah I. Morton; Julian W. Sacre; Sallie-Anne Pearson; Michael O. Falster (European Journal of Clinical Pharmacology, 2025)
Purpose We quantified variation in the uptake of sodium-glucose co-transporter 2 inhibitors (SGLT2i) and glucagon-like peptide-1 receptor analogues (GLP-1RA) across sociodemographic, behavioural and clinical characteristics of people with type 2 diabetes (T2D) at high cardiovascular risk. Methods We used the 45 and Up Study survey data (2018–2020) linked to dispensing and service claims for 10,171 people with T2D (56% male, median age of 72 years, median diabetes duration of 11 years). We calculated the prevalence of GLP-1RA and SGLT2i use within 1 year and used logistic regressions to assess associations with each participant characteristic. Results We found that 2270 (22.3%) people with T2D used SGLT2i and 679 (6.7%) used GLP-1RA. Use of these medicines was higher in people diagnosed with diabetes for a longer period, a high number of comorbidities and survey year, decreased in older people, and varied by sex. After adjusting for these factors, utilisation of these medicines was lower among people who consume alcohol (versus non-drinkers) and higher among those with overweight or obesity. SGLT2i use was also higher in people who were less physically active or had established cardiovascular disease and lower in people with anxiety or depression. GLP-1RA use was higher among people with poorer health and lower in people born outside Australia/New Zealand. Conclusion Prevalent use of SGLT2i and GLP-1RA was suboptimal and varied across clinical characteristics and behavioural risk factors. While some variation reflects complexities in prescribing for this older population, there remains opportunity for optimised prescribing within this high-risk population.

Metrics of Urbanicity and Rurality in US-Based Epidemiologic Studies of Ambient Temperature and Health: A Scoping Review - Nicholaus P. Johnson; Alexandra Del Favero-Campbell; Amruta Nori-Sarma; Audrey Amezcua-Smith; Brandon Lewis; Chen Chen; Chengyi Lin; Damien Foo; Garam Byun; Hayon Michelle Choi; Honghyok Kim; Jesse D. Berman; et al. (Current Environmental Health Reports, 2025)

Nicotinamide riboside combined with exercise to treat hypertension in middle-aged and older adults: a pilot randomized clinical trial - Yi Lin; Rola S. Zeidan; Stephanie Lapierre-Nguyen; Hannah M. Costello; Stephen D. Anton; Thomas W. Buford; Demetra D. Christou; Michelle L. Gumz; Christiaan Leeuwenburgh; Christopher R. Martens; Mary M. McDermott; Marie E. Migaud; et al. (GeroScience, 2025)
Aerobic exercise lowers blood pressure (BP) with varying effects in hypertensive adults, potentially due to age-related nicotinamide adenine dinucleotide (NAD) metabolism dysregulation. This pilot randomized clinical trial (RCT) tested the efficacy of combining aerobic exercise with the NAD booster nicotinamide riboside (NR) to enhance BP control. In this double-blinded RCT, 54 sedentary adults (≥ 55 years) with mean daytime systolic BP (SBP) ≥ 130 mmHg were randomized to 6 weeks of 1000 mg/day of NR combined with 3 days/week of supervised 30-min walking exercise (NR + Ex), Placebo combined with the same exercise regimen (PL + Ex), or NR alone (NR). The primary outcome was daytime SBP. Other outcomes included pulse wave velocity (PWV), NAD catabolites, and nighttime BP. The primary comparison was between NR + Ex and PL + Ex. Of 54 participants (mean age 67 years, 61% female), 49 (NR + Ex: n = 15, PL + Ex: n = 16, NR: n = 18) completed all study visits (93% adherence to exercise and 90% to supplementation). NR + Ex (mean change = 5.19 ± 13.2 mmHg) did not reduce SBP more than PL + Ex (− 2.71 ± 10.5 mmHg). NR + Ex (− 0.31 ± 0.77 m/s) showed a trend toward a greater reduction in PWV. Levels of NAD catabolites were higher in NR groups. In a post hoc analysis, NR + Ex showed a trend toward greater nighttime BP reductions (systolic: − 9.6 ± 9.22; diastolic: − 4.51 ± 7.12 mmHg) in participants without antihypertensive medications. NR + Ex was not superior to PL + Ex in reducing BP in hypertensive middle-aged and older. However, trends toward greater nighttime BP reduction in NR + Ex in participants without antihypertensive medication warrant further investigation in a Phase IIb RCT. Graphical Abstract

Socioeconomic impacts linked to land use and land use changes affecting blue carbon ecosystems in Southeast Asia: A systematic map - Maryam Jamilah; Amani Becker; Soon Loong Lee; T.E. Angela L. Quiros; Su Yin Chee; Claire Evans; Yu Yang Tan; Lian Lin Ti; Irsyad Pishal; Amy Yee Hui Then (Ocean & Coastal Management, 2025)

Psychosocial stress and associations with inflammation in mid-gestation maternal, fetal, and placental tissue - Neha Sehgal; Lin Li; Dana E. Goin; Jessica Chen; Unurzul Jigmeddagva; Rachel Morello-Frosch; Tracey J. Woodruff; Stephanie L. Gaw; Joshua F. Robinson; Stephanie M. Eick (Reproductive Toxicology, 2025)

Celebrating the fifth edition of the International Symposium on Fungal Stress – ISFUS, a decade after its 2014 debut - Alene Alder-Rangel; Amanda E.A. Rangel; Arturo Casadevall; Asiya Gusa; Chaoyang Xue; Charles M. Boone; Chris Todd Hittinger; Claudio A. Masuda; Consuelo Olivares-Yañez; Deborah Bell-Pedersen; Erica J. Washington; Gerhard Braus; et al. (Fungal Biology, 2025)

Revealing how urban morphology at urban planning and design stage influence energy using urban building energy model - F. Lin; L. Luo; Q. Gu; S. Hao; W. Wang (International Journal of Environmental Science and Technology, 2025)

Status quo and predictions of the most and least discussed sustainable development goals - H.-H. Chung; F.-L. Chung; S.-M. Lin (International Journal of Environmental Science and Technology, 2025)

Corrigendum to “Structural evolution of the southern Swayze greenstone belt, Superior Craton: Implications for the Neoarchean crustal dynamics” [J. Struct. Geol. (2025) 105373] - Qǐháng Wú; Shoufa Lin; Thomas Gemmell; Sandra L. Kamo; Jian Zhang; Lijun Wang (Journal of Structural Geology, 2025)

Drivers of state legislative actions restricting foreign holdings of U.S. agricultural land - Lin Lin; David L. Ortega (Food Policy, 2025)

Quantitative diagnostics in the presence of image distortion by artifacts due to metal implants using computed tomography and targeted X-ray absorption spectrometry with a contrast agent - A. G. Turyanskiy; R. M. Ainetdinov; Kyaw Zaw Lin; V. M. Senkov; M. Z. Ziyatdinova; L. Yu. Nikitina (Biomedical Engineering, 2025)

Image-well solution for island aquifers with pumping, recharge, and complex coastlines - Ying-Fan Lin; Barret L. Kurylyk; Adrian D. Werner; Chih-Yu Liu; Cristina Solórzano-Rivas; Jun-Hong Lin (Advances in Water Resources, 2025)

International Consortium on Ageing-Related Pathologies (ICCARP) Audiovestibular Group: fostering international consensus to refine International Classification of Diseases (ICD-11) codes for hearing loss across the life course - Dialechti Tsimpida; Michael A. Akeroyd; Barry L. Bentley; Shuvarthi Bhattacharjee; Michael R. Bowl; Emma Broome; Stuart R. G. Calimport; Sian Calvert; Gary Christopher; Tom Dening; Silvia Di Bonaventura; Ankita Goswami; et al. (GeroScience, 2025)

Structural evolution of the southern Swayze greenstone belt, Superior Craton: Implications for the Neoarchean crustal dynamics - Qǐháng Wú; Shoufa Lin; Thomas Gemmell; Sandra L. Kamo; Jian Zhang; Lijun Wang (Journal of Structural Geology, 2025)

Characterizing ancient seep environments by in-situ sulfur isotope composition of authigenic pyrite - Qinyi Zhang; Zhiyong Lin; Harald Strauss; Tingting Chen; Yang Lu; James L. Goedert; Jörn Peckmann (Chemical Geology, 2025)

Temperature matters: Acute and latent toxicity of diluted bitumen to developing salmon is potentiated by a modest increase in water temperature - Derin M. Çalık; Feng Lin; Mackenzie Edgar; Anthony P. Farrell; Christopher J. Kennedy; Todd E. Gillis; Sarah L. Alderman (Aquatic Toxicology, 2025)

Influence of infant feeding practices on childhood dietary patterns in Upstate KIDS - Priscilla K. Clayton; Diane L. Putnick; Tzu-Chun Lin; Edwina H. Yeung (Appetite, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Woody plant cell walls: Fundamentals and utilization - Wei Li; Ying-Chung Jimmy Lin; Ying-Lan Chen; Chenguang Zhou; Shuang Li; Nette De Ridder; Dyoni M. Oliveira; Lanjun Zhang; Baocai Zhang; Jack P. Wang; Changzheng Xu; Xiaokang Fu; et al. (Molecular Plant, 2025)

Tidal signal propagation in coastal aquifers considering semi-permeable boundaries and partial penetration effects - Fu-Kuo Huang; Ying-Fan Lin; Grace S. Wang; Barret L. Kurylyk (Journal of Hydrology, 2025)

Health risk assessment of dietary cadmium exposure based on cadmium bioavailability in food: Opportunities and challenges - Di Zhao; Guo-Bin Lin; Chenjing Liu; Albert L. Juhasz; Lena Q. Ma (Journal of Hazardous Materials, 2025)

Nanoengineered cellulose for sustainable selective separation of precious metals from electronic waste - Roya Koshani; Shang-Lin Yeh; Mica L. Pitcher; Lucas Lawrence Franz; Mitchell Robert Davis; Min Ju Park; Said Khalifa Ahmed Al Qassabi; Joelson Patricio Manuel Alves; Younes Shekarian; Hevapathiranage Chandima Sudantha Subasinghe; Sarma V. Pisupati; Mohammad Rezaee; et al. (Chemical Engineering Journal, 2025)

The potent human CAR activator CITCO is a non-genotoxic hepatic tumour-promoting agent in humanised constitutive androstane receptor mice but not in wild-type animals - C. J. Henderson; A. W. McLaren; A. K. MacLeod; D. Lin; A. R. Cameron; L. R. Chatham; J. Moggs; F. Inesta-Vaquera; John P. Thomson; Richard R. Meehan; P. Chakravarty; M. Schwarz; et al. (Archives of Toxicology, 2025)
A large number of drugs and compounds produced by the chemical and agrochemical industry, often referred to as ‘non-genotoxic carcinogens’ (NGC), score as tumour promotors in rodent models. It is unclear whether these compounds act similarly in humans. The most extensively investigated compounds have been the anti-convulsive drugs, phenobarbital (PB), and phenytoin. Liver tumours induced by PB are dependent upon the activation of the constitutive androstane receptor (CAR). However, marked species differences in CAR activation by exogenous chemicals exist with some being much more potent activators of human CAR, e.g., 6-(4-chlorophenyl)imidazo[2,1-β][1,3]thiazole-5-carbaldehyde-O-(3,4-dichlorobenzyl)oxime (CITCO). We have compared CITCO-induced tumour formation in the livers of mice in which murine CAR has been replaced with its human counterpart. Our findings reveal that CITCO-dependent liver tumours are only formed in mice-expressing human CAR and not in wild-type animals. In addition, contrary to one of the proposed mechanisms of NGC carcinogenicity, we show that CITCO did not induce a hyperplastic response in the liver of the humanised mice. These data raise some key questions about the mechanism of action of NGCs and identify the limitations of current rodent carcinogenicity test systems in relation to risk assessment.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Constraints of the paleowind directions on the paleogeography of the North China, South China and Tarim cratons during the Ediacaran Period - C. L. Hu; Z. Q. Lin; J. A. Quaye; X. B. Fu (Australian Journal of Earth Sciences, 2025)

Polyelectrolyte nanofiltration membranes for base separation and recovery - Joshua L. Livingston; Abigail Cafferty; Riley Miller; Allison V. Cordova-Huaman; Jin Zhang; G. Kane Jennings; Shihong Lin (Water Research, 2025)

Exploring calcium pillaring of O3-type NaNi0.9Ti0.1O2 cathodes to advance Na-ion battery technology - Siyu An; Leonhard Karger; Philipp Müller; Jing Lin; Sami Vasala; Volodymyr Baran; Sören L. Dreyer; Ruizhuo Zhang; Fatih Ulusoy; Aleksandr Kondrakov; Jürgen Janek; Torsten Brezesinski (Chemical Engineering Journal, 2025)

Experimental study on macro spray, combustion and emission characteristics of biodiesel and diethyl carbonate blends - L. Zhao; X. Zhu; R. Zhao; J. Tian; D. Qian; Q. Lin (International Journal of Environmental Science and Technology, 2025)

Extreme Drought Increases the Temporal Variability of Grassland Productivity by Suppressing Dominant Grasses - Wentao Luo; Naohiro I. Ishii; Taofeek O. Muraina; Lin Song; Niwu Te; Robert J. Griffin‐Nolan; Ingrid J. Slette; Samuel R. P. J. Ross; Takehiro Sasaki; Jennifer A. Rudgers; Melinda D. Smith; Alan K. Knapp; et al. (Ecology Letters, 2025)
Extreme droughts are intensifying, yet their impact on temporal variability of grassland functioning and its drivers remains poorly understood. We imposed a 6‐year extreme drought in two semiarid grasslands to explore how drought influences the temporal variability of ANPP and identify potential stabilising mechanisms. Drought decreased ANPP while increasing its temporal variability across grasslands. In the absence of drought, ANPP variability was strongly driven by the dominant plant species (i.e., mass‐ratio effects), as captured by community‐weighted traits and species stability. However, drought decreased the dominance of perennial grasses, providing opportunities for subordinate species to alter the stability of productivity through compensatory dynamics. Specifically, under drought, species asynchrony emerged as a more important correlate of ANPP variability than community‐weighted traits or species stability. Our findings suggest that in grasslands, prolonged, extreme droughts may decrease the relative contribution of mass‐ratio effects versus compensatory dynamics to productivity stability by reducing the influence of dominant species.

Native polymer degradation capacity of microorganisms in agricultural soils - Zahra F. Islam; Pavel V. Cherepanov; Wanjun Xu; Helen L. Hayden; Elena Colombi; Zhixing Lin; Omid Mazaheri; Frank Caruso; Deli Chen; Hang-Wei Hu (Science of The Total Environment, 2025)

Predicting the impact of rare variants on RNA splicing in CAGI6 - Jenny Lord; Carolina Jaramillo Oquendo; Htoo A. Wai; Andrew G. L. Douglas; David J. Bunyan; Yaqiong Wang; Zhiqiang Hu; Zishuo Zeng; Daniel Danis; Panagiotis Katsonis; Amanda Williams; Olivier Lichtarge; et al. (Human Genetics, 2025)
Variants which disrupt splicing are a frequent cause of rare disease that have been under-ascertained clinically. Accurate and efficient methods to predict a variant’s impact on splicing are needed to interpret the growing number of variants of unknown significance (VUS) identified by exome and genome sequencing. Here, we present the results of the CAGI6 Splicing VUS challenge, which invited predictions of the splicing impact of 56 variants ascertained clinically and functionally validated to determine splicing impact. The performance of 12 prediction methods, along with SpliceAI and CADD, was compared on the 56 functionally validated variants. The maximum accuracy achieved was 82% from two different approaches, one weighting SpliceAI scores by minor allele frequency, and one applying the recently published Splicing Prediction Pipeline (SPiP). SPiP performed optimally in terms of sensitivity, while an ensemble method combining multiple prediction tools and information from databases exceeded all others for specificity. Several challenge methods equalled or exceeded the performance of SpliceAI, with ultimate choice of prediction method likely to depend on experimental or clinical aims. One quarter of the variants were incorrectly predicted by at least 50% of the methods, highlighting the need for further improvements to splicing prediction methods for successful clinical application.

The impacts of shrub branch shelter and nitrogen addition on soil microbial activity and plant litter decomposition in a desert steppe - Xiongkui Lin; Rebecca L. Schneider; Stephen J. Morreale; Hongmei Wang; Jianping Li; Zhigang Li (Applied Soil Ecology, 2025)

Costs of induced defenses dissipate by maturity for diploid and triploid oysters - Benjamin A. Belgrad; Carter Lin; Christa Russell; Randi Cannon; Jessica Lunt; Delbert L. Smee (Aquaculture, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

A high-resolution multiproxy speleothem record of Eastern China hydroclimate variation during last glacial maximum - Shuyu Xue; Hongbin Zhang; Michael L. Griffiths; Chengfei He; Yitao Liu; Junhua Huang; Hai Cheng; Wei Guo; Shitou Wu; Jianzong Zhou; Youfeng Ning; Lin Chen; et al. (Quaternary Science Reviews, 2025)

Spatial and temporal variation in benthic foraminiferal assemblages record history of human activities within the Matagorda Bay system - Paige P. Klug; Christina L. Belanger; Timothy Dellapenna; Yoonho Jung; Anna M. Mozisek; Zachary Clore; Peng Lin; Wei Xing; Danielle Fehrenbach; J.T. Bowling; Gael Ndi Nkwain (Estuarine, Coastal and Shelf Science, 2025)

Grassland bud and shoot demographic responses to single and recurrent droughts vary across an aridity gradient - Niwu Te; Robert J. Griffin‐Nolan; Ingrid J. Slette; Yuan Shi; Lin Song; Jiaqi Chen; Hongqiang Wang; Jianqiang Qian; Qiang Yu; Zhengwen Wang; Xiaotao Lü; Xingguo Han; et al. (Ecology, 2025)
Clonal demographic traits play important roles in regulating community dynamics. Yet, it remains unclear how the responses of these clonal traits to drought might depend on previous drought exposure, and how drought responses vary among grasslands. We conducted a repeated drought experiment across four grasslands along an aridity gradient in northern China. We assessed the effects of single (precipitation reduction in 2021–2022) versus recurrent (precipitation reduction in 2015–2018 and 2021–2022) drought on bud density, shoot density, and the ratio of bud to shoot density. Drought reduced bud density at all grasslands and shoot density at most grasslands. Drought reduced the ratio of bud‐to‐shoot density only in the most arid grasslands. Recurrent drought had larger negative effects than a single drought on bud density and composition of bud and shoot at only one of four grasslands, and on shoot density at two of four grasslands. Our results suggest that previous drought exposure can alter the response of plant clonal demographic traits to subsequent drought in some but not all grasslands, and that responses can vary with mean climate.

Recent progress on triterpenoid derivatives and their anticancer potential - Zi-Xuan Zhao; Qiong-Yu Zou; Ying-Hong Ma; Susan L. Morris‐Natschke; Xiang-Yuan Li; Lin-Chun Shi; Guo-Xu Ma; Xu‐Dong Xu; Mei‐Hua Yang; Zi-Jian Zhao; Yuan-Xiang Li; Jing Xue; et al. (Phytochemistry, 2025)

Toward reproducible and interoperable environmental modeling: Integration of HydroShare with server-side methods for exposing large-extent spatial datasets to models - Young-Don Choi; Iman Maghami; Jonathan L. Goodall; Lawrence Band; Ayman Nassar; Laurence Lin; Linnea Saby; Zhiyu Li; Shaowen Wang; Chris Calloway; Hong Yi; Martin Seul; et al. (Environmental Modelling & Software, 2025)

Observations on Deraniyagala's beaked whale ( Mesoplodon hotaula ) in the South China Sea based on the first confirmed live sightings - Mingming Liu; Wenzhi Lin; Binshuai Liu; Shenglan Chen; Mingli Lin; Lijun Dong; Hui Kang; Mingyue Ouyang; Zixin Yang; Xiaoyu Huang; Massimiliano Rosso; L. Todd Pusser; et al. (Marine Mammal Science, 2025)
Deraniyagala's beaked whale, Mesoplodon hotaula , was previously known from eight published strandings and no confirmed live sightings, making it one of the least‐known cetaceans. We conducted six cetacean survey cruises in the South China Sea between 2019 and 2023, and during 120 sea‐days we recorded 12 sightings of unidentified Mesoplodon . From biopsy samples and acoustic recordings, five sightings were subsequently confirmed as M. hotaula. Using photographs, we provide the first field descriptions and observations of this species. The calf/juvenile has a distinctive facial coloration and dorsal striping pattern that appear to be diagnostic among Indo‐Pacific Mesoplodon ; among adult males, the dark rostrum of M. hotaula and the distinctively white‐tipped beak of ginkgo‐toothed beaked whale, M. ginkgodens , distinguish these similar‐looking, partially sympatric species. Mean group size was small (3.0, n = 5), with a preference for deep (2,156 m, n = 5), warm (30.3°C, n = 3) water. We update the known distribution of this species, present evidence of fishery interactions, and document the first reported mixed‐species Mesoplodon group: a juvenile Blainville's beaked whale M. densirostris associated with four M. hotaula. These sightings identify the South China Sea as a potentially important area for this almost completely unknown species.

Imperiled wanderlust lichens in steppe habitats of western North America comprise geographically structured mycobiont lineages and a reversal to sexual reproduction within this asexual clade - Robert Hadfield; Teagan Mulford; Makani L. Fisher; Abigail Borgmeier; Diego A. Ardon; Andrew D. Suchomel; Judicaël Fomekong-Lontchi; Laura Sutherland; Madison Huie; Pungki Lupiyaningdyah; Sierra Nichols; Ying Fei Lin; et al. (Molecular Phylogenetics and Evolution, 2024)

Corrigendum to Non-essential and essential trace element mixtures and kidney function in early pregnancy – A cross-sectional analysis in project viva [Environ. Res. 216P4 (2023) 114846] - Pi-I.D. Lin; Andres Cardenas; Sheryl L. Rifas-Shiman; Ami R. Zota; Marie-France Hivert; Izzuddin M. Aris; Alison P. Sanders (Environmental Research, 2024)

Long-term impact of Hurricane Maria on point-of-use drinking water quality in Puerto Rico and associated potential adverse health effects - Yishan Lin; Guangyu Li; Maria Sevillano Rivera; Tao Jiang; Irmarie Cotto; Corey M.G. Carpenter; Stephanie L. Rich; Roger W. Giese; Damian E. Helbling; Ingrid Y. Padilla; Zaira Rosario-Pabón; Akram N. Alshawabkeh; et al. (Water Research, 2024)

Outdoor physical activity is not associated with better mental health in a sample of predominantly Black people, but spending time in parks is - Amber L. Pearson; Wei Liu; Zihan Lin; Teresa H. Horton; Jennifer D. Roberts; Tim Chambers; Ashton Shortridge; Karin A. Pfeiffer; Joseph Gardiner (Urban Forestry & Urban Greening, 2024)

Residue depletion profiles and withdrawal intervals of florfenicol and its metabolite florfenicol amine in plasma and milk of lactating goats after repeated subcutaneous administrations - Qiran Chen; Zhoumeng Lin; Jennifer L. Davis; Emily Toney; Maaike O. Clapham; Xue Wu; Lisa A. Tell (Regulatory Toxicology and Pharmacology, 2024)

Fluid inclusion characteristics and mechanisms of tin mineralisation in the Jialong tin polymetallic deposits, Jiuwandashan–Yuanbaoshan, northern Guangxi, China - C-L. Meng; L-A. Bai; Z-H. Yue; S-Y. Zhou; Y. Dai; Z-H. Feng; X-J. Liu; H. Zhang; L-Z. Lin (Australian Journal of Earth Sciences, 2024)

Biodegradation of phthalic acid esters by a novel marine bacterial strain RL-BY03: Characterization, metabolic pathway, bioaugmentation and genome analysis - Lei Ren; Xingjia Wang; John L. Zhou; Yang Jia; Hanqiao Hu; Chengyong Li; Zhong Lin; Mei Liang; Yanyan Wang (Chemosphere, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Characterizing fire and fire atmospheric states from space using collocated hyperspectral infrared sounding and narrow-band imagery - Xuyang Zhou; Qing Yue; King-Fai Li; Evan Fishbein; Xiuhong Chen; Lin Tan; Sally Newman; Eric Fetzer; Yuk L. Yung (Remote Sensing of Environment, 2024)

What Teenagers Eat and What Specific Food Recommendations Can Be Made to Improve Their Poor Diet Quality - L. Lin (Journal of the Academy of Nutrition and Dietetics, 2024)

Prenatal blood metals, per- and polyfluoroalkyl substances and antigen- or mitogen-stimulated cord blood lymphocyte proliferation and cytokine secretion - Anna R. Smith; Pi-I.D. Lin; Sheryl L. Rifas-Shiman; Abby F. Fleisch; Robert O. Wright; Brent Coull; Patricia W. Finn; Emily Oken; Diane R. Gold; Andres Cardenas (Environmental Research, 2024)

Correction to: Neutralizing Antibody Sample Testing and Report Harmonization - Darshana Jani; Michele Gunsior; Robin Marsden; Kyra J. Cowan; Susan C. Irvin; Laura Schild Hay; Bethany Ward; Luke Armstrong; Mitra Azadeh; Liching Cao; Rebecca Carmean; Jason DelCarpini; et al. (The AAPS Journal, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Practical Characterization Strategies for Comparison, Qualification, and Selection of Cell Viability Detection Methods for Cellular Therapeutic Product Development and Manufacturing - Yongyang Huang; Rachel Watkins; Samir Patel; Mackenzie Pierce; Carolina Franco Nitta; Henry Qazi; William L. Rice; Bo Lin; Chris Lowe; Carlos le Sage; Leo Li-Ying Chan (Journal of Fluorescence, 2024)

Nonlinear contributions of surface solar brightening to maize yield gains in the US Corn Belt - H. Zhao; H. Yang; T.J. Avenson; G.F. Sassenrath; MB. Kirkham; S.W. Welch; L. Zhang; N. Wan; A.M. Nelson; P. Gowda; X. Lin (Agricultural and Forest Meteorology, 2024)

Development of 3D-iNET ORION: a novel, pre-clinical, three-dimensional in vitro cell model for modeling human metastatic neuroendocrine tumor of the pancreas - Jan Strnadel; Mark A. Valasek; Grace Y. Lin; Huahui Lin; Ann M. Ponsford Tipps; Sang Myung Woo; Ken Fujimura; Huawei Wang; Sunkyu Choi; Jack Bui; Christopher Hermosillo; Kristen Jepsen; et al. (Human Cell, 2024)
Neuroendocrine tumors (NETs) of the pancreas are rare neoplasms that present complex challenges to diagnosis and treatment due to their indolent course. The incidence of pancreatic neuroendocrine tumors has increased significantly over the past two decades. A limited number of pancreatic neuroendocrine cell lines are currently available for the research. Here, we present 3D-iNET ORION, a novel 3-dimensional (spheroid) cell line, isolated from human pancreatic neuroendocrine tumor liver metastasis. Three-dimensionally grown (3D) cancer cell lines have gained interest over the past years as 3D cancer cell lines better recapitulate the in vivo structure of tumors, and are more suitable for in vitro and in vivo experiments. 3D-iNET ORION cancer cell line showed high potential to form tumorspheres when embedded in Matrigel matrix and expresses synaptophysin and EpCAM. Electron microscopy analysis of cancer cell line proved the presence of dense neurosecretory granules. When xenografted into athymic mice, 3D-iNET ORION cells produce slow-growing tumors, positive for chromogranin and synaptophysin. Human Core Exome Panel Analysis has shown that 3DiNET ORION cell line retains the genetic aberration profile detected in the original tumor. In conclusion, our newly developed neuroendocrine cancer cell line can be considered as a new research tool for in vitro and in vivo experiments.

An in vitro-in silico workflow for predicting renal clearance of PFAS - Hsing-Chieh Lin; Courtney Sakolish; Haley L. Moyer; Paul L. Carmichael; Maria T. Baltazar; Stephen S. Ferguson; Jason P. Stanko; Philip Hewitt; Ivan Rusyn; Weihsueh A. Chiu (Toxicology and Applied Pharmacology, 2024)

Mild chemical recycling of carbon fiber-reinforced epoxy composites in aqueous buffers and development of hydrothermally recyclable vitrimer composites from recyclates - Cheng Hao; Baoming Zhao; Lin Shao; Yiding Cao; Mingen Fei; Wangcheng Liu; Tuan Liu; Yu-Chung Chang; Kevin L. Simmons; Jinwen Zhang (Resources, Conservation and Recycling, 2024)

Au-TiO2 nanoparticles enabled catalytic treatment of oil and gas produced water in slurry and vacuum membrane distillation systems - Lin Chen; Pei Xu; Yanyan Zhang; Darrious Betts; Ganesh L. Ghurye; Huiyao Wang (Journal of Water Process Engineering, 2024)

Etiology and treatment of cancer-related secondary lymphedema - Michael Bernas; Sara Al-Ghadban; Saskia R. J. Thiadens; Karen Ashforth; Walter C. Lin; Bauback Safa; Rudolf Buntic; Michael Paukshto; Alexandra Rovnaya; Margaret L. McNeely (Clinical & Experimental Metastasis, 2024)

Neutralizing Antibody Sample Testing and Report Harmonization - Darshana Jani; Michele Gunsior; Robin Marsden; Kyra J. Cowan; Susan C. Irvin; Laura Schild Hay; Bethany Ward; Luke Armstrong; Mitra Azadeh; Liching Cao; Rebecca Carmean; Jason DelCarpini; et al. (The AAPS Journal, 2024)
Immunogenicity testing and characterization is an important part of understanding the immune response to administration of a protein therapeutic. Neutralizing antibody (NAb) assays are used to characterize a positive anti-drug antibody (ADA) response. Harmonization of reporting of NAb assay performance and results enables efficient communication and expedient review by industry and health authorities. Herein, a cross-industry group of NAb assay experts have harmonized NAb assay reporting recommendations and provided a bioanalytical report (BAR) submission editable template developed to facilitate agency filings. This document addresses key bioanalytical reporting gaps and provides a report structure for documenting clinical NAb assay performance and results. This publication focuses on the content and presentation of the NAb sample analysis report including essential elements such as the method, critical reagents and equipment, data analysis, study samples, and results. The interpretation of immunogenicity data, including the evaluation of the impact of NAb on safety, exposure, and efficacy, is out of scope of this publication. Graphical Abstract

Associations between follicular fluid trace elements and ovarian response during in vitro fertilization - Rooshna Mohsin; Victor Y. Fujimoto; Aubrey L. Galusha; Patrick J. Parsons; Jenna R. Krall; Celeste D. Butts-Jackson; Evelyn Mok-Lin; Michael S. Bloom (Environmental Research, 2024)

Challenges in assessing and managing multi-hazard risks: A European stakeholders perspective - Robert Šakić Trogrlić; Karina Reiter; Roxana L. Ciurean; Stefania Gottardo; Silvia Torresan; Anne Sophie Daloz; Lin Ma; Noemi Padrón Fumero; Sharon Tatman; Stefan Hochrainer-Stigler; Marleen C. de Ruiter; Julius Schlumberger; et al. (Environmental Science & Policy, 2024)

Association between pre-diagnosis recreational physical activity and risk of breast cancer recurrence: the California Teachers Study - Dan Lin; Cheryl L. Thompson; Alaina Demalis; Rebecca Derbes; Laila Al-Shaar; Emma S. Spielfogel; Kathleen M. Sturgeon (Cancer Causes & Control, 2024)

Where the rubber meets the road: Emerging environmental impacts of tire wear particles and their chemical cocktails - Paul M. Mayer; Kelly D. Moran; Ezra L. Miller; Susanne M. Brander; Stacey Harper; Manuel Garcia-Jaramillo; Victor Carrasco-Navarro; Kay T. Ho; Robert M. Burgess; Leah M. Thornton Hampton; Elise F. Granek; Margaret McCauley; et al. (Science of The Total Environment, 2024)

Characteristics and formation of rare-metal pegmatites and granites in the Duanfengshan-Guanyuan district of the northern Mufushan granite complex in South China - Lu Zhang; Shao-Yong Jiang; Rolf L. Romer; Hao-Xiang Zhang; Song-Lin Wan (Lithos, 2024)

Effects on soil carbon storage from municipal biosolids application to agricultural fields - Zheya Lin; G.W. Price; Chang Liang; David L. Burton; Derek H. Lynch (Journal of Environmental Management, 2024)

Vectorgastrogram: dynamic trajectory and recurrence quantification analysis to assess slow wave vector movement in healthy subjects - Gema Prats-Boluda; Jose L. Martinez-de-Juan; Felix Nieto-del-Amor; María Termenon; Cristina Varón; Yiyao Ye-Lin (Physical and Engineering Sciences in Medicine, 2024)
Functional gastric disorders entail chronic or recurrent symptoms, high prevalence and a significant financial burden. These disorders do not always involve structural abnormalities and since they cannot be diagnosed by routine procedures, electrogastrography (EGG) has been proposed as a diagnostic alternative. However, the method still has not been transferred to clinical practice due to the difficulty of identifying gastric activity because of the low-frequency interference caused by skin–electrode contact potential in obtaining spatiotemporal information by simple procedures. This work attempted to robustly identify the gastric slow wave (SW) main components by applying multivariate variational mode decomposition (MVMD) to the multichannel EGG. Another aim was to obtain the 2D SW vectorgastrogram VGG SW from 4 electrodes perpendicularly arranged in a T-shape and analyse its dynamic trajectory and recurrence quantification (RQA) to assess slow wave vector movement in healthy subjects. The results revealed that MVMD can reliably identify the gastric SW, with detection rates over 91% in fasting postprandial subjects and a frequency instability of less than 5.3%, statistically increasing its amplitude and frequency after ingestion. The VGG SW dynamic trajectory showed a statistically higher predominance of vertical displacement after ingestion. RQA metrics (recurrence ratio, average length, entropy, and trapping time) showed a postprandial statistical increase, suggesting that gastric SW became more intense and coordinated with a less complex VGG SW and higher periodicity. The results support the VGG SW as a simple technique that can provide relevant information on the “global” spatial pattern of gastric slow wave propagation that could help diagnose gastric pathologies.

Quantitative Applications of Weather Satellite Data for Nowcasting: Progress and Challenges - Jun Li; Jing Zheng; Bo Li; Min Min; Yanan Liu; Chian-Yi Liu; Zhenglong Li; W. Paul Menzel; Timothy J. Schmit; John L. Cintineo; Scott Lindstrom; Scott Bachmeier; et al. (Journal of Meteorological Research, 2024)

Consensus Paper: Cerebellum and Reward - Mario Manto; Michael Adamaszek; Richard Apps; Erik Carlson; Julian Guarque-Chabrera; Elien Heleven; Shinji Kakei; Kamran Khodakhah; Sheng-Han Kuo; Chi-Ying R. Lin; Mati Joshua; Marta Miquel; et al. (The Cerebellum, 2024)

Spatial relationship between pre-harvest hail and the impact from the wheat streak mosaic disease complex by using remote sensing data - Dongmei Chen; Gary L. Hein; Rebecca Adams-Selin; Lin Wang; Jingcheng Zhang; Xianfeng Zhou; Huiqin Ma; Justin McMechan; Yeyin Shi (Crop Protection, 2024)

Exploring the food-energy-water nexus in coupled natural-human systems under climate change with a fully integrated agent-based modeling framework - Jiaorui Zhang; Y.C. Ethan Yang; Guta W. Abeshu; Hongyi Li; Fengwei Hung; Chung-Yi Lin; L. Ruby Leung (Journal of Hydrology, 2024)

Analytical methodology for determining the extent of pumped freshwater lenses in recharge-limited, circular islands - Barret L. Kurylyk; Yin-Fang Lin; S. Cristina Solórzano-Rivas; Adrian D. Werner (Advances in Water Resources, 2024)

On the brink of explosion? Identifying the source and potential spread of introduced Zosterops white-eyes in North America - Devon A. DeRaad; Marlon E. Cobos; Natalie R. Hofmeister; Lucas H. DeCicco; Madhvi X. Venkatraman; Isao Nishiumi; Bailey McKay; Fa-Sheng Zou; Kazuto Kawakami; Chang-Hoe Kim; Ruey-Shing Lin; Cheng-Te Yao; et al. (Biological Invasions, 2024)

Nucleocytoplasmic shuttling of BEFV M protein-modulated by lamin A/C and chromosome maintenance region 1 through a transcription-, carrier- and energy-dependent pathway - Yu-Kang Chang; Yi-Jyum Lin; Ching-Yuan Cheng; Pei-Chien Tsai; Chi-Young Wang; Brent L. Nielsen; Hung-Jen Liu (Veterinary Microbiology, 2024)

Using process-oriented model output to enhance machine learning-based soil organic carbon prediction in space and time - Lei Zhang; Gerard B.M. Heuvelink; Vera L. Mulder; Songchao Chen; Xunfei Deng; Lin Yang (Science of The Total Environment, 2024)

Cross-sectional and prospective associations of early childhood circulating metals with early and mid-childhood cognition in the Project Viva cohort - Ruwan Thilakaratne; Pi-I D. Lin; Sheryl L. Rifas-Shiman; Julio Landero; Robert O. Wright; David Bellinger; Emily Oken; Andres Cardenas (Environmental Research, 2024)

Telomere dynamics during hibernation in a tropical primate - M. B. Blanco; D. L. Smith; L. K. Greene; A. D. Yoder; E. E. Ehmke; J. Lin; P. H. Klopfer (Journal of Comparative Physiology B, 2024)

Beauty is in the eye of the beholder: Moderate ability to predict perceptions of beauty, restorativeness, and naturalness, in imagery among 10,727 participants - Amber L. Pearson; Zihan Lin; Ashton Shortridge (Landscape and Urban Planning, 2024)

RNF4 prevents genomic instability caused by chronic DNA under-replication - Marissa K. Oram; Ryan M. Baxley; Emily M. Simon; Kevin Lin; Ya-Chu Chang; Liangjun Wang; Chad L. Myers; Anja-Katrin Bielinsky (DNA Repair, 2024)

Inherited BRCA1 and RNF43 pathogenic variants in a familial colorectal cancer type X family - James M. Chan; Mark Clendenning; Sharelle Joseland; Peter Georgeson; Khalid Mahmood; Jihoon E. Joo; Romy Walker; Julia Como; Susan Preston; Shuyi Marci Chai; Yen Lin Chu; Aaron L. Meyers; et al. (Familial Cancer, 2024)
Genetic susceptibility to familial colorectal cancer (CRC), including for individuals classified as Familial Colorectal Cancer Type X (FCCTX), remains poorly understood. We describe a multi-generation CRC-affected family segregating pathogenic variants in both BRCA1 , a gene associated with breast and ovarian cancer and RNF43 , a gene associated with Serrated Polyposis Syndrome (SPS). A single family out of 105 families meeting the criteria for FCCTX (Amsterdam I family history criteria with mismatch repair (MMR)-proficient CRCs) recruited to the Australasian Colorectal Cancer Family Registry (ACCFR; 1998–2008) that underwent whole exome sequencing (WES), was selected for further testing. CRC and polyp tissue from four carriers were molecularly characterized including a single CRC that underwent WES to determine tumor mutational signatures and loss of heterozygosity (LOH) events. Ten carriers of a germline pathogenic variant BRCA1 :c.2681_2682delAA p.Lys894ThrfsTer8 and eight carriers of a germline pathogenic variant RNF43 :c.988 C > T p.Arg330Ter were identified in this family. Seven members carried both variants, four of which developed CRC. A single carrier of the RNF43 variant met the 2019 World Health Organization (WHO 2019 ) criteria for SPS, developing a BRAF p.V600 wildtype CRC. Loss of the wildtype allele for both BRCA1 and RNF43 variants was observed in three CRC tumors while a LOH event across chromosome 17q encompassing both genes was observed in a CRC. Tumor mutational signature analysis identified the homologous recombination deficiency (HRD)-associated COSMIC signatures SBS3 and ID6 in a CRC for a carrier of both variants. Our findings show digenic inheritance of pathogenic variants in BRCA1 and RNF43 segregating with CRC in a FCCTX family. LOH and evidence of BRCA1-associated HRD supports the importance of both these tumor suppressor genes in CRC tumorigenesis.

Vegetation−fire feedbacks increase subtropical wildfire risk in scrubland and reduce it in forests - P. Wei; B. Lamont; T. He; W. Xue; P.C. Wang; W. Song; R. Zhang; A.B. Keyhani; S. Zhao; W. Lu; F. Dong; R. Gao; et al. (Journal of Environmental Management, 2024)

Environmental drivers and prediction of Karenia mikimotoi proliferation in coastal area, Southeast China - Jinzhu Su; Balaji Prasath Barathan; Yuping Su; Steve L. Morton; Chenxing She; Hong Zhang; Xiongsheng Lin (Marine Biology, 2024)

Synthesis of nano-MgO hybrid SDB hydrophobic catalyst carriers and its adsorption behavior of Fe3+ - Y. Fan; H. R. Peng; C. Li; K. Fu; X. Y. Ren; H. J. Yang; S. D. Lin; C. L. Liu (International Journal of Environmental Science and Technology, 2024)

Region and cloud regime dependence of parametric sensitivity in E3SM atmosphere model - Yun Qian; Zhun Guo; Vincent E. Larson; L. Ruby Leung; Wuyin Lin; Po-Lun Ma; Hui Wan; Hailong Wang; Heng Xiao; Shaocheng Xie; Ben Yang; Kai Zhang; et al. (Climate Dynamics, 2024)
The Department of Energy (DOE)’s Energy Exascale Earth System Model (E3SM), including its atmosphere model (EAM), has many relatively new features. In a previous study we conducted a systematic parametric sensitivity analysis for EAM based on short, perturbed parameter ensemble (PPE) simulations, mainly focusing on global mean climate features and metrics. While parameter values in global climate models are generally invariant in space and time, model response to parameters perturbation may vary by regions and climate regimes, which motivates the need to better understand the EAM model behaviors and physics at regional scale and process level. In this study, using the same set of PPE simulations and a similar sensitivity analysis framework, we identify parameters that cause largest sensitivities over different regions and compare model responses in fast atmospheric processes to the parameters across different cloud regimes for several important cloud-related fidelity metrics. We find that cloud forcing has opposite response to some parameters over mid-latitude vs. tropical land. We also analyze how the parametric sensitivity varies as stratocumulus transitions to shallow convection and to deep convection over ocean. Low cloud forcing and shortwave cloud forcing in the subtropical eastern Pacific are most sensitive to the parameters controlling the width of the probability density function (PDF) of the subgrid vertical velocity ( w’ ) ( gamma ) and the damping of the w’ skewness ( c8 ) near the coast but become more sensitive to the parameter affecting the damping of the w’ variance ( c1 ) further offshore. Detailed interpretation of the spatial dependence of parametric sensitivity is provided. We also investigate how the parametric sensitivity evolves with prediction duration. This study improves our process-level understanding of cloud physics and parameterization and provides insights for developing more advanced regime-aware parameterization schemes in global climate model.

Grassland sensitivity to drought is related to functional composition across E ast A sia and N orth A merica - Lin Song; Robert J. Griffin‐Nolan; Taofeek O. Muraina; Jiaqi Chen; Niwu Te; Yuan Shi; Kenneth D. Whitney; Bingchuan Zhang; Qiang Yu; Melinda D. Smith; Xiaoan Zuo; Zhengwen Wang; et al. (Ecology, 2024)
Plant traits can be helpful for understanding grassland ecosystem responses to climate extremes, such as severe drought. However, intercontinental comparisons of how drought affects plant functional traits and ecosystem functioning are rare. The Extreme Drought in Grasslands experiment (EDGE) was established across the major grassland types in East Asia and North America (six sites on each continent) to measure variability in grassland ecosystem sensitivity to extreme, prolonged drought. At all sites, we quantified community‐weighted mean functional composition and functional diversity of two leaf economic traits, specific leaf area and leaf nitrogen content, in response to drought. We found that experimental drought significantly increased community‐weighted means of specific leaf area and leaf nitrogen content at all North American sites and at the wetter East Asian sites, but drought decreased community‐weighted means of these traits at moderate to dry East Asian sites. Drought significantly decreased functional richness but increased functional evenness and dispersion at most East Asian and North American sites. Ecosystem drought sensitivity (percentage reduction in aboveground net primary productivity) positively correlated with community‐weighted means of specific leaf area and leaf nitrogen content and negatively correlated with functional diversity (i.e., richness) on an intercontinental scale, but results differed within regions. These findings highlight both broad generalities but also unique responses to drought of community‐weighted trait means as well as their functional diversity across grassland ecosystems.

Early-Life Social Determinants of SCA6 Age at Onset, Severity, and Progression - Tiffany X. Chen; Hannah L. Casey; Chi-Ying R. Lin; Theresa A. Boyle; Jeremy D. Schmahmann; Gilbert J. L’Italien; Sheng-Han Kuo; Christopher M. Gomez (The Cerebellum, 2024)
SCA6 patients with the same size CAG repeat allele can vary significantly in age at onset (AAO) and clinical progression. The specific external factors affecting SCA6 have yet to be investigated. We assessed the effect of early life events on AAO, severity, and progression in SCA6 patients using a social determinant of health approach. We performed a survey of biological and social factors in SCA6 patients enrolled in the SCA6 Network at the University of Chicago. AAO of ataxia symptoms and patient-reported outcome measure (PROM) of ataxia were used as primary outcome measures. Least absolute shrinkage and selection operation (LASSO) regressions were used to identify which early life factors are predictive of SCA6 AAO, severity, and progression. Multiple linear regression models were then used to assess the degree to which these determinants influence SCA6 health outcomes. A total of 105 participants with genetically confirmed SCA6 completed the assessments. SCA6 participants with maternal difficulty during pregnancy, active participation in school sports, and/or longer CAG repeats were determined to have earlier AAO. We found a 13.44-year earlier AAO for those with maternal difficulty in pregnancy than those without ( p = 0.008) and a 12.31-year earlier AAO for those active in school sports than those who were not ( p < 0.001). Higher education attainment was associated with decreased SCA6 severity and slower progression. Early life biological and social factors can have a strong influence on the SCA6 disease course, indicating that non-genetic factors can contribute significantly to SCA6 health outcomes.

Effects of field-aging on the impact of biochar on herbicide fate and microbial community structure in the soil environment - Hongguang Cheng; Dan Xing; Gratien Twagirayezu; Shan Lin; Shangyi Gu; Chenglong Tu; Paul W. Hill; David R. Chadwick; Davey L. Jones (Chemosphere, 2024)

Woody plant cell walls: Fundamentals and utilization - Wei Li; Ying-Chung Jimmy Lin; Ying-Lan Chen; Chenguang Zhou; Shuang Li; Nette De Ridder; Dyoni M. Oliveira; Lanjun Zhang; Baocai Zhang; Jack P. Wang; Changzheng Xu; Xiaokang Fu; et al. (Molecular Plant, 2024)

Effect of micro-fin tube geometry parameters on evaporator material savings - M.A. Kedzierski; L. Lin; K. Han (International Journal of Refrigeration, 2024)

Returning personal genetic information on susceptibility to arsenic toxicity to research participants in Bangladesh - Lizeth I. Tamayo; Syed Emdadul Haque; Tariqul Islam; Alauddin Ahmed; Moziber Rahman; Abu Horayra; Lin Tong; Lin Chen; Aresha Martinez-Cardoso; Habibul Ahsan; Brandon L. Pierce (Environmental Research, 2024)

Multi-scale numerical simulations of the synoptic environment, Diablo windstorm, and wildfire formation mechanisms for the Tubbs Fire (2017) - Jackson T. Wiles; Yuh-Lang Lin; Michael L. Kaplan (Meteorology and Atmospheric Physics, 2024)

Distinct variations in fluorescent DOM components along a trophic gradient in the lower Fox River-Green Bay as characterized using one-sample PARAFAC approach - Hui Lin; Sarah L. Bartlett; Laodong Guo (Science of The Total Environment, 2023)

The Pacific water flow branches in the eastern Chukchi Sea - Robert S. Pickart; Peigen Lin; Frank Bahr; Leah T. McRaven; Jie Huang; Astrid Pacini; Kevin R. Arrigo; Carin J. Ashjian; Catherine Berchok; Mark F. Baumgartner; Kyoung-Ho Cho; Lee W. Cooper; et al. (Progress in Oceanography, 2023)

Multifunctional photocatalytic membrane distillation for treatment of hypersaline produced water using hydrophobically modified tubular ceramic membranes - Lin Chen; Pei Xu; Deepak A. Musale; Yanyan Zhang; Raed Asfan; Carlos Galdeano; Ganesh L. Ghurye; Huiyao Wang (Journal of Environmental Chemical Engineering, 2023)

Assessing the Impacts of Wetlands on Discharge and Nutrient Loading: Insights from Restoring Past Wetlands with GIS-Based Analysis and Modeling - Mosammat Mustari Khanaum; Tiansong Qi; Kyle D. Boutin; Marinus L. Otte; Zhulu Lin; Xuefeng Chu (Wetlands, 2023)

Nuts and berries from agroforestry systems in temperate regions can form the foundation for a healthier human diet and improved outcomes from diet-related diseases - Sarah Taylor Lovell; Kiruba Krishnaswamy; Chung-Ho Lin; Nicholas Meier; Ronald S. Revord; Andrew L. Thomas (Agroforestry Systems, 2023)
Agroforestry is a specific type of agroecosystem that includes trees and shrubs with the potential to yield nutrient-rich products that contribute to human health. This paper reviews the literature on the human health benefits of tree nut and berry species commonly associated with agroforestry systems of the United States, considering their potential for preventing certain diet-related diseases. Emphasis is placed on those diseases that are most closely associated with poor outcomes from COVID-19, as they are indicators of confounding health prognoses. Results indicate that tree nuts reduce the risk of coronary heart disease, and walnuts ( Juglans species) are particularly effective because of their unique fatty acid profile. Berries that are grown on shrubs have the potential to contribute to mitigation of hypertension, prevention of Type II diabetes, and reduced risk of cardiovascular disease. To optimize human health benefits, plant breeding programs can focus on the traits that enhance the naturally-occurring phytochemicals, through biofortification. Value-added processing techniques should be selected and employed to preserve the phytonutrients, so they are maintained through the point of consumption. Agroforestry systems can offer valuable human health outcomes for common diet-related diseases, in addition to providing many environmental benefits, particularly if they are purposefully designed with that goal in mind. The food system policies in the U.S. might be reoriented to prioritize these food production systems based on the health benefits.

Intimately tracking NO2 pollution over the New York City - Long Island Sound land-water continuum: An integration of shipboard, airborne, satellite observations, and models - Maria Tzortziou; Christopher P. Loughner; Daniel L. Goldberg; Laura Judd; Dilchand Nauth; Charlotte F. Kwong; Tong Lin; Alexander Cede; Nader Abuhassan (Science of The Total Environment, 2023)

Pharmacokinetics, tissue residue depletion, and withdrawal interval estimations of florfenicol in goats following repeated subcutaneous administrations - Xue Wu; Zhoumeng Lin; Emily Toney; Maaike O. Clapham; Scott E. Wetzlich; Jennifer L. Davis; Qiran Chen; Lisa A. Tell (Food and Chemical Toxicology, 2023)

Development and application of an interactive generic physiologically based pharmacokinetic (igPBPK) model for adult beef cattle and lactating dairy cows to estimate tissue distribution and edible tissue and milk withdrawal intervals for per- and polyfluoroalkyl substances (PFAS) - Wei-Chun Chou; Lisa A. Tell; Ronald E. Baynes; Jennifer L. Davis; Yi-Hsien Cheng; Fiona P. Maunsell; Jim E. Riviere; Zhoumeng Lin (Food and Chemical Toxicology, 2023)

Nepalese indoor cookstove smoke extracts alter human airway epithelial gene expression, DNA methylation and hydroxymethylation - Poojitha Rajasekar; Robert J. Hall; K.C. Binaya; Parth S. Mahapatra; Siva P. Puppala; Dhruma Thakker; Julia L. MacIsaac; David Lin; Michael Kobor; Charlotte E. Bolton; Ian Sayers; Ian P. Hall; et al. (Environmental Pollution, 2023)

Advancing co-production for transformative change by synthesizing guidance from case studies on the sustainable management and governance of natural resources - Fernanda A. van Maurik Matuk; Bas Verschuuren; Piero Morseletto; Torsten Krause; David Ludwig; Steven J. Cooke; Moacir Haverroth; Marieke Meesters; Thomas J.M. Mattijssen; Sabine Keßler; Tomaz R. Lanza; Esther Milberg; et al. (Environmental Science & Policy, 2023)

The effect of polychlorinated biphenyls extracted from offshore sediments on the intestinal epithelium and microflora of zebrafish - M. Zhang; D-H Zhu; Q-L Song; M-M Chen; Y Hu; D-J Kang; Z-B Chen; H-Y Lin; F-H Nie; J-J Chen (International Journal of Environmental Science and Technology, 2023)

Are associations between obesity and prostate cancer outcomes following radical prostatectomy the same in smokers and non-smokers? Results from the SEARCH Cohort - Ivy T. Liu; Lin Gu; Amanda M. De Hoedt; Matthew R. Cooperberg; Christopher L. Amling; Christopher J. Kane; Zachary Klaassen; Martha K. Terris; Lourdes Guerrios-Rivera; Adriana C. Vidal; William J. Aronson; Stephen J. Freedland; et al. (Cancer Causes & Control, 2023)

The Relationship Between Cortical Morphological and Functional Topological Properties and Clinical Manifestations in Patients with Posttraumatic Diffuse Axonal Injury: An Individual Brain Network Study - Fuqing Zhou; Lin Wu; Long Qian; Hongmei Kuang; Jie Zhan; Jian Li; Gerald L. Cheung; Aimin Ding; Honghan Gong (Brain Topography, 2023)

Biosimilars approvals by thirteen regulatory authorities: A cross-national comparison - Fernanda Lacerda da Silva Machado; Martín Cañás; Svetlana V. Doubova; Martín A. Urtasun; Gustavo H. Marín; Claudia Garcia Serpa Osorio-de-Castro; Flavia Caixeta Albuquerque; Tatiane Bonfim Ribeiro; Lisa Pont; José Crisóstomo Landeros; Juan Roldán Saelzer; Dino Sepúlveda Viveros; et al. (Regulatory Toxicology and Pharmacology, 2023)

Cloud condensation nuclei activation properties of Mediterranean pollen types considering organic chemical composition and surface tension effects - A. Casans; F. Rejano; J. Maldonado-Valderrama; J.A. Casquero-Vera; S. Ruiz-Peñuela; B.L. van Drooge; H. Lyamani; A. Cazorla; E. Andrews; Jack J. Lin; F. Mirza-Montoro; D. Pérez-Ramírez; et al. (Atmospheric Environment, 2023)

Characterization of fouled ultrafiltration membranes from a full-scale wastewater reclamation plant in iron and steel industry - P.-H. Lin; Y.-C. Su; C.-L. Chen; I.-Y. Tsao (International Journal of Environmental Science and Technology, 2023)

Supporting regional co-operation in the South China Sea with an initial assessment of the data-limited skipjack tuna fishery - Jeremy Prince; Xuefeng Wang; Kun Lin; Ani Suryanti; Sallehudin Jamon; Mudjekeewis D. Santos; Francisco SB. Torres; Nicko Amor L. Flores; Vu Viet Ha; Tran Thi Ngoc Anh (Marine Policy, 2023)

Pandemic gardening: A narrative review, vignettes and implications for future research - Jonathan Kingsley; Kelly Donati; Jill Litt; Naomi Shimpo; Chris Blythe; Jan Vávra; Silvio Caputo; Paul Milbourne; Lucy O. Diekmann; Nick Rose; Runrid Fox-Kämper; Agnes van den Berg; et al. (Urban Forestry & Urban Greening, 2023)

Repeated manure inputs to a forage production soil increase microbial biomass and diversity and select for lower abundance genera - Jordan M. Sayre; Daoyuan Wang; Jonathan Y. Lin; Rachel E. Danielson; Kate M. Scow; Jorge L. Mazza Rodrigues (Agriculture, Ecosystems & Environment, 2023)

Reconstructing population exposures to acrylamide from human monitoring data using a pharmacokinetic framework - Yu-Sheng Lin; Viktor Morozov; Abdel-Razak Kadry; James L Caffrey; Wei-Chun Chou (Chemosphere, 2023)

Formation and circulation of newly ventilated winter water in the western Beaufort Sea - Peigen Lin; Robert S. Pickart; Thomas J. Weingartner; Harper L. Simmons; Motoyo Itoh; Takashi Kikuchi (Progress in Oceanography, 2023)

Impact of Primary Container Closure System on PS80 Oxidation and the Mechanistic Understanding - Ryan Mould; Peter William Sargent; Yining Huang; Allison L. Fields; Lin Zhang; Fabian Castro Herbert; Stephanie Lynn Stewart; Tingting Wang (Pharmaceutical Research, 2023)

A monitoring system for CO2-EOR and storage based on reactive transport simulation of CO2 migration in groundwater - L. Li; Y. Wu; Q. Lin; Q. Wen; S. Chong (International Journal of Environmental Science and Technology, 2023)

Neutralizing Antibody Validation Testing and Reporting Harmonization - Heather Myler; João Pedras-Vasconcelos; Todd Lester; Francesca Civoli; Weifeng Xu; Bonnie Wu; Inna Vainshtein; Linlin Luo; Mohamed Hassanein; Susana Liu; Swarna Suba Ramaswamy; Johanna Mora; et al. (The AAPS Journal, 2023)
Evolving immunogenicity assay performance expectations and a lack of harmonized neutralizing antibody validation testing and reporting tools have resulted in significant time spent by health authorities and sponsors on resolving filing queries. A team of experts within the American Association of Pharmaceutical Scientists’ Therapeutic Product Immunogenicity Community across industry and the Food and Drug Administration addressed challenges unique to cell-based and non-cell-based neutralizing antibody assays. Harmonization of validation expectations and data reporting will facilitate filings to health authorities and are described in this manuscript. This team provides validation testing and reporting strategies and tools for the following assessments: (1) format selection; (2) cut point; (3) assay acceptance criteria; (4) control precision; (5) sensitivity including positive control selection and performance tracking; (6) negative control selection; (7) selectivity/specificity including matrix interference, hemolysis, lipemia, bilirubin, concomitant medications, and structurally similar analytes; (8) drug tolerance; (9) target tolerance; (10) sample stability; and (11) assay robustness. Graphical Abstract

Trace analysis of per- and polyfluorinated alkyl substances (PFAS) in dried blood spots – Demonstration of reproducibility and comparability to venous blood samples - Elizabeth Z. Lin; Sara L. Nason; Alexander Zhong; John Fortner; Krystal J. Godri Pollitt (Science of The Total Environment, 2023)

Shifts in the composition of nitrogen deposition in the conterminous United States are discernable in stream chemistry - Meredith G. Lassiter; Jiajia Lin; Jana E. Compton; Jennifer Phelan; Robert D. Sabo; John L. Stoddard; Stephen R. McDow; Tara L. Greaver (Science of The Total Environment, 2023)

Geological controls on the distribution of gas hydrates in the shallow parts of the gas hydrate stability zone – constraints from seafloor drilling off Taiwan - G. Bohrmann; C. Berndt; S. Lin; T.-H. Tu; A.T. Lin; H.-H. Hsu; M.-C. Lai; W.-C. Chi; C. Deusner; J. Elger; K. Wallmann; T. Freudenthal; et al. (Marine and Petroleum Geology, 2023)

Nitrogen isotope enrichment predicts growth response of Pinus radiata in New Zealand to nitrogen fertiliser addition - Loretta G. Garrett; Yue Lin; Amanda L. Matson; Brian D. Strahm (Biology and Fertility of Soils, 2023)
The fertiliser growth response of planted forests can vary due to differences in site-specific factors like climate and soil fertility. We identified when forest stands responded to a standard, single application of nitrogen (N) fertiliser and employed a machine learning random forest model to test the use of natural abundance stable isotopic N (δ 15 N) to predict site response. Pinus radiata growth response was calculated as the change in periodic annual increment of basal area (PAI BA) from replicated control and treatment (~ 200 kg N ha −1 ) plots within trials across New Zealand. Variables in the analysis were climate, silviculture, soil, and foliage chemical properties, including natural abundance δ 15 N values as integrators of historical patterns in N cycling. Our Random Forest model explained 78% of the variation in growth with tree age and the δ 15 N enrichment factor (δ 15 N foliage − δ 15 N soil ) showing more than 50% relative importance to the model. Tree growth rates generally decreased with more negative δ 15 N enrichment factors. Growth response to N fertiliser was highly variable. If a response was going to occur, it was most likely within 1–3 years after fertiliser addition. The Random Forest model predicts that younger stands (< 15 years old) with the freedom to grow and sites with more negative δ 15 N isotopic enrichment factors will exhibit the biggest growth response to N fertiliser. Supporting the challenge of forest nutrient management, these findings provide a novel decision-support tool to guide the intensification of nutrient additions.

Anatomy of a craton: Isotopic heterogeneity across an Archean crustal cross-section - Jillian Kendrick; Manuel Duguet; Christopher L. Kirkland; Janne Liebmann; Shoufa Lin; Desmond E. Moser; Chris Yakymchuk (Precambrian Research, 2023)

Contributions of plant litter to soil microbial activity improvement and soil nutrient enhancement along with herb and shrub colonization expansions in an arid sandy land - Jing Liu; Jun Wang; Stephen J. Morreale; Rebecca L. Schneider; Zhigang Li; Gao-Lin Wu (CATENA, 2023)

Two new species of Sarcomyxa (Agaricales) from China - Qing Cai; Wen-Fei Lin; Jian-Wei Liu; Yong Zhou; Zhu L. Yang (Mycological Progress, 2023)

Characteristics and correlation of soil low-molecular-weight organic acids and nutrients in four plantations in red soil area of south China - Y. M. Ren; Z. J. Hou; T. Su; Z. R. Lin; A. Q. Liu; L. P. Cai (International Journal of Environmental Science and Technology, 2023)

Solubility controls on plutonium and americium release in subsurface environments exposed to acidic processing wastes - Hilary P. Emerson; Sergey I. Sinkov; Carolyn I. Pearce; Kirk J. Cantrell; Calvin H. Delegard; Michelle M.V. Snyder; May-Lin Thomas; Dallas D. Reilly; Edgar C. Buck; Lucas E. Sweet; Amanda J. Casella; Jennifer C. Carter; et al. (Applied Geochemistry, 2023)

Macroalgae exhibit diverse responses to human disturbances on coral reefs - Sara E. Cannon; Simon D. Donner; Angela Liu; Pedro C. González Espinosa; Andrew H. Baird; Julia K. Baum; Andrew G. Bauman; Maria Beger; Cassandra E. Benkwitt; Matthew J. Birt; Yannick Chancerelle; Joshua E. Cinner; et al. (Global Change Biology, 2023)
Scientists and managers rely on indicator taxa such as coral and macroalgal cover to evaluate the effects of human disturbance on coral reefs, often assuming a universally positive relationship between local human disturbance and macroalgae. Despite evidence that macroalgae respond to local stressors in diverse ways, there have been few efforts to evaluate relationships between specific macroalgae taxa and local human‐driven disturbance. Using genus‐level monitoring data from 1205 sites in the Indian and Pacific Oceans, we assess whether macroalgae percent cover correlates with local human disturbance while accounting for factors that could obscure or confound relationships. Assessing macroalgae at genus level revealed that no genera were positively correlated with all human disturbance metrics. Instead, we found relationships between the division or genera of algae and specific human disturbances that were not detectable when pooling taxa into a single functional category, which is common to many analyses. The convention to use percent cover of macroalgae as an indication of local human disturbance therefore likely obscures signatures of local anthropogenic threats to reefs. Our limited understanding of relationships between human disturbance, macroalgae taxa, and their responses to human disturbances impedes the ability to diagnose and respond appropriately to these threats.

Virulence assessment of four Glaesserella parasuis strains isolated in Liaoning province of China - Ping Yan; Yong C. Jia; Xue L. Zhang; Yuan Y. Zhou; Ying Guo; Rong L. Yin; Jing Yuan; Lin X. Wang; Zhong B. Guo; Jing Y. Wang; Xin Wang; Rong H. Yin (Research in Veterinary Science, 2023)

Thermal degradation of thaumatin at low pH and its prevention using alkyl gallates - Benjamin Pomon; Yu Zhao; Alex L. Lai; Tiantian Lin; Jack H. Freed; Alireza Abbaspourrad (Food Hydrocolloids, 2023)

Microplastics affect arsenic bioavailability by altering gut microbiota and metabolites in a mouse model - Shan Chen; Jin-Lei Yang; Yao-Sheng Zhang; Hong-Yu Wang; Xin-Ying Lin; Rong-Yue Xue; Meng-Ya Li; Shi-Wei Li; Albert L. Juhasz; Lena Q. Ma; Dong-Mei Zhou; Hong-Bo Li (Environmental Pollution, 2023)

The contributions of root morphological characteristics and soil property to soil infiltration in a reseeded desert steppe - Bo Wang; Jing Liu; Zhigang Li; Stephen J. Morreale; Rebecca L. Schneider; Dongmei Xu; Xiongkui Lin (CATENA, 2023)

Corrigendum to “Carbonate U Pb and illite Rb Sr geochronology of sediment-hosted gold: A case study of Yata gold deposit” [Chemical Geology 621 (2023) 121352] - Ruixue Wang; Qingfei Wang; Jian-Xin Zhao; David I. Groves; Christopher L. Kirkland; Yue-Xing Feng; I. Tonguç Uysal; Lin Yang; Jun Deng (Chemical Geology, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

A novel aerobic denitrifying phosphate-accumulating bacterium efficiently removes phthalic acid ester, total nitrogen and phosphate from municipal wastewater - Lei Ren; Zhenzhao Guo; Lele Zhang; Hanqiao Hu; Chengyong Li; Zhong Lin; Zhen Zhen; John L. Zhou (Journal of Water Process Engineering, 2023)

Relative sea level response to mixed carbonate-siliciclastic sediment loading along the Great Barrier Reef margin - Yucheng Lin; Pippa L. Whitehouse; Fiona D. Hibbert; Sarah A. Woodroffe; Gustavo Hinestrosa; Jody M. Webster (Earth and Planetary Science Letters, 2023)

Ammonium removal characteristics of Delftia tsuruhatensis SDU2 with potential application in ammonium‑rich wastewater treatment - L. F. Chen; L. X. Chen; D. Pan; Y. L. Ren; J. Zhang; B. Zhou; J. Q. Lin; J. Q. Lin (International Journal of Environmental Science and Technology, 2023)

Bioturbation in sediment cores from the Clarion-Clipperton Zone in the northeast Pacific: Evidence from excess 210Pb - W. Yu; F. Lin; L. Lin (Marine Pollution Bulletin, 2023)

On-road mobile mapping of spatial variations and source contributions of ammonia in Beijing, China - Weiwei Pu; Jiujiang Sheng; Ping Tian; Mengyu Huang; Xiangxue Liu; Jeffrey L. Collett; Ziming Li; Xiujuan Zhao; Di He; Fan Dong; Nannan Zhang; Weijun Quan; et al. (Science of The Total Environment, 2023)

Dietary Lactobacillus reuteri prevent from inflammation mediated apoptosis of liver via improving intestinal microbiota and bile acid metabolism - Zishen Lin; Jianmin Wu; Jinping Wang; Crystal L. Levesque; Xi Ma (Food Chemistry, 2023)

Carbonate U Pb and illite Rb Sr geochronology of sediment-hosted gold: A case study of Yata gold deposit - Ruixue Wang; Qingfei Wang; Jian-Xin Zhao; David I. Groves; Christopher L. Kirkland; Yue-Xing Feng; I. Tonguç Uysal; Lin Yang; Jun Deng (Chemical Geology, 2023)

Soil organic carbon, aggregation and fungi community after 44 years of no-till and cropping systems in the Central Great Plains, USA - James S. Lin; Marcos V. M. Sarto; Tiffany L. Carter; Dallas E. Peterson; Colleen Gura; Laura Mino; Megan Rohrs; Hallie Lucas; Jamie Clark; Charles W. Rice (Archives of Microbiology, 2023)

A critical thermal transition driving spring phenology of Northern Hemisphere conifers - Jian‐Guo Huang; Yaling Zhang; Minhuang Wang; Xiaohan Yu; Annie Deslauriers; Patrick Fonti; Eryuan Liang; Harri Mäkinen; Walter Oberhuber; Cyrille B. K. Rathgeber; Roberto Tognetti; Václav Treml; et al. (Global Change Biology, 2023)
Despite growing interest in predicting plant phenological shifts, advanced spring phenology by global climate change remains debated. Evidence documenting either small or large advancement of spring phenology to rising temperature over the spatio‐temporal scales implies a potential existence of a thermal threshold in the responses of forests to global warming. We collected a unique data set of xylem cell‐wall‐thickening onset dates in 20 coniferous species covering a broad mean annual temperature (MAT) gradient (−3.05 to 22.9°C) across the Northern Hemisphere (latitudes 23°–66° N). Along the MAT gradient, we identified a threshold temperature (using segmented regression) of 4.9 ± 1.1°C, above which the response of xylem phenology to rising temperatures significantly decline. This threshold separates the Northern Hemisphere conifers into cold and warm thermal niches, with MAT and spring forcing being the primary drivers for the onset dates (estimated by linear and Bayesian mixed‐effect models), respectively. The identified thermal threshold should be integrated into the Earth‐System‐Models for a better understanding of spring phenology in response to global warming and an improved prediction of global climate‐carbon feedbacks.

Food values drive Chinese consumers' demand for meat and milk substitutes - Jiayu Sun; David L. Ortega; Wen Lin (Appetite, 2023)

Predicting future well performance for environmental remediation design using deep learning - Xuehang Song; Huiying Ren; Zhangshuan Hou; Xinming Lin; Marinko Karanovic; Matt Tonkin; Vicky L. Freedman; Inci Demirkanli; Rob Mackley (Journal of Hydrology, 2023)

The TCI Clinical Encounter Program for PhD Students in Cancer Biology: a Feasibility Pilot - Alexander M. Real; Jenny J. Lin; Janice L. Gabrilove (Journal of Cancer Education, 2023)
Clinical rotations are often not included in graduate-level cancer biology curricula; however, basic insight into clinical oncology is often crucial for developing translational research that addresses unmet needs with the potential to benefit cancer patients. We describe a needs assessment, design, implementation, and descriptive evaluation of an oncology-specific pilot clinical encounter program developed for PhD students in the Cancer Biology Training Area (CAB) in the Graduate School of Biomedical Sciences (GSBS) and Tisch Cancer Institute (TCI) at the Icahn School of Medicine at Mount Sinai (ISMMS). Prior to the development of this pilot program, CAB students, in years 2–5 + , were surveyed to determine their interest in a structured clinical experience. Seventeen out of thirty-one students responded (55%) to the survey. Of those seventeen respondents, fifteen (88.2%) expressed that exposure to cancer patients in the clinical setting would be useful for their pre-doctoral biomedical science and cancer biology training and indicated an interest in participating in the clinical encounter program. Based on these responses, a three-session clinical encounter pilot program was designed. Two separate cohorts of 5 students participated in this pilot program. During a formal debrief, following the clinical experience, students commented on the resilience of patients and the importance of research on clinical decision making, and reported that they found the experience motivational. Five out of 10 students responded (50%) to a post-program assessment survey; all five respondents answered that they would recommend the clinical encounter program to their peers. While limited in size and scope, this pilot TCI Clinical Encounter Program proved feasible and has the potential to enrich and inform the experience of PhD students pursing advanced degrees in a cancer biology.

Responses of a semiarid grassland to recurrent drought are linked to community functional composition - Wentao Luo; Taofeek O. Muraina; Robert J. Griffin‐Nolan; Wang Ma; Lin Song; Wei Fu; Qiang Yu; Alan K. Knapp; Zhengwen Wang; Xingguo Han; Scott L. Collins (Ecology, 2023)
Recurrent droughts are an inevitable consequence of climate change, yet how grasslands respond to such events is unclear. We conducted a 6‐year rainfall manipulation experiment in a semiarid grassland that consisted of an initial 2‐year drought (2015–2016), followed by a recovery period (2017–2018) and, finally, a second 2‐year drought (2019–2020). In each year, we estimated aboveground net primary productivity (ANPP), species richness, community‐weighted mean (CWM) plant traits, and several indices of functional diversity. The initial drought led to reduced ANPP, which was primarily driven by limited growth of forbs in the first year and grasses in the second year. Total ANPP completely recovered as the rapid recovery of grass productivity compensated for the slow recovery of forb productivity. The subsequent drought led to a greater reduction in total ANPP than the initial drought due to the greater decline of both grass and forb productivity. The structural equation models revealed that soil moisture influenced ANPP responses directly during the initial drought, and indirectly during the subsequent drought by lowering functional diversity, which resulted in reduced total ANPP. Additionally, ANPP was positively influenced by CWM plant height and leaf nitrogen during the recovery period and recurrent drought, respectively. Overall, the greater impact of the second drought on ecosystem function than the initial drought, as well as the underlying differential mechanism, underscores the need for an understanding of how increased drought frequency may alter semiarid grassland functioning.

Relative sensitivity of hydrodynamic, thermodynamic, and chemical processes for simulating the buoyant multiphase plume and surfacing flows of an oil and gas blowout - Anusha L. Dissanayake; Scott A. Socolofsky; Jonas Gros; Inok Jun; Lin Zhao; Michel C. Boufadel; J. Samuel Arey (Marine Pollution Bulletin, 2023)

Early pregnancy essential and non-essential metal mixtures and maternal antepartum and postpartum depressive symptoms - Lisa B. Rokoff; Andres Cardenas; Pi-I D. Lin; Sheryl L. Rifas-Shiman; Robert O. Wright; Michelle Bosquet Enlow; Brent A. Coull; Emily Oken; Susan A. Korrick (NeuroToxicology, 2023)

Non-essential and essential trace element mixtures and kidney function in early pregnancy – A cross-sectional analysis in project viva - Pi-I.D. Lin; Andres Cardenas; Sheryl L. Rifas-Shiman; Ami R. Zota; Marie-France Hivert; Izzuddin M. Aris; Alison P. Sanders (Environmental Research, 2023)

An ultra-sensitive and specific nanoplasmonic-enhanced isothermal amplification platform for the ultrafast point-of-care testing of SARS-CoV-2 - Juxiang Liu; Ping Chen; Xulong Hu; Liping Huang; Zhi Geng; Hao Xu; Wenjun Hu; Lin Wang; Ping Wu; Gang L. Liu (Chemical Engineering Journal, 2023)

Elastoplastic Modelling of Porous Limestones with Porosity Dependency - B. Han; Q. M. Gong; X. L. Du; Y. Gao; W. Q. Shen; S. Lin (Rock Mechanics and Rock Engineering, 2022)

Dancing to a different tune: changing reproductive seasonality in an introduced chital deer population - Catherine L. Kelly; Lin Schwarzkopf; Iain J. Gordon; Anthony Pople; David L. Kelly; Ben T. Hirsch (Oecologia, 2022)
Male and female reproductive behaviour is typically synchronised. In species such as those in the family Cervidae , reproductive timing is often cued by photoperiod, although in females, it can be dependent on body condition. When a species is introduced to a novel environment, the environment changes, or responses of the sexes to such cues differ, asynchronous reproductive behaviour between males and females may occur. We investigated the seasonality of reproductive behaviour in introduced chital deer in northern Queensland by examining male antler phase in relation to female conception rates. We then analysed the influence of different variables likely to affect the timing of male and female reproductive physiology. The lowest percentage of chital in hard antler in any 1 month in this study was 35% (Fig. 1), but the average value was closer to 50%, thus there was a seasonal peak in antler phase linked with photoperiod. Females conceived at any time of year, but were strongly influenced by the amount of rainfall 3 months prior to conception. This resulted in varying conception peaks year-to-year that often did not correspond to the male’s peak in hard antler. In this system, a proportion of males and females were physiologically and behaviourally ready to mate at any time of the year. We predict that differences in the timing of the peaks between the males and females will lead to increased reproductive skew (variation in reproductive success among individual males). This pattern may select for different mating strategies or physiological mechanisms to increase reproductive success.

A study of peatland-derived dissolved organic matter from headstream to sea using multiple analytical tools - François L. L. Muller; Kuei-Chen Chang; Yu-Chieh Wang; Chon-Lin Lee (Environmental Science and Pollution Research, 2022)

A 10-miRNA risk score-based prediction model for pathological complete response to neoadjuvant chemotherapy in hormone receptor-positive breast cancer - Chang Gong; Ziliang Cheng; Yaping Yang; Jun Shen; Yingying Zhu; Li Ling; Wanyi Lin; Zhigang Yu; Zhihua Li; Weige Tan; Chushan Zheng; Wenbo Zheng; et al. (Science China Life Sciences, 2022)

Long‐term drought aggravates instability of alpine grassland productivity to extreme climatic event - Yun L. He; Jin S. Wang; Da S. Tian; Quan Quan; Lin Jiang; Fang F. Ma; Lu Yang; Fang Y. Zhang; Qing P. Zhou; Shu L. Niu (Ecology, 2022)
The frequency and severity of extreme weather events are increasing and expected to increase more in the future, together with global change. However, how extreme events and global change factors interactively influence community structures and ecosystem processes is largely unknown. Here, we investigated the responses of the temporal stability and resilience of aboveground net primary productivity (ANPP) of an alpine meadow to an extreme flooding event under different treatments of experimental drought and clipping. We found that ecosystems that were exposed to drought treatments for 3 years significantly decreased the temporal stability of community productivity but increased resilience to flooding, whereas their resistance to or recovery from flooding did not change. Neither clipping nor its interaction with drought altered the responses of these community stability metrics to flooding. Drought treatments significantly decreased plant species richness and asynchrony and dominant species stability, leading to a decrease in temporal stability and an increase in resilience in response to the extreme flooding event. The study also revealed that the change in species asynchrony was the dominant impact pathway determining the responses of resilience and temporal stability to flooding. Our results highlight that alpine grassland that experiences a multiyear drought may aggravate the instability of community productivity to extreme climatic events by reducing species asynchrony.

Anti-drug Antibody Sample Testing and Reporting Harmonization - Darshana Jani; Robin Marsden; Michele Gunsior; Laura Schild Hay; Bethany Ward; Kyra J. Cowan; Mitra Azadeh; Breann Barker; Liching Cao; Kristin R. Closson; Kelly Coble; Sanjay L. Dholakiya; et al. (The AAPS Journal, 2022)
A clear scientific and operational need exists for harmonized bioanalytical immunogenicity study reporting to facilitate communication of immunogenicity findings and expedient review by industry and health authorities. To address these key bioanalytical reporting gaps and provide a report structure for documenting immunogenicity results, this cross-industry group was formed to establish harmonized recommendations and a develop a submission template to facilitate agency filings. Provided here are recommendations for reporting clinical anti-drug antibody (ADA) assay results using ligand-binding assay technologies. This publication describes the essential bioanalytical report (BAR) elements such as the method, critical reagents and equipment, study samples, results, and data analysis, and provides a template for a suggested structure for the ADA BAR. This publication focuses on the content and presentation of the bioanalytical ADA sample analysis report. The interpretation of immunogenicity data, including the evaluation of the impact of ADA on safety, exposure, and efficacy, is out of scope of this publication. Graphical Abstract

Vulnerability of exploited deep-sea demersal species to ocean warming, deoxygenation, and acidification - William W. L. Cheung; Chih-Lin Wei; Lisa A. Levin (Environmental Biology of Fishes, 2022)

Acanthopagrus oconnorae , a new species of seabream (Sparidae) from the Red Sea - Lucía Pombo‐Ayora; Viktor N. Peinemann; Collin T. Williams; Song He; Yu Jia Lin; Yukio Iwatsuki; Donal D. C. Bradley; Michael L. Berumen (Journal of Fish Biology, 2022)
A new species of sparid fish, Acanthopagrus oconnorae , is described based on 11 specimens collected in the shallow (0–1 m depth) mangrove‐adjacent sandflats of Thuwal, Saudi Arabia. The new species is distinguished from its congeners by the following combination of characters: second anal‐fin spine 12.8%–16.6% of standard length (SL); 3½ scale rows between the fifth dorsal‐fin spine and lateral line; suborbital width 5.7%–6.7% of SL; eyes positioned at the anterior edge of the head, often forming a weakly convex break in an otherwise gently curved head profile, when viewed laterally; caudal fin light yellow with black posterior margin (approximately half of fin); anal fin dusky grey, with posterior one‐fifth of the fin light yellow; black streaks on inter‐radial membranes of anal fin absent. The most similar species to A. oconnorae is Acanthopagrus vagus , which differs by the presence of a w‐shaped anterior edge of the scaled predorsal area, a more acute snout and black streaks on the inter‐radial membranes of the anal fin. Phylogenetic placement and species delimitation of A. oconnorae are discussed based on COI, CytB and 16S sequences. It is hypothesized that ecology and behaviour explain how this species avoided detection despite its likely occurrence in coastal areas of the Red Sea with historically high fishing pressure.

Performance of Semi-passive Systems for the Biological Treatment of High-As Acid Mine Drainage: Results from a Year of Monitoring at the Carnoulès Mine (Southern France) - C. Diaz-Vanegas; C. Casiot; L. Lin; L. De Windt; M. Héry; A. Desoeuvre; O. Bruneel; F. Battaglia-Brunet; J. Jacob (Mine Water and the Environment, 2022)

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

An unknown component of a well-known population: socio-demographic parameters of Indo-Pacific humpback dolphins (Sousa chinensis) at the western reaches of the Pearl River Delta region - Stephen C. Y. Chan; Leszek Karczmarski; Wenzhi Lin; Ruiqiang Zheng; Yuen-Wa Ho; Lang Guo; Yaqian Mo; Andy T. L. Lee; Carmen K. M. Or; Yuping Wu (Mammalian Biology, 2022)

Tisch Cancer Institute Scholars Program: Mentored Cancer Research Training Pipeline for Medical Students - Kaitlyn Ben-David; Jenny J. Lin; James L. M. Ferrara; Janice L. Gabrilove (Journal of Cancer Education, 2022)

Modelling the variation of demersal fish distribution in Yellow Sea under climate change - Yugui Zhu; Yuting Lin; Jiansong Chu; Bin Kang; Gabriel Reygondeau; Qianshuo Zhao; Zhixin Zhang; Yunfeng Wang; William W. L. Cheung (Journal of Oceanology and Limnology, 2022)

A Brief Educational Intervention to Increase ED Initiation of Buprenorphine for Opioid Use Disorder (OUD) - Utsha G. Khatri; Kathleen Lee; Theodore Lin; Joseph L. D’Orazio; Mitesh S. Patel; Frances S. Shofer; Jeanmarie Perrone (Journal of Medical Toxicology, 2022)

Factors associated with changes in exercise behaviors during the COVID-19 pandemic - Caroline Himbert; Cassandra A. Hathaway; Bailee Daniels; Karen Salas; Anjelica Ashworth; Biljana Gigic; Tengda Lin; Richard Viskochil; Anne C. Kirchhoff; Douglas Grossman; Jennifer Ose; Jonathan Tward; et al. (Cancer Causes & Control, 2022)

Cerebellar Oscillations in Familial and Sporadic Essential Tremor - Shi-Bing Wong; Yi-Mei Wang; Chih-Chun Lin; Scott Kun Geng; Nora Vanegas-Arroyave; Seth L. Pullman; Sheng-Han Kuo; Ming-Kai Pan (The Cerebellum, 2022)

Parenthood among individuals with Turner syndrome: results of an online survey of attitudes towards pregnancy, adoption, and surrogacy - Erin Falsey; Allison L. Cirino; Emma Snyder; Marcie Steeves; Angela E. Lin (Journal of Community Genetics, 2022)

Evolution of Bordetella pertussis in the acellular vaccine era in Norway, 1996 to 2019 - Lin T. Brandal; Didrik F. Vestrheim; Torbjørn Bruvik; Ragnhild B. Roness; Martha L. Bjørnstad; Margrethe Greve-Isdahl; Anneke Steens; Ola B. Brynildsrud (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
We described the population structure of Bordetella pertussis ( B. pertussis ) in Norway from 1996 to 2019 and determined if there were evolutionary shifts and whether these correlated with changes in the childhood immunization program. We selected 180 B. pertussis isolates, 22 from the whole cell vaccine (WCV) era (1996–1997) and 158 from the acellular vaccine (ACV) era (1998–2019). We conducted whole genome sequencing and determined the distribution and frequency of allelic variants and temporal changes of ACV genes. Norwegian B. pertussis isolates were evenly distributed across a phylogenetic tree that included global strains. We identified seven different allelic profiles of ACV genes (A–F), in which profiles A1, A2, and B dominated (89%), all having pertussis toxin ( ptxA ) allele 1, pertussis toxin promoter ( ptxP ) allele 3, and pertactin ( prn ) allele 2 present. Isolates with ptxP1 and prn1 were not detected after 2007, whereas the prn2 allele likely emerged prior to 1972, and ptxP3 before the early 1980s. Allele conversions of ACV genes all occurred prior to the introduction of ACV. Sixteen percent of our isolates showed mutations within the prn gene. ACV and its booster doses (implemented for children in 2007 and adolescents in 2013) might have contributed to evolvement of a more uniform B. pertussis population, with recent circulating strains having ptxA1 , ptxP3 , and prn2 present, and an increasing number of prn mutations. These strains clearly deviate from ACV strains ( ptxA1 , ptxP1 , prn1 ), and this could have implications for vaccine efficiency and, therefore, prevention and control of pertussis.

Anomaly and cyber fraud detection in pipelines and supply chains for liquid fuels - Alinne Beteto; Vidal Melo; Jessica Lin; Marwan Alsultan; Eduardo Mario Dias; Elizabeth Korte; DeAndre A. Johnson; Negin Moghadasi; Thomas L. Polmateer; James H. Lambert (Environment Systems and Decisions, 2022)

Trametes suaveolens-derived biochar loaded on nanoscale zero-valent iron particles for the adsorption and reduction of Cr(VI) - W.-D. Wang; H.-T. Ma; W. Lin; P. Sun; L.-K. Zhang; J.-H. Han (International Journal of Environmental Science and Technology, 2022)

Very Low Stocks and Inputs of Necromass in Wind-affected Tropical Forests - Kuo-Jung Chao; Pin-Siou Liao; Yi-Sheng Chen; Guo-Zhang Michael Song; Oliver L. Phillips; Hsing-Juh Lin (Ecosystems, 2022)

Low Redox Decreases Potential Phosphorus Limitation on Soil Biogeochemical Cycling Along a Tropical Rainfall Gradient - Yang Lin; Avner Gross; Whendee L. Silver (Ecosystems, 2022)

Gene duplication to the Y chromosome in Trinidadian Guppies - Yuying Lin; Iulia Darolti; Benjamin L. S. Furman; Pedro Almeida; Benjamin A. Sandkam; Felix Breden; Alison E. Wright; Judith E. Mank (Molecular Ecology, 2022)
Differences in allele frequencies at autosomal genes between males and females in a population can result from two scenarios. First, unresolved sexual conflict over survival can produce allelic differentiation between the sexes. However, given the substantial mortality costs required to produce allelic differences between males and females at each generation, it remains unclear how many loci within the genome experience significant sexual conflict over survival. Alternatively, recent studies have shown that similarity between autosomal and Y sequences can create perceived allelic differences between the sexes. However, Y duplications are most likely in species with large nonrecombining regions, in part because they simply represent larger targets for duplications. We assessed the genomes of 120 wild‐caught guppies, which experience extensive predation‐ and pathogen‐induced mortality and have a relatively small ancestral Y chromosome. We identified seven autosomal genes that show allelic differences between male and female adults. Five of these genes show clear evidence of whole or partial gene duplication between the Y chromosome and the autosomes. The remaining two genes show evidence of partial homology to the Y. Overall, our findings suggest that the guppy genome experiences a very low level of unresolved sexual conflict over survival, and instead the Y chromosome, despite its small ancestral size and recent origin, may nonetheless accumulate genes with male‐specific functions.

miR-146a-5p modulates cellular senescence and apoptosis in visceral adipose tissue of long-lived Ames dwarf mice and in cultured pre-adipocytes - Allancer D. C. Nunes; Moritz Weigl; Augusto Schneider; Sarah Noureddine; Lin Yu; Collin Lahde; Tatiana Dandolini Saccon; Kunal Mitra; Esther Beltran; Johannes Grillari; James L. Kirkland; Tamara Tchkonia; et al. (GeroScience, 2022)

Antigen production and development of an indirect ELISA based on the nucleocapsid protein to detect human SARS-CoV-2 seroconversion - Marcelo S. Conzentino; Karl Forchhammer; Emanuel M. Souza; Fábio O. Pedrosa; Meri B. Nogueira; Sônia M. Raboni; Fabiane G. M. Rego; Dalila L. Zanette; Mateus N. Aoki; Jeanine M. Nardin; Bruna Fornazari; Hugo M. P. Morales; et al. (Brazilian Journal of Microbiology, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

First Evidence of Cryptic Species Diversity and Population Structuring of Selaroides leptolepis in the Tropical Western Pacific - Lorenzo C. Halasan; Paul John L. Geraldino; Hsiu-Chin Lin (Frontiers in Marine Science, 2021)
The yellowstripe scad, Selaroides leptolepis (Carangidae), is an important fish commodity in the Tropical Western Pacific (TWP). It has a latitudinal Pacific range from south of Japan down to northern Australia, with the highest concentration in Southeast Asia. However, its TWP fishing grounds have long been a hotspot of unsustainable exploitations, thus threatening the remaining wild populations. Despite the species’ commercial significance, there is limited understanding of its genetic structure and diversity. Herein, the genetic structure of S. leptolepis was examined using mitochondrial COI and CytB sequences. Both markers denoted significant genetic structuring based on high overall F ST values. Hierarchical analysis of molecular variance (AMOVA), maximum likelihood (ML) phylogenetic trees, and median-joining (MJ) haplotype networks strongly supported the occurrence of two allopatrically distributed lineages. These comprised of a widespread Asian lineage and an isolated Australian lineage. Within-lineage distances were low (K2P < 1%) whereas across-lineage distances were remarkably high (K2P > 6%), already comparable to that of interspecific carangid divergences. Haplotype sequence memberships, high genetic variations, and the geographic correlation suggested that the Australian lineage was a putative cryptic species. Historical demographic inferences also revealed that the species experienced rapid expansion commencing on the late Pleistocene, most likely during the end of the Last Glacial Maximum (∼20,000 years ago). The present study encouraged the application of lineage-specific management efforts, as the lineages are experiencing different evolutionary pressures. Overall, accurate knowledge of the species’ genetic distribution is fundamental in protecting its diversity and assuring stock sustainability.

Comparing the clinical outcomes across different sodium/glucose cotransporter 2 (SGLT2) inhibitors in heart failure patients: a systematic review and network meta-analysis of randomized controlled trials - Yao Hao Teo; Celine Shuen Yin Yoong; Nicholas L. Syn; Yao Neng Teo; Jia Yang Alex Cheong; Yoke-Ching Lim; Chi-Hang Lee; Tiong-Cheng Yeo; Ping Chai; Raymond C. C. Wong; Weiqin Lin; Ching-Hui Sia (European Journal of Clinical Pharmacology, 2021)

Numerical and experimental studies of turbulence in vegetated open-channel flows - Xiaochun Tang; Pengzhi Lin; Philip L.-F. Liu; Xiaofeng Zhang (Environmental Fluid Mechanics, 2021)

Distribution, Temporal Change, and Conservation Status of Tropical Seagrass Beds in Southeast Asia: 2000–2020 - Kenji Sudo; T. E. Angela L. Quiros; Anchana Prathep; Cao Van Luong; Hsing-Juh Lin; Japar Sidik Bujang; Jillian Lean Sim Ooi; Miguel D. Fortes; Muta Harah Zakaria; Siti Maryam Yaakub; Yi Mei Tan; Xiaoping Huang; et al. (Frontiers in Marine Science, 2021)
Although Southeast Asia is a hotspot of global seagrass diversity, there are considerable information gaps in the distribution of seagrass beds. Broad-scale seagrass distribution has not been updated in the global seagrass database by UNEP-WCMC since 2000, although studies on seagrasses have been undertaken intensively in each region. Here we analyze the recent distribution of tropical seagrass beds, their temporal changes, causes of decline and conservation status in Southeast Asia (plus southern mainland China, Taiwan and Ryukyu Island of Japan) using data collected after 2000. Based on the 195 literature published since 2000, we identified 1,259 point data and 1,461 polygon data showing the distribution of seagrass beds. A large discrepancy was found in the seagrass bed distribution between our updated data and the UNEP-WCMC database, mostly due to inaccurate and low resolution location information in the latter. Temporal changes in seagrass bed area analyzed for 68 sites in nine countries/regions demonstrated that more than 60% of seagrass beds declined at an average rate of 10.9% year –1 , whereas 20% of beds increased at an average rate of 8.1% year –1 , leading to an overall average decline of 4.7% year –1 . Various types of human-induced threats were reported as causes for the decline, including coastal development, fisheries/aquaculture, and natural factors such as typhoons and tsunamis. The percentage of seagrass beds covered with existing marine protected areas (MPAs) varied greatly among countries/regions, from less than 1% in Brunei Darussalam and Singapore to 100% in southern Japan. However, the degree of conservation regulation was not sufficient even in regions with higher MPA coverage. The percentage of seagrass beds within EBSAs (Ecologically and Biologically Significant Area determined by the Convention of Biological Diversity) was higher than that within MPAs because EBSAs cover a greater area than MPAs. Therefore, designating EBSAs as legally effective MPAs can greatly improve the conservation status of seagrass beds in Southeast Asia.

Effect of water regime and harvest stage on essential oil accumulation in basil plant growing in sandy soil - João V. R. S. Souza; Lin Chau Ming; Marcos A. L. Santos; James E. Simon; Hector R. Juliani; João C. C. Saad (Irrigation Science, 2021)

Effects of process factors on the performance of electrochemical disinfection for wastewater in a continuous-flow cell reactor - Che-Jen Lin; Ruolin Zhang; Scott A. Waisner; Tabish Nawaz; Lori Center; David B. Gent; Jared L. Johnson; Sabin Holland (Environmental Science and Pollution Research, 2021)

Correction to: Genomic Action of Sigma-1 Receptor Chaperone Relates to Neuropathic Pain - Shao-Ming Wang; Nino Goguadze; Yuriko Kimura; Yuko Yasui; Bin Pan; Tzu-Yun Wang; Yoki Nakamura; Yu-Ting Lin; Quinn H. Hogan; Katherine L. Wilson; Tsung-Ping Su; Hsiang-en Wu (Molecular Neurobiology, 2021)
A correction to this paper has been published: 10.1007/s12035-021-02310-3

Genomic Action of Sigma-1 Receptor Chaperone Relates to Neuropathic Pain - Shao-Ming Wang; Nino Goguadze; Yuriko Kimura; Yuko Yasui; Bin Pan; Tzu-Yun Wang; Yoki Nakamura; Yu-Ting Lin; Quinn H. Hogan; Katherine L. Wilson; Tsung-Ping Su; Hsiang-en Wu (Molecular Neurobiology, 2021)
Sigma-1 receptors (Sig-1Rs) are endoplasmic reticulum (ER) chaperones implicated in neuropathic pain. Here we examine if the Sig-1R may relate to neuropathic pain at the level of dorsal root ganglia (DRG). We focus on the neuronal excitability of DRG in a “spare nerve injury” (SNI) model of neuropathic pain in rats and find that Sig-1Rs likely contribute to the genesis of DRG neuronal excitability by decreasing the protein level of voltage-gated Cav2.2 as a translational inhibitor of mRNA. Specifically, during SNI, Sig-1Rs translocate from ER to the nuclear envelope via a trafficking protein Sec61β. At the nucleus, the Sig-1R interacts with cFos and binds to the promoter of 4E-BP1, leading to an upregulation of 4E-BP1 that binds and prevents eIF4E from initiating the mRNA translation for Cav2.2. Interestingly, in Sig-1R knockout HEK cells, Cav2.2 is upregulated. In accordance with those findings, we find that intra-DRG injection of Sig-1R agonist (+)pentazocine increases frequency of action potentials via regulation of voltage-gated Ca2+ channels. Conversely, intra-DRG injection of Sig-1R antagonist BD1047 attenuates neuropathic pain. Hence, we discover that the Sig-1R chaperone causes neuropathic pain indirectly as a translational inhibitor.

Cultivation of halophilic archaea (class Halobacteria) from thalassohaline and athalassohaline environments - Heng-Lin Cui; Mike L. Dyall-Smith (Marine Life Science & Technology, 2021)

Pomc Plays an Important Role in Sexual Size Dimorphism in Tilapia - Z. Y. Wan; V. C. L. Lin; Yue Gen Hua (Marine Biotechnology, 2021)

A global collaboration to study intimate partner violence-related head trauma: The ENIGMA consortium IPV working group - Carrie Esopenko; Jessica Meyer; Elisabeth A. Wilde; Amy D. Marshall; David F. Tate; Alexander P. Lin; Inga K. Koerte; Kimberly B. Werner; Emily L. Dennis; Ashley L. Ware; Nicola L. de Souza; Deleene S. Menefee; et al. (Brain Imaging and Behavior, 2021)

The clinical utility of proton magnetic resonance spectroscopy in traumatic brain injury: recommendations from the ENIGMA MRS working group - Brenda L Bartnik-Olson; Jeffry R Alger; Talin Babikian; Ashley D Harris; Barbara Holshouser; Ivan I Kirov; Andrew A Maudsley; Paul M Thompson; Emily L Dennis; David F Tate; Elisabeth A Wilde; Alexander Lin (Brain Imaging and Behavior, 2021)

The ENIGMA sports injury working group:– an international collaboration to further our understanding of sport-related brain injury - Inga K. Koerte; Carrie Esopenko; Sidney R. Hinds; Martha E. Shenton; Elena M. Bonke; Jeffrey J. Bazarian; Kevin C. Bickart; Erin D. Bigler; Sylvain Bouix; Thomas A. Buckley; Meeryo C. Choe; Paul S. Echlin; et al. (Brain Imaging and Behavior, 2021)
Sport-related brain injury is very common, and the potential long-term effects include a wide range of neurological and psychiatric symptoms, and potentially neurodegeneration. Around the globe, researchers are conducting neuroimaging studies on primarily homogenous samples of athletes. However, neuroimaging studies are expensive and time consuming, and thus current findings from studies of sport-related brain injury are often limited by small sample sizes. Further, current studies apply a variety of neuroimaging techniques and analysis tools which limit comparability among studies. The ENIGMA Sports Injury working group aims to provide a platform for data sharing and collaborative data analysis thereby leveraging existing data and expertise. By harmonizing data from a large number of studies from around the globe, we will work towards reproducibility of previously published findings and towards addressing important research questions with regard to diagnosis, prognosis, and efficacy of treatment for sport-related brain injury. Moreover, the ENIGMA Sports Injury working group is committed to providing recommendations for future prospective data acquisition to enhance data quality and scientific rigor.

Glutathione and the intracellular labile heme pool - Rosemary O’Keeffe; Gladys Oluyemisi Latunde-Dada; Yu-Lin Chen; Xiaole L. Kong; Agostino Cilibrizzi; Robert C. Hider (BioMetals, 2021)
One candidate for the cytosolic labile iron pool is iron(II)glutathione. There is also a widely held opinion that an equivalent cytosolic labile heme pool exists and that this pool is important for the intracellular transfer of heme. Here we describe a study designed to characterise conjugates that form between heme and glutathione. In contrast to hydrated iron(II), heme reacts with glutathione, under aerobic conditions, to form the stable hematin–glutathione complex, which contains iron(III). Thus, glutathione is clearly not the cytosolic ligand for heme, indeed we demonstrate that the rate of heme degradation is enhanced in the presence of glutathione. We suggest that the concentration of heme in the cytosol is extremely low and that intracellular heme transfer occurs via intracellular membrane structures. Should any heme inadvertently escape into the cytosol, it would be rapidly conjugated to glutathione thereby protecting the cell from the toxic effects of heme.

A Millifluidic Perfusion Cassette for Studying the Pathogenesis of Enteric Infections Using Ex-Vivo Organoids - Reid L. Wilson; Sarah A. Hewes; Anubama Rajan; Shih-Ching Lin; Carolyn Bomidi; Takanori Iida; Mary K. Estes; Anthony W. Maresso; K. Jane Grande-Allen (Annals of Biomedical Engineering, 2021)

The influence of vector‐borne disease on human history: socio‐ecological mechanisms - Tejas S. Athni; Marta S. Shocket; Lisa I. Couper; Nicole Nova; Iain R. Caldwell; Jamie M. Caldwell; Jasmine N. Childress; Marissa L. Childs; Giulio A. De Leo; Devin G. Kirk; Andrew J. MacDonald; Kathryn Olivarius; et al. (Ecology Letters, 2021)
Vector‐borne diseases (VBDs) are embedded within complex socio‐ecological systems. While research has traditionally focused on the direct effects of VBDs on human morbidity and mortality, it is increasingly clear that their impacts are much more pervasive. VBDs are dynamically linked to feedbacks between environmental conditions, vector ecology, disease burden, and societal responses that drive transmission. As a result, VBDs have had profound influence on human history. Mechanisms include: (1) killing or debilitating large numbers of people, with demographic and population‐level impacts; (2) differentially affecting populations based on prior history of disease exposure, immunity, and resistance; (3) being weaponised to promote or justify hierarchies of power, colonialism, racism, classism and sexism; (4) catalysing changes in ideas, institutions, infrastructure, technologies and social practices in efforts to control disease outbreaks; and (5) changing human relationships with the land and environment. We use historical and archaeological evidence interpreted through an ecological lens to illustrate how VBDs have shaped society and culture, focusing on case studies from four pertinent VBDs: plague, malaria, yellow fever and trypanosomiasis. By comparing across diseases, time periods and geographies, we highlight the enormous scope and variety of mechanisms by which VBDs have influenced human history.

The conduction velocity-potassium relationship in the heart is modulated by sodium and calcium - D. Ryan King; Michael Entz; Grace A. Blair; Ian Crandell; Alexandra L. Hanlon; Joyce Lin; Gregory S. Hoeker; Steven Poelzing (Pflügers Archiv - European Journal of Physiology, 2021)
The relationship between cardiac conduction velocity (CV) and extracellular potassium (K + ) is biphasic, with modest hyperkalemia increasing CV and severe hyperkalemia slowing CV. Recent studies from our group suggest that elevating extracellular sodium (Na + ) and calcium (Ca 2+ ) can enhance CV by an extracellular pathway parallel to gap junctional coupling (GJC) called ephaptic coupling that can occur in the gap junction adjacent perinexus. However, it remains unknown whether these same interventions modulate CV as a function of K + . We hypothesize that Na + , Ca 2+ , and GJC can attenuate conduction slowing consequent to severe hyperkalemia. Elevating Ca 2+ from 1.25 to 2.00 mM significantly narrowed perinexal width measured by transmission electron microscopy. Optically mapped, Langendorff-perfused guinea pig hearts perfused with increasing K + revealed the expected biphasic CV-K + relationship during perfusion with different Na + and Ca 2+ concentrations. Neither elevating Na + nor Ca 2+ alone consistently modulated the positive slope of CV-K + or conduction slowing at 10-mM K + ; however, combined Na + and Ca 2+ elevation significantly mitigated conduction slowing at 10-mM K + . Pharmacologic GJC inhibition with 30-μM carbenoxolone slowed CV without changing the shape of CV-K + curves. A computational model of CV predicted that elevating Na + and narrowing clefts between myocytes, as occur with perinexal narrowing, reduces the positive and negative slopes of the CV-K + relationship but do not support a primary role of GJC or sodium channel conductance. These data demonstrate that combinatorial effects of Na + and Ca 2+ differentially modulate conduction during hyperkalemia, and enhancing determinants of ephaptic coupling may attenuate conduction changes in a variety of physiologic conditions.

Genetic diversity and life‐history traits of bonefish Albula spp. from the Red Sea - Collin T. Williams; Ashlie J. McIvor; Elizabeth M. Wallace; Yu‐Jia Lin; Michael L. Berumen (Journal of Fish Biology, 2021)
The management of bonefishes Albula spp. has been hindered by unresolved species distributions and a general lack of life‐history information. This study provides the first genetic species identifications of Albula spp. from the northern Indian Ocean. The roundjaw bonefish Albula glossodonta was documented in the Red Sea, and the smallscale bonefish A. oligolepis was identified in the Gulf of Aden with no evidence supporting sympatry. Estimates of genetic differentiation indicate three closely related lineages of A. glossodonta in the Red Sea, Indian Ocean and Pacific Ocean (Red Sea‐Pacific Ocean, F st = 0.295; Red Sea‐Seychelles, F st = 0.193; Pacific Ocean‐Seychelles, F st = 0.141). In addition, the authors provide the first life‐history information of Albula spp. in the Indian Ocean. Age‐based growth models of A. glossodonta from the Red Sea demonstrated statistically significant differences compared to previously published data from the Pacific Ocean. Spawning activity during winter months was derived from gonado‐somatic index values of A. glossodonta from the Red Sea and corresponded with spawning seasonality previously documented for the species in the Pacific Ocean. The results of this study aid in refining biogeographical uncertainties of Albula spp. and illustrate the importance of collecting regional growth information for subsequent management of A. glossodonta .

Preformulation Characterization of Griffithsin, a Biopharmaceutical Candidate for HIV Prevention - Lindsay F. Kramzer; Krystal T. Hamorsky; Phillip W. Graebing; Lin Wang; Joshua L. Fuqua; Nobuyuki Matoba; Amanda B. Lasnik; Bernard J. Moncla; Junmei Zhang; Kenneth E. Palmer; Lisa C. Rohan (AAPS PharmSciTech, 2021)

Fracture Propagation of Rock like Material with a Fluid-Infiltrated Pre-existing Flaw Under Uniaxial Compression - C. Wei; B. Zhang; W. Zhu; S. Wang; J. Li; ·L. Yang; C. Lin (Rock Mechanics and Rock Engineering, 2021)

Machine learning prediction of neurocognitive impairment among people with HIV using clinical and multimodal magnetic resonance imaging data - Yunan Xu; Yizi Lin; Ryan P. Bell; Sheri L. Towe; John M. Pearson; Tauseef Nadeem; Cliburn Chan; Christina S. Meade (Journal of NeuroVirology, 2021)

Fine-scale roadkill risk models: understanding the intersection of wildlife and roads - Kristina Chyn; Te-En Lin; David P. Wilkinson; James L. Tracy; A. Michelle Lawing; Lee A. Fitzgerald (Biodiversity and Conservation, 2021)

Exposure to a high dose of amoxicillin causes behavioral changes and oxidative stress in young zebrafish - Cinara L. Gonçalves; Francine F. P. Vasconcelos; Leticia B. Wessler; Isabela S. Lemos; Gabriela Candiotto; Jaime Lin; Mariane B. D. Matias; Eduardo P. Rico; Emilio L. Streck (Metabolic Brain Disease, 2020)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Peripheral ProBDNF Delivered by an AAV Vector to the Muscle Triggers Depression-Like Behaviours in Mice - L. Y. Lin; S. Kelliny; L. C. Liu; M. Al-Hawwas; X. F. Zhou; L. Bobrovskaya (Neurotoxicity Research, 2020)

A magnetic resonance spectroscopy investigation in symptomatic former NFL players - Michael L. Alosco; Yorghos Tripodis; Benjamin Rowland; Alicia S. Chua; Huijun Liao; Brett Martin; Johnny Jarnagin; Christine E. Chaisson; Ofer Pasternak; Sarina Karmacharya; Inga K. Koerte; Robert C. Cantu; et al. (Brain Imaging and Behavior, 2020)

Climate change considerations are fundamental to management of deep‐sea resource extraction - Lisa A. Levin; Chih‐Lin Wei; Daniel C. Dunn; Diva J. Amon; Oliver S. Ashford; William W. L. Cheung; Ana Colaço; Carlos Dominguez‐Carrió; Elva G. Escobar; Harriet R. Harden‐Davies; Jeffrey C. Drazen; Khaira Ismail; et al. (Global Change Biology, 2020)
Climate change manifestation in the ocean, through warming, oxygen loss, increasing acidification, and changing particulate organic carbon flux (one metric of altered food supply), is projected to affect most deep‐ocean ecosystems concomitantly with increasing direct human disturbance. Climate drivers will alter deep‐sea biodiversity and associated ecosystem services, and may interact with disturbance from resource extraction activities or even climate geoengineering. We suggest that to ensure the effective management of increasing use of the deep ocean (e.g., for bottom fishing, oil and gas extraction, and deep‐seabed mining), environmental management and developing regulations must consider climate change. Strategic planning, impact assessment and monitoring, spatial management, application of the precautionary approach, and full‐cost accounting of extraction activities should embrace climate consciousness. Coupled climate and biological modeling approaches applied in the water and on the seafloor can help accomplish this goal. For example, Earth‐System Model projections of climate‐change parameters at the seafloor reveal heterogeneity in projected climate hazard and time of emergence (beyond natural variability) in regions targeted for deep‐seabed mining. Models that combine climate‐induced changes in ocean circulation with particle tracking predict altered transport of early life stages (larvae) under climate change. Habitat suitability models can help assess the consequences of altered larval dispersal, predict climate refugia, and identify vulnerable regions for multiple species under climate change. Engaging the deep observing community can support the necessary data provisioning to mainstream climate into the development of environmental management plans. To illustrate this approach, we focus on deep‐seabed mining and the International Seabed Authority, whose mandates include regulation of all mineral‐related activities in international waters and protecting the marine environment from the harmful effects of mining. However, achieving deep‐ocean sustainability under the UN Sustainable Development Goals will require integration of climate consideration across all policy sectors.

An integrated biophysical approach to discovering mechanisms of NDM-1 inhibition for several thiol-containing drugs - Sarah Fullington; Zishuo Cheng; Caitlyn Thomas; Callie Miller; Kundi Yang; Lin-Cheng Ju; Alexander Bergstrom; Ben A. Shurina; Stacey Lowery Bretz; Richard C. Page; David L. Tierney; Michael W. Crowder (JBIC Journal of Biological Inorganic Chemistry, 2020)

Correction to: Potato Cultivar Susceptibility to Pythium Leak as Influenced by Harvest and Early Storage Temperatures - Andrew K Hollingshead; Nora L. Olsen; Mike Thornton; Jeff S. Miller; Amy Hui-Mei Lin (American Journal of Potato Research, 2020)

Potato Cultivar Susceptibility to Pythium Leak as Influenced by Harvest and Early Storage Temperatures - Andrew K Hollingshead; Nora L. Olsen; Mike Thornton; Jeff S. Miller; Amy Hui-Mei Lin (American Journal of Potato Research, 2020)

A System Level Analysis of Coastal Ecosystem Responses to Hurricane Impacts - C. J. Patrick; L. Yeager; A. R. Armitage; F. Carvallo; V. M. Congdon; K. H. Dunton; M. Fisher; A. K. Hardison; J. D. Hogan; J. Hosen; X. Hu; B. Kiel Reese; et al. (Estuaries and Coasts, 2020)

Toxicity assessment of electrochemical advanced oxidation process-treated groundwater from a gas station with petrochemical contamination - How-Ran Chao; Danielle E. Que; Alisha C. Aquino; Yan-You Gou; Lemmuel L. Tayo; Yi-Hsien Lin; Ming-Hsien Tsai; Fu-Lin Hsu; I-Cheng Lu; Sheng-Lun Lin; Natwat Srikhao; Cherng-Gueih Shy; et al. (Environmental Monitoring and Assessment, 2020)

Waiting and “weighted down”: the challenge of anticipatory loss for individuals and families with Li-Fraumeni Syndrome - Allison Werner-Lin; Jennifer L. Young; Catherine Wilsnack; Shana L. Merrill; Victoria Groner; Mark H. Greene; Payal P. Khincha (Familial Cancer, 2020)

DNA methylation and histone acetylation changes to cytochrome P450 2E1 regulation in normal aging and impact on rates of drug metabolism in the liver - Mohamad M. Kronfol; Fay M. Jahr; Mikhail G. Dozmorov; Palak S. Phansalkar; Lin Y. Xie; Karolina A. Aberg; MaryPeace McRae; Elvin T. Price; Patricia W. Slattum; Philip M. Gerk; Joseph L. McClay (GeroScience, 2020)

Assessment of ammonium fertilization as a stimulus for proline accumulation in Oryza sativa L. during cyanide assimilation - W. Liu; X.-Z. Yu; S.-Y. Lei; L. Yang; Y.-J. Lin (International Journal of Environmental Science and Technology, 2020)

Climate‐induced changes in the suitable habitat of cold‐water corals and commercially important deep‐sea fishes in the North Atlantic - Telmo Morato; José‐Manuel González‐Irusta; Carlos Dominguez‐Carrió; Chih‐Lin Wei; Andrew Davies; Andrew K. Sweetman; Gerald H. Taranto; Lindsay Beazley; Ana García‐Alegre; Anthony Grehan; Pascal Laffargue; Francisco Javier Murillo; et al. (Global Change Biology, 2020)
The deep sea plays a critical role in global climate regulation through uptake and storage of heat and carbon dioxide. However, this regulating service causes warming, acidification and deoxygenation of deep waters, leading to decreased food availability at the seafloor. These changes and their projections are likely to affect productivity, biodiversity and distributions of deep‐sea fauna, thereby compromising key ecosystem services. Understanding how climate change can lead to shifts in deep‐sea species distributions is critically important in developing management measures. We used environmental niche modelling along with the best available species occurrence data and environmental parameters to model habitat suitability for key cold‐water coral and commercially important deep‐sea fish species under present‐day (1951–2000) environmental conditions and to project changes under severe, high emissions future (2081–2100) climate projections (RCP8.5 scenario) for the North Atlantic Ocean. Our models projected a decrease of 28%–100% in suitable habitat for cold‐water corals and a shift in suitable habitat for deep‐sea fishes of 2.0°–9.9° towards higher latitudes. The largest reductions in suitable habitat were projected for the scleractinian coral Lophelia pertusa and the octocoral Paragorgia arborea , with declines of at least 79% and 99% respectively. We projected the expansion of suitable habitat by 2100 only for the fishes Helicolenus dactylopterus and Sebastes mentella (20%–30%), mostly through northern latitudinal range expansion. Our results projected limited climate refugia locations in the North Atlantic by 2100 for scleractinian corals (30%–42% of present‐day suitable habitat), even smaller refugia locations for the octocorals Acanella arbuscula and Acanthogorgia armata (6%–14%), and almost no refugia for P. arborea . Our results emphasize the need to understand how anticipated climate change will affect the distribution of deep‐sea species including commercially important fishes and foundation species, and highlight the importance of identifying and preserving climate refugia for a range of area‐based planning and management tools.

Correction to: Microsatellite records for volume 10, issue 2 - Dan Yu; Xueyun Ding; Zhi Zhang; Yu Zeng; Huanzhang Liu; Lin Wang; Ye Gong; Xingtu Liu; Xianguo Lyu; Gregory R. McCracken; Francisca V. Valenzuela-Aguayo; Evelyn M. Habit; et al. (Conservation Genetics Resources, 2020)

Cold treatment for guava fruits infested with oriental fruit fly, Bactrocera dorsalis (Diptera: Tephritidae) - Kao W. Lin; Huey L. Lin; Ching C. Shiesh; Yu. L. Hsu; Chih. H. Lin; Su. C. Chen; Wen B. Yeh (Applied Entomology and Zoology, 2020)

The role of soil redox conditions in microbial phosphorus cycling in humid tropical forests - Avner Gross; Yang Lin; Peter K. Weber; Jennifer Pett‐Ridge; Whendee L. Silver (Ecology, 2020)
Humid tropical forests are among the most productive ecosystems globally, yet they often occur on soils with high phosphorus (P) sorption capacity, lowering P availability to biota. Short‐term anoxic events are thought to release sorbed P and enhance its acquisition by soil microbes. However, the actual effects of anoxic conditions on microbial P acquisition in humid tropical forest soils are surprisingly poorly studied. We used laboratory incubations of bulk soils, NanoSIMS analysis of single microbial cells, and landscape‐scale measurements in the Luquillo Experimental Forest (LEF), Puerto Rico to test the hypothesis that anoxic conditions increase microbial P acquisition in humid tropical forests. In laboratory and field experiments, we found that microbial P uptake generally decreased under anoxic conditions, leading to high microbial carbon (C) to P ratios in anoxic soils. The decreased P acquisition under anoxic conditions was correlated with lower microbial C use efficiency (CUE), an index of microbial energy transfer in ecosystems. Phosphorus amendments to anoxic soils led to increased microbial P uptake and higher CUE suggesting that microbes were less able to access and utilize P under natural low redox conditions. Under oxic conditions, microbial C:P ratios and CUE did not respond to changes in substrate stoichiometry. These results challenge the existing paradigm by showing that anoxic conditions can decrease microbial P uptake and ultimately constrain microbial CUE. Our findings indicate that soil redox conditions tightly couple soil P and C cycles and advance our understanding of controls on P cycling in humid tropical forest ecosystems.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Expanding Tara Oceans Protocols for Underway, Ecosystemic Sampling of the Ocean-Atmosphere Interface During Tara Pacific Expedition (2016–2018) - Gabriel Gorsky; Guillaume Bourdin; Fabien Lombard; Maria Luiza Pedrotti; Samuel Audrain; Nicolas Bin; Emmanuel Boss; Chris Bowler; Nicolas Cassar; Loic Caudan; Genevieve Chabot; Natalie R. Cohen; et al. (Frontiers in Marine Science, 2019)

High-throughput transcriptome analysis reveals that the loss of Pten activates a novel NKX6-1/RASGRP1 regulatory module to rescue microphthalmia caused by Fgfr2-deficient lenses - Stephanie L. Padula; Deepti Anand; Thanh V. Hoang; Blake R. Chaffee; Lin Liu; Chun Liang; Salil A. Lachke; Michael L. Robinson (Human Genetics, 2019)

Characteristics and distribution of clay minerals and their effects on reservoir quality: Huagang Formation in the Xihu Sag, East China Sea Basin - X. L. Sun; C. Y. Lin; X. G. Zhang; J. L. Lin; Z. X. Zhao; D. W. Huang; D. P. Duan (Australian Journal of Earth Sciences, 2019)

Tropical cyclone sensitivities to CO2 doubling: roles of atmospheric resolution, synoptic variability and background climate changes - Gabriel A. Vecchi; Thomas L. Delworth; Hiroyuki Murakami; Seth D. Underwood; Andrew T. Wittenberg; Fanrong Zeng; Wei Zhang; Jane W. Baldwin; Kieran T. Bhatia; William Cooke; Jie He; Sarah B. Kapnick; et al. (Climate Dynamics, 2019)

Effect of Peptide AEDG on Telomere Length and Mitotic Index of PHA-Stimulated Human Blood Lymphocytes - V. Kh. Khavinson; A. A. Pendina; O. A. Efimova; A. V. Tikhonov; A. S. Koltsova; M. I. Krapivin; A. V. Petrovskaia-Kaminskaia; L. I. Petrova; N. S. Lin’kova; V. S. Baranov (Bulletin of Experimental Biology and Medicine, 2019)

The neural correlates of perceived energy levels in older adults with late-life depression - Charlene L. M. Lam; Ho-Ling Liu; Chih-Mao Huang; Yau-Yau Wai; Shwu-Hua Lee; Jenny Yiend; Chemin Lin; Tatia M. C. Lee (Brain Imaging and Behavior, 2019)

Bismuth(III) interactions with Desulfovibrio desulfuricans: inhibition of cell energetics and nanocrystal formation of Bi2S3 and Bi0 - Larry L. Barton; Alex S. Granat; Seungyeol Lee; Huifang Xu; Nathaniel L. Ritz; Robert Hider; Henry C. Lin (BioMetals, 2019)

The Long-Term Effects of Ethanol and Corticosterone on the Mood-Related Behaviours and the Balance Between Mature BDNF and proBDNF in Mice - L. Y. Lin; S. Y. Luo; M. Al-Hawwas; M. F. Herselman; X. F. Zhou; Larisa Bobrovskaya (Journal of Molecular Neuroscience, 2019)

Global Perspectives on Observing Ocean Boundary Current Systems - Robert E. Todd; Francisco P. Chavez; Sophie Clayton; Sophie Cravatte; Marlos Goes; Michelle Graco; Xiaopei Lin; Janet Sprintall; Nathalie V. Zilberman; Matthew Archer; Javier Arístegui; Magdalena Balmaseda; et al. (Frontiers in Marine Science, 2019)

Foundations and Frontiers of Ecosystem Science: Legacy of a Classic Paper (Odum 1969) - Jessica R. Corman; Scott L. Collins; Elizabeth M. Cook; Xiaoli Dong; Laureano A. Gherardi; Nancy B. Grimm; Rebecca L. Hale; Tao Lin; Jorge Ramos; Lara G. Reichmann; Osvaldo E. Sala (Ecosystems, 2019)

Wake Characteristics of Tall Buildings in a Realistic Urban Canopy - Denise Hertwig; Hannah L. Gough; Sue Grimmond; Janet F. Barlow; Christoph W. Kent; William E. Lin; Alan G. Robins; Paul Hayden (Boundary-Layer Meteorology, 2019)

Ocean Climate Observing Requirements in Support of Climate Research and Climate Information - Detlef Stammer; Annalisa Bracco; Krishna AchutaRao; Lisa Beal; Nathaniel L. Bindoff; Pascale Braconnot; Wenju Cai; Dake Chen; Matthew Collins; Gokhan Danabasoglu; Boris Dewitte; Riccardo Farneti; et al. (Frontiers in Marine Science, 2019)

Perspective: Something Old, Something New? Review of Wasting and Other Mortality in Asteroidea (Echinodermata) - Ian Hewson; Brooke Sullivan; Elliot W. Jackson; Qiang Xu; Hao Long; Chenggang Lin; Eva Marie Quijano Cardé; Justin Seymour; Nachshon Siboni; Matthew R. L. Jones; Mary A. Sewell (Frontiers in Marine Science, 2019)

Taxonomy of the order Mononegavirales: update 2019 - Gaya K. Amarasinghe; María A. Ayllón; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Camila Chabi-Jesus; et al. (Archives of Virology, 2019)

Integration of Food Animal Residue Avoidance Databank (FARAD) empirical methods for drug withdrawal interval determination with a mechanistic population-based interactive physiologically based pharmacokinetic (iPBPK) modeling platform: example for flunixin meglumine administration - Miao Li; Yi-Hsien Cheng; Jason T. Chittenden; Ronald E. Baynes; Lisa A. Tell; Jennifer L. Davis; Thomas W. Vickroy; Jim E. Riviere; Zhoumeng Lin (Archives of Toxicology, 2019)

Host genetic determinants of the gut microbiota of wild mice - Taichi A. Suzuki; Megan Phifer‐Rixey; Katya L. Mack; Michael J. Sheehan; Dana Lin; Ke Bi; Michael W. Nachman (Molecular Ecology, 2019)
Identifying a common set of genes that mediate host–microbial interactions across populations and species of mammals has broad relevance for human health and animal biology. However, the genetic basis of the gut microbial composition in natural populations remains largely unknown outside of humans. Here, we used wild house mouse populations as a model system to ask three major questions: (a) Does host genetic relatedness explain interindividual variation in gut microbial composition? (b) Do population differences in the microbiota persist in a common environment? (c) What are the host genes associated with microbial richness and the relative abundance of bacterial genera? We found that host genetic distance is a strong predictor of the gut microbial composition as characterized by 16S amplicon sequencing. Using a common garden approach, we then identified differences in microbial composition between populations that persisted in a shared laboratory environment. Finally, we used exome sequencing to associate host genetic variants with microbial diversity and relative abundance of microbial taxa in wild mice. We identified 20 genes that were associated with microbial diversity or abundance including a macrophage‐derived cytokine ( IL12a ) that contained three nonsynonymous mutations. Surprisingly, we found a significant overrepresentation of candidate genes that were previously associated with microbial measurements in humans. The homologous genes that overlapped between wild mice and humans included genes that have been associated with traits related to host immunity and obesity in humans. Gene–bacteria associations identified in both humans and wild mice suggest some commonality to the host genetic determinants of gut microbial composition across mammals.

Seasonal climatic effects and feedbacks of anthropogenic heat release due to global energy consumption with CAM5 - Bing Chen; C. Wu; X. Liu; L. Chen; Jian Wu; H. Yang; Tao Luo; Xue Wu; Yiquan Jiang; Lei Jiang; H. Y. Brown; Z. Lu; et al. (Climate Dynamics, 2019)

Lifetime recreational physical activity and the risk of prostate cancer - Elizabeth Sorial; Si Si; Lin Fritschi; Ellie Darcey; Justine E. Leavy; Jennifer Girschik; Gina L. Ambrosini; Terry Boyle (Cancer Causes & Control, 2019)

Limbic system structure volumes and associated neurocognitive functioning in former NFL players - Christian Lepage; Marc Muehlmann; Yorghos Tripodis; Jakob Hufschmidt; Julie Stamm; Katie Green; Pawel Wrobel; Vivian Schultz; Isabelle Weir; Michael L. Alosco; Christine M. Baugh; Nathan G. Fritts; et al. (Brain Imaging and Behavior, 2019)

Taxonomy of the order Mononegavirales: second update 2018 - Piet Maes; Gaya K. Amarasinghe; María A. Ayllón; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Kartik Chandran; et al. (Archives of Virology, 2019)

Structural Properties of the San Jacinto Fault Zone at Blackburn Saddle from Seismic Data of a Dense Linear Array - Pieter-Ewald Share; Amir A. Allam; Yehuda Ben-Zion; Fan-Chi Lin; Frank L. Vernon (Pure and Applied Geophysics, 2019)

Tropical Pacific Observing System - Neville Smith; William S. Kessler; Sophie Cravatte; Janet Sprintall; Susan Wijffels; Meghan F. Cronin; Adrienne Sutton; Yolande L. Serra; Boris Dewitte; Peter G. Strutton; Katherine Hill; Alex Sen Gupta; et al. (Frontiers in Marine Science, 2019)

Direct and indirect effects of climate on richness drive the latitudinal diversity gradient in forest trees - Chengjin Chu; James A. Lutz; Kamil Král; Tomáš Vrška; Xue Yin; Jonathan A. Myers; Iveren Abiem; Alfonso Alonso; Norm Bourg; David F.R.P. Burslem; Min Cao; Hazel Chapman; et al. (Ecology Letters, 2019)
Climate is widely recognised as an important determinant of the latitudinal diversity gradient. However, most existing studies make no distinction between direct and indirect effects of climate, which substantially hinders our understanding of how climate constrains biodiversity globally. Using data from 35 large forest plots, we test hypothesised relationships amongst climate, topography, forest structural attributes (stem abundance, tree size variation and stand basal area) and tree species richness to better understand drivers of latitudinal tree diversity patterns. Climate influences tree richness both directly, with more species in warm, moist, aseasonal climates and indirectly, with more species at higher stem abundance. These results imply direct limitation of species diversity by climatic stress and more rapid (co‐)evolution and narrower niche partitioning in warm climates. They also support the idea that increased numbers of individuals associated with high primary productivity are partitioned to support a greater number of species.

Does Regional Development Influence Sedimentary Blue Carbon Stocks? A Case Study From Three Australian Estuaries - Stephen Conrad; Dylan R. Brown; Paula Gomez Alvarez; Bronte Bates; Nizam Ibrahim; Alex Reid; Luciana Silva Monteiro; Daniela A. Silva; Lea T. Mamo; Jacob R. Bowtell; Huang An Lin; Nathaniel L. Tolentino; et al. (Frontiers in Marine Science, 2019)

The contribution of parent-to-offspring transmission of telomeres to the heritability of telomere length in humans - Dayana A. Delgado; Chenan Zhang; Kevin Gleason; Kathryn Demanelis; Lin S. Chen; Jianjun Gao; Shantanu Roy; Justin Shinkle; Mekala Sabarinathan; Maria Argos; Lin Tong; Alauddin Ahmed; et al. (Human Genetics, 2019)

Gross primary productivity of a large metropolitan region in midsummer using high spatial resolution satellite imagery - David L. Miller; Dar A. Roberts; Keith C. Clarke; Yang Lin; Olaf Menzer; Emily B. Peters; Joseph P. McFadden (Urban Ecosystems, 2018)

Single nucleotide polymorphisms in a regulatory site of VRN-A1 first intron are associated with differences in vernalization requirement in winter wheat - Nestor Kippes; Mohammed Guedira; Lijuan Lin; Maria A. Alvarez; Gina L. Brown-Guedira; Jorge Dubcovsky (Molecular Genetics and Genomics, 2018)

Aeromonas shuberti as a cause of multi‐organ necrosis in internal organs of Nile tilapia, Oreochromis niloticus - C Liu; O Q Chang; D F Zhang; K B Li; F Wang; M H Lin; C B Shi; L Jiang; Q Wang; S M Bergmann (Journal of Fish Diseases, 2018)
A disease with white spots in internal organs of Nile tilapia occurred in Zhanjiang, southern China. Multiple, white nodules, 0.8–2.2 mm in diameter, were scattered throughout the liver, spleen and kidney of diseased fish. Signs of nodules reproduced after artificial infection with the isolated strain. Isolated bacteria were Gram‐negative, facultative anaerobic, motile, short rod‐shaped, with a length of 1.2–2.2 μm. Morphological and biochemical tests, as well as phylogenetic analysis, all strongly indicated that the isolate from tilapia is identical to Aeromonas schubertii ( A. schubertii) which temporary named LF 1708 strain. Antibiotic sensitivity assays showed the LF 1708 is sensitive to 24 of 27 tested antibiotics. Pathogenicity test revealed that the isolate at the dose of 3.75 × 10 6 CFU /g killed 100% of experimental tilapia within 2 days and the dose of 1 × 10 7 CFU /g killed 100% of experimental zebrafish within 1 day. Histopathology of diseased tilapia infected with A. schubertii showed numerous necrotic lesions widely distributed in spleen, liver and kidney, and infiltration with a large number of bacteria. To our knowledge, this was the first report that associated A. schubertii with mortality in tilapia.

Evidence of differential adaptation to decreased temperature by anammox bacteria - Ximao Lin; Yayi Wang; Xiao Ma; Yuan Yan; Min Wu; Philip L. Bond; Jianhua Guo (Environmental Microbiology, 2018)
Summary Low temperature is recognized as one of the major barriers for the application of the anaerobic ammonium oxidation (anammox) process to treat mainstream wastewater. Studies are yet to reveal the underlying biological limitations and molecular mechanisms associated with the inhibition of low temperature on the anammox process. In this study, metaproteomics was used to examine proteome modulation patterns of the anammox community occurring at different temperatures. The anammox community remarkably altered their proteomes when the temperature decreased from 35 °C to 20 °C. This was especially for proteins involved in energy conversion, transcription and translation and inorganic ion transport. However, at 15 °C the anammox activities became distinctly inhibited, and there was evidence of energy limitations and severe stress in Candidatus Kuenenia and to a lesser degree in Candidatus Brocadia. Candidatus Jettenia exhibited more changes in its proteome at 15 °C. From the proteomes, at the lower temperatures there was evidence of stress caused by toxic nitrogen compounds or reactive oxygen species in the anammox bacteria. Hydroxylamine oxidoreductase (HAO)‐like proteins and an oxidative stress response protein (a catalase) were in high abundance to potentially ameliorate these inhibitory effects. This study offers metaproteomic insight into the anammox community‐based physiological response to decreasing temperatures.

Before and after: craving, mood, and background stress in the hours surrounding drug use and stressful events in patients with opioid-use disorder - Kenzie L. Preston; William J. Kowalczyk; Karran A. Phillips; Michelle L. Jobes; Massoud Vahabzadeh; Jia-Ling Lin; Mustapha Mezghanni; David H. Epstein (Psychopharmacology, 2018)

A Comparative Placebo-Controlled Clinical Trial of the Efficacy and Safety of Interferon β-1a Formulations for S.C. Administration in Patients with Remitting Multiple Sclerosis: First-Year Results - A. N. Boiko; L. P. Bosenko; V. V. Vasilovskii; L. I. Volkova; M. N. Zakharova; S. V. Kotov; E. V. Lekomtseva; T. I. Negrich; E. V. Parshina; O. P. Patrusheva; S. V. Prokopenko; D. V. Sazonov; et al. (Neuroscience and Behavioral Physiology, 2018)

Behavioural responses of an Australian colubrid snake (Dendrelaphis punctulatus) to a novel toxic prey item (the Cane Toad Rhinella marina) - John Llewelyn; Neil C. Choyce; Benjamin L. Phillips; Jonathan K. Webb; David J. Pearson; Lin Schwarzkopf; Richard Shine (Biological Invasions, 2018)

Speciation in the mountains and dispersal by rivers: Molecular phylogeny of Eulamprus water skinks and the biogeography of Eastern Australia - Mitzy Pepper; Joanna Sumner; Ian G. Brennan; Kate Hodges; Alan R. Lemmon; Emily Moriarty Lemmon; Garry Peterson; Daniel L. Rabosky; Lin Schwarzkopf; Ian A. W. Scott; Glenn Shea; J. Scott Keogh (Journal of Biogeography, 2018)
Aim To develop a robust phylogeny for the iconic Australian water skinks ( Eulamprus ) and to explore the influence of landscape evolution of eastern Australia on phylogeographic patterns. Location Eastern and south‐eastern Australia. Methods We used Sanger methods to sequence a mitochondrial DNA (mt DNA ) locus for 386 individuals across the five Eulamprus species to elucidate phylogeographic structure. We also sequenced a second mt DNA locus and four nuclear DNA ( nDNA ) loci for a subset of individuals to help inform our sampling strategy for next‐generation sequencing. Finally, we generated an anchored hybrid enrichment ( AHE ) approach to sequence 378 loci for 25 individuals representing the major lineages identified in our Sanger dataset. These data were used to resolve the phylogenetic relationships among the species using coalescent‐based species tree inference in * BEAST and ASTRAL . Results The relationships between Eulamprus species were resolved with a high level of confidence using our AHE dataset. In addition, our extensive mt DNA sampling revealed substantial phylogeographic structure in all species, with the exception of the geographically highly restricted E . leuraensis . Ratios of patristic distances (mt DNA / nDNA ) indicate on average a 30‐fold greater distance as estimated using the mt DNA locus ND 4. Main conclusions The major divergences between lineages strongly support previously identified biogeographic barriers in eastern Australia based on studies of other taxa. These breaks appear to correlate with regions where the Great Escarpment is absent or obscure, suggesting topographic lowlands and the accompanying dry woodlands are a major barrier to dispersal for water skinks. While some river corridors, such as the Hunter Valley, were likely historically dry enough to inhibit the movement of Eulamprus populations, our data indicate that others, such as the Murray and Darling Rivers, are able to facilitate extensive gene flow through the vast arid and semi‐arid lowlands of New South Wales and South Australia. Comparing the patristic distances between the mitochondrial and AHE datasets highlights the continued value in analysing both types of data.

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Modeling of the strong ground motion of 25th April 2015 Nepal earthquake using modified semi-empirical technique - Sohan Lal; A. Joshi; Sandeep; Monu Tomer; Parveen Kumar; Chun-Hsiang Kuo; Che-Min Lin; Kuo-Liang Wen; M. L. Sharma (Acta Geophysica, 2018)

Transcriptional responses of the marine green alga Micromonas pusilla and an infecting prasinovirus under different phosphate conditions - Charles Bachy; Christina J. Charlesworth; Amy M. Chan; Jan F. Finke; Chee‐Hong Wong; Chia‐Lin Wei; Sebastian Sudek; Maureen L. Coleman; Curtis A. Suttle; Alexandra Z. Worden (Environmental Microbiology, 2018)
Summary Prasinophytes are widespread marine algae for which responses to nutrient limitation and viral infection are not well understood. We studied the picoprasinophyte, Micromonas pusilla , grown under phosphate‐replete (0.65 ± 0.07 d −1 ) and 10‐fold lower (low)‐phosphate (0.11 ± 0.04 d −1 ) conditions, and infected by the phycodnavirus MpV‐SP1. Expression of 17% of Micromonas genes in uninfected cells differed by >1.5‐fold ( q

Effects of acute morphine withdrawal on ultrasonic vocalizations in adult rats: unchanged 50-kHz call rate and altered subtype profile - YiQi C. Lin; Leah L. Zhao; Paul B. S. Clarke (Psychopharmacology, 2018)

AZI23’UTR Is a New SLC6A3 Downregulator Associated with an Epistatic Protection Against Substance Use Disorders - Kefu Liu; Jinlong Yu; Juan Zhao; Yanhong Zhou; Nian Xiong; Jie Xu; Tao Wang; Richard L. Bell; Hong Qing; Zhicheng Lin (Molecular Neurobiology, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Bacillus Probiotic Supplementations Improve Laying Performance, Egg Quality, Hatching of Laying Hens, and Sperm Quality of Roosters - Maria S. Mazanko; Ivan F. Gorlov; Evgeniya V. Prazdnova; Maxim S. Makarenko; Alexander V. Usatov; Anzhelika B. Bren; Vladimir A. Chistyakov; Alexey V. Tutelyan; Zoya B. Komarova; Natalia I. Mosolova; Denis N. Pilipenko; Olga E. Krotova; et al. (Probiotics and Antimicrobial Proteins, 2018)

DNA Barcoding for Identification of Sugarcane Borers in China - J- D Wang; W- Z Wang; Z- L Lin; A Ali; H- Y Fu; M- T Huang; S- J Gao; R Wang (Neotropical Entomology, 2018)

Burly1 is a mouse QTL for lean body mass that maps to a 0.8-Mb region of chromosome 2 - Cailu Lin; Brad D. Fesi; Michael Marquis; Natalia P. Bosak; Anna Lysenko; Mohammed Amin Koshnevisan; Fujiko F. Duke; Maria L. Theodorides; Theodore M. Nelson; Amanda H. McDaniel; Mauricio Avigdor; Charles J. Arayata; et al. (Mammalian Genome, 2018)

Global environmental costs of China's thirst for milk - Zhaohai Bai; Michael R. F. Lee; Lin Ma; Stewart Ledgard; Oene Oenema; Gerard L. Velthof; Wenqi Ma; Mengchu Guo; Zhanqing Zhao; Sha Wei; Shengli Li; Xia Liu; et al. (Global Change Biology, 2018)
China has an ever‐increasing thirst for milk, with a predicted 3.2‐fold increase in demand by 2050 compared to the production level in 2010. What are the environmental implications of meeting this demand, and what is the preferred pathway? We addressed these questions by using a nexus approach, to examine the interdependencies of increasing milk consumption in China by 2050 and its global impacts, under different scenarios of domestic milk production and importation. Meeting China's milk demand in a business as usual scenario will increase global dairy‐related (China and the leading milk exporting regions) greenhouse gas ( GHG ) emissions by 35% (from 565 to 764 Tg CO 2eq ) and land use for dairy feed production by 32% (from 84 to 111 million ha) compared to 2010, while reactive nitrogen losses from the dairy sector will increase by 48% (from 3.6 to 5.4 Tg nitrogen). Producing all additional milk in China with current technology will greatly increase animal feed import; from 1.9 to 8.5 Tg for concentrates and from 1.0 to 6.2 Tg for forage (alfalfa). In addition, it will increase domestic dairy related GHG emissions by 2.2 times compared to 2010 levels. Importing the extra milk will transfer the environmental burden from China to milk exporting countries; current dairy exporting countries may be unable to produce all additional milk due to physical limitations or environmental preferences/legislation. For example, the farmland area for cattle‐feed production in New Zealand would have to increase by more than 57% (1.3 million ha) and that in Europe by more than 39% (15 million ha), while GHG emissions and nitrogen losses would increase roughly proportionally with the increase of farmland in both regions. We propose that a more sustainable dairy future will rely on high milk demanding regions (such as China) improving their domestic milk and feed production efficiencies up to the level of leading milk producing countries. This will decrease the global dairy related GHG emissions and land use by 12% (90 Tg CO 2eq reduction) and 30% (34 million ha land reduction) compared to the business as usual scenario, respectively. However, this still represents an increase in total GHG emissions of 19% whereas land use will decrease by 8% when compared with 2010 levels, respectively.

Formation and characteristics of the Xiaoba landslide in Fuquan, Guizhou, China - F. Lin; L. Z. Wu; R. Q. Huang; H. Zhang (Landslides, 2018)

Comparing strategies for selection of low-density SNPs for imputation-mediated genomic prediction in U. S. Holsteins - Jun He; Jiaqi Xu; Xiao-Lin Wu; Stewart Bauck; Jungjae Lee; Gota Morota; Stephen D. Kachman; Matthew L. Spangler (Genetica, 2018)

Treatment outcome of non-carbapenemase-producing carbapenem-resistant Klebsiella pneumoniae infections: a multicenter study in Taiwan - Chin-Fang Su; Chien Chuang; Yi-Tsung Lin; Yu-Jiun Chan; Jung-Chung Lin; Po-Liang Lu; Ching-Tai Huang; Jann-Tay Wang; Yin-Ching Chuang; L. Kristopher Siu; Chang-Phone Fung (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Rice ecosystem services in South-east Asia - Josef Settele; Kong Luen Heong; Ingolf Kühn; Stefan Klotz; Joachim H. Spangenberg; Gertrudo Arida; Alexis Beaurepaire; Silke Beck; Erwin Bergmeier; Benjamin Burkhard; Roland Brandl; Jesus Victor Bustamante; et al. (Paddy and Water Environment, 2018)

Late sodium current associated cardiac electrophysiological and mechanical dysfunction - Shandong Yu; Gang Li; Christopher L.-H. Huang; Ming Lei; Lin Wu (Pflügers Archiv - European Journal of Physiology, 2018)

Temporal Profile and Severity Correlation of a Panel of Rat Spinal Cord Injury Protein Biomarkers - Zhihui Yang; Helen M. Bramlett; Ahmed Moghieb; Dongnan Yu; Ping Wang; Fan Lin; Carl Bauer; Tyler M. Selig; Emily Jaalouk; Amanda S. Weissman; Disa S. Rathore; Pammela Romo; et al. (Molecular Neurobiology, 2018)

Levels of PCDD/Fs, PBDEs, and PBDD/Fs in Breast Milk from Southern Taiwan - Men-Wen Chen; Bryan Angelo A. Castillo; Din-Yan Lin; How-Ran Chao; Lemmuel L. Tayo; Yan-You Gou; Fu-An Chen; Kuo-Lin Huang (Bulletin of Environmental Contamination and Toxicology, 2018)

Matrix Metalloproteinases MMP-1 and MMP-9 and Their Inhibitor TIMP-1 as Markers of Dilated Cardiomyopathy in Patients of Different Age - I. B. Antonov; K. L. Kozlov; E. M. Pal’tseva; O. V. Polyakova; N. S. Lin’kova (Bulletin of Experimental Biology and Medicine, 2018)

Screening for gene–environment (G×E) interaction using omics data from exposed individuals: an application to gene-arsenic interaction - Maria Argos; Lin Tong; Shantanu Roy; Mekala Sabarinathan; Alauddin Ahmed; Md. Tariqul Islam; Tariqul Islam; Muhammad Rakibuz-Zaman; Golam Sarwar; Hasan Shahriar; Mahfuzar Rahman; Md. Yunus; et al. (Mammalian Genome, 2018)

Simulated differences in 21st century aridity due to different scenarios of greenhouse gases and aerosols - L. Lin; A. Gettelman; Q. Fu; Y. Xu (Climatic Change, 2018)

Aerosol microphysical and radiative effects on continental cloud ensembles - Yuan Wang; Jonathan M. Vogel; Yun Lin; Bowen Pan; Jiaxi Hu; Yangang Liu; Xiquan Dong; Jonathan H. Jiang; Yuk L. Yung; Renyi Zhang (Advances in Atmospheric Sciences, 2018)

Microbial dolomite in the sabkha environment of the middle Cambrian in the Tarim Basin, NW China - X. L. You; S. Sun; C. S. Lin; J. Q. Zhu (Australian Journal of Earth Sciences, 2018)

Characterizing the neighborhood obesogenic environment in the Multiethnic Cohort: a multi-level infrastructure for cancer health disparities research - Shannon M. Conroy; Salma Shariff-Marco; Juan Yang; Andrew Hertz; Myles Cockburn; Yurii B. Shvetsov; Christina A. Clarke; Cheryl L. Abright; Christopher A. Haiman; Loïc Le Marchand; Laurence N. Kolonel; Kristine R. Monroe; et al. (Cancer Causes & Control, 2018)

Molecular screening of multidrug-resistance tuberculosis by a designated public health laboratory in Taiwan - H.-C. Lin; C.-L. Perng; Y.-W. Lai; F.-G. Lin; C.-J. Chiang; H.-A. Lin; R. Jou; T.-S. Chiueh (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Characterization of Eptesipoxvirus, a novel poxvirus from a microchiropteran bat - Shin-Lin Tu; Yoshinori Nakazawa; Jinxin Gao; Kimberly Wilkins; Nadia Gallardo-Romero; Yu Li; Ginny L. Emerson; Darin S. Carroll; Chris Upton (Virus Genes, 2017)

Context and craving during stressful events in the daily lives of drug-dependent patients - Kenzie L. Preston; William J. Kowalczyk; Karran A. Phillips; Michelle L. Jobes; Massoud Vahabzadeh; Jia-Ling Lin; Mustapha Mezghanni; David H. Epstein (Psychopharmacology, 2017)

Identification of a seed coat-specific promoter fragment from the Arabidopsis MUCILAGE-MODIFIED4 gene - Gillian H. Dean; Zhaoqing Jin; Lin Shi; Elahe Esfandiari; Robert McGee; Kylie Nabata; Tiffany Lee; Ljerka Kunst; Tamara L. Western; George W. Haughn (Plant Molecular Biology, 2017)

Rethinking communication in risk interpretation and action - Shabana Khan; Jyoti L. Mishra; Kuna-hui Elaine Lin; Emma E. H. Doyle (Natural Hazards, 2017)

Development of a two-stage washing and biodegradation system to remediate octachlorinated dibenzo-p-dioxin-contaminated soils - J. L. Lin; C. D. Dong; C. W. Chen; S. H. Chen; T. E. Hsieh; C. M. Kao (International Journal of Environmental Science and Technology, 2017)

Racial differences in the effects of comorbidity on breast cancer-specific survival - Melissa L. Santorelli; Kim M. Hirshfield; Michael B. Steinberg; Yong Lin; George G. Rhoads; Elisa V. Bandera; Kitaw Demissie (Cancer Causes & Control, 2017)

Expression of Signal Molecules in Culture of Human Endothelial Cells in Atherosclerosis and Restenosis - K. L. Kozlov; I. I. Bolotov; N. S. Lin’kova; A. O. Drobintseva (Bulletin of Experimental Biology and Medicine, 2017)

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Experimental Investigation of the Anisotropic Mechanical Properties of a Columnar Jointed Rock Mass: Observations from Laboratory-Based Physical Modelling - H. Ji; J. C. Zhang; W. Y. Xu; R. B. Wang; H. L. Wang; L. Yan; Z. N. Lin (Rock Mechanics and Rock Engineering, 2017)

Cardiotoxicity Associated with Nicotinamide Phosphoribosyltransferase Inhibitors in Rodents and in Rat and Human-Derived Cells Lines - D. L. Misner; M. A. Kauss; J. Singh; H. Uppal; A. Bruening-Wright; B. M. Liederer; T. Lin; B. McCray; N. La; T. Nguyen; D. Sampath; P. S. Dragovich; et al. (Cardiovascular Toxicology, 2017)

Development of In situ hybridization and real‐time PCR assays for the detection of Hepatospora eriocheir , a microsporidian pathogen in the Chinese mitten crab Eriocheir sinensis - Z F Ding; J Q Chen; J Lin; X S Zhu; G H Xu; R L Wang; Q G Meng; W Wang (Journal of Fish Diseases, 2017)
A microsporidian parasite, Hepatospora eriocheir , is an emerging pathogen for the Chinese mitten crab Eriocheir sinensis . Currently, there is scant information about the way it transmits infection in the crustacean of commercial importance, including its pathogenesis, propagation and infection route in vivo . In this study, chromogenic in situ hybridization ( ISH ) and quantitative real‐time PCR ( qPCR ) assays were developed to address this pressing need, and we provided an advance in the detection methods available. Pathogens can be seen in situ with associated lesions using ISH . Positive hybridization signals were noted inside the epithelial cells of the hepatopancreas, and putative free parasite spores were observed within the tubule lumen, which were associated with lesions detected by electron microscopy and haematoxylin and eosin (H&E) analysis. qPCR allows the determination of parasite loads in infected tissues, which is important for understanding disease progression and transmission. The hepatopancreas displayed the biggest statistical copy numbers among different tissues of infected crabs, confirming a tissue‐specific pathogen infection characteristic. The qPCR assay also proved to be suitable for the diagnosis of asymptomatic carrier crabs. Combination of the two methods could facilitate the study of H. eriocheir infection mechanism in E. sinensis , enhance the early diagnosis of the pathogen and improve the management of microsporidian diseases in commercial crustaceans.

Skin Examination Practices Among Melanoma Survivors and Their Children - Beth A. Glenn; Katherine L. Chen; L. Cindy Chang; Tiffany Lin; Roshan Bastani (Journal of Cancer Education, 2017)

Erratum to: Atmospheric Nitrogen Emission, Deposition, and Air Quality Impacts in China: an Overview - Xuejun Liu; Wen Xu; Lei Duan; Enzai Du; Yuepeng Pan; Xiankai Lu; Lin Zhang; Zhiyong Wu; Xuemei Wang; Ying Zhang; Jianlin Shen; Ling Song; et al. (Current Pollution Reports, 2017)

Atmospheric Nitrogen Emission, Deposition, and Air Quality Impacts in China: an Overview - Xuejun Liu; Wen Xu; Lei Duan; Enzai Du; Yuepeng Pan; Xiankai Lu; Lin Zhang; Zhiyong Wu; Xuemei Wang; Ying Zhang; Jianlin Shen; Ling Song; et al. (Current Pollution Reports, 2017)

Tissue and cell-type co-expression networks of transcription factors and wood component genes in Populus trichocarpa - Rui Shi; Jack P. Wang; Ying-Chung Lin; Quanzi Li; Ying-Hsuan Sun; Hao Chen; Ronald R. Sederoff; Vincent L. Chiang (Planta, 2017)

Endometriosis and risk of ovarian and endometrial cancers in a large prospective cohort of U.S. nurses - Elizabeth M. Poole; Wayne T. Lin; Marina Kvaskoff; Immaculata De Vivo; Kathryn L. Terry; Stacey A. Missmer (Cancer Causes & Control, 2017)

Identification of diverse bacterial communities for potential bio-aids capable of troubleshooting for wastewater biological treatment processes - H-W Kuo; C-Y Huang; C-N Chang; P-L Lee; Y-W Chen; C-F Huang; H-H Chang; Y-H Tang; S-Z Zeng; G-Y Li; C-R Lin; L-Z Chen (International Journal of Environmental Science and Technology, 2017)

Increased risk of chronic osteomyelitis after hip replacement: a retrospective population-based cohort study in an Asian population - D.-Z. Hung; N. Tien; C.-L. Lin; Y.-R. Lee; C. C. N. Wang; J.-J. Chen; Y.-P. Lim (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Experimental and statistical methods to evaluate antibacterial activity of a quaternary pyridinium salt on planktonic, biofilm-forming, and biofilm states - Daneli López Pérez; Paula J. Baker; Adam L. Pintar; Jirun Sun; Nancy J. Lin; Sheng Lin-Gibson (Biofouling, 2017)

Glycerol enhances fungal germination at the water‐activity limit for life - Andrew Stevenson; Philip G. Hamill; Ángel Medina; Gerhard Kminek; John D. Rummel; Jan Dijksterhuis; David J. Timson; Naresh Magan; Su‐Lin L. Leong; John E. Hallsworth (Environmental Microbiology, 2017)
Summary For the most‐extreme fungal xerophiles, metabolic activity and cell division typically halts between 0.700 and 0.640 water activity (approximately 70.0–64.0% relative humidity). Here, we investigate whether glycerol can enhance xerophile germination under acute water‐activity regimes, using an experimental system which represents the biophysical limit of Earth's biosphere. Spores from a variety of species, including Aspergillus penicillioides , Eurotium halophilicum , Xerochrysium xerophilum (formerly Chrysosporium xerophilum ) and Xeromyces bisporus , were produced by cultures growing on media supplemented with glycerol (and contained up to 189 mg glycerol g dry spores −1 ). The ability of these spores to germinate, and the kinetics of germination, were then determined on a range of media designed to recreate stresses experienced in microbial habitats or anthropogenic systems (with water‐activities from 0.765 to 0.575). For A. penicillioides , Eurotium amstelodami , E. halophilicum , X. xerophilum and X. bisporus , germination occurred at lower water‐activities than previously recorded (0.640, 0.685, 0.651, 0.664 and 0.637 respectively). In addition, the kinetics of germination at low water‐activities were substantially faster than those reported previously. Extrapolations indicated theoretical water‐activity minima below these values; as low as 0.570 for A. penicillioides and X. bisporus . Glycerol is present at high concentrations (up to molar levels) in many types of microbial habitat. We discuss the likely role of glycerol in expanding the water‐activity limit for microbial cell function in relation to temporal constraints and location of the microbial cell or habitat. The findings reported here have also critical implications for understanding the extremes of Earth's biosphere; for understanding the potency of disease‐causing microorganisms; and in biotechnologies that operate at the limits of microbial function.

Variability of hydrological extreme events in East Asia and their dynamical control: a comparison between observations and two high-resolution global climate models - N. Freychet; A. Duchez; C.-H. Wu; C.-A. Chen; H.-H. Hsu; J. Hirschi; A. Forryan; B. Sinha; A. L. New; T. Graham; M. B. Andrews; C.-Y. Tu; et al. (Climate Dynamics, 2017)

Recent declines in cancer incidence: related to the Great Recession? - Scarlett Lin Gomez; Alison J. Canchola; David O. Nelson; Theresa H. M. Keegan; Christina A. Clarke; Iona Cheng; Salma Shariff-Marco; Mindy DeRouen; Ralph Catalano; William A. Satariano; Kathleen Davidson-Allen; Sally L. Glaser (Cancer Causes & Control, 2017)

Transcriptomic imprints of adaptation to fresh water: parallel evolution of osmoregulatory gene expression in the Alewife - Jonathan P. Velotta; Jill L. Wegrzyn; Samuel Ginzburg; Lin Kang; Sergiusz Czesny; Rachel J. O'Neill; Stephen D. McCormick; Pawel Michalak; Eric T. Schultz (Molecular Ecology, 2017)
Comparative approaches in physiological genomics offer an opportunity to understand the functional importance of genes involved in niche exploitation. We used populations of Alewife ( Alosa pseudoharengus ) to explore the transcriptional mechanisms that underlie adaptation to fresh water. Ancestrally anadromous Alewives have recently formed multiple, independently derived, landlocked populations, which exhibit reduced tolerance of saltwater and enhanced tolerance of fresh water. Using RNA ‐seq, we compared transcriptional responses of an anadromous Alewife population to two landlocked populations after acclimation to fresh (0 ppt) and saltwater (35 ppt). Our results suggest that the gill transcriptome has evolved in primarily discordant ways between independent landlocked populations and their anadromous ancestor. By contrast, evolved shifts in the transcription of a small suite of well‐characterized osmoregulatory genes exhibited a strong degree of parallelism. In particular, transcription of genes that regulate gill ion exchange has diverged in accordance with functional predictions: freshwater ion‐uptake genes (most notably, the ‘freshwater paralog’ of Na + /K + ‐ ATP ase α‐subunit) were more highly expressed in landlocked forms, whereas genes that regulate saltwater ion secretion (e.g. the ‘saltwater paralog’ of NKA α) exhibited a blunted response to saltwater. Parallel divergence of ion transport gene expression is associated with shifts in salinity tolerance limits among landlocked forms, suggesting that changes to the gill's transcriptional response to salinity facilitate freshwater adaptation.

Structuraland antigenic analysis of a new Rhoptry Pseudokinase Gene (ROP54) in Toxoplasma gondii - Jian Zhou; Gang Lu; Lin Wang; Aihua H. Zhou; Yali L. Han; Jingjing J. Guo; Pengxia X. Song; Huaiyu Y. Zhou; Hua Cong; Ming Hou; Shenyi Y. He (Acta Parasitologica, 2017)
is defined as an obligate intracellular apicomplexan parasite and influences approximatelyone-third of the human all over the world. ROP54 protein is expressed in the rhoptry of

A decision analysis approach to climate adaptation: a structured method to consider multiple options - L. Richard Little; Brenda B. Lin (Mitigation and Adaptation Strategies for Global Change, 2017)

The Diagnosis and Natural History of Multiple System Atrophy, Cerebellar Type - David J. Lin; Katherine L. Hermann; Jeremy D. Schmahmann (The Cerebellum, 2016)

A new region-based preparatory factor for landslide susceptibility models: the total flux - C. C. Liu; W. Luo; M. C. Chen; Y. T. Lin; H. L. Wen (Landslides, 2016)

Limited diversity associated with duplicated class II MHC-DRB genes in the red squirrel population in the United Kingdom compared with continental Europe - Keith T. Ballingall; Angeline McIntyre; Zhenzhen Lin; Naomi Timmerman; Erik Matthysen; Peter W.W. Lurz; Lynsey Melville; Amy Wallace; Anna L. Meredith; Claudia Romeo; Lucas A. Wauters; Anthony W. Sainsbury; et al. (Conservation Genetics, 2016)

Genetic Diversity of Populations of Saccharum spontaneum with Different Ploidy Levels Using SSR Molecular Markers - X. L. Liu; X. J. Li; C. H. Xu; X. Q. Lin; Z. H. Deng (Sugar Tech, 2016)

Extracellular Cl− regulates human SO4 2−/anion exchanger SLC26A1 by altering pH sensitivity of anion transport - Meng Wu; John F. Heneghan; David H. Vandorpe; Laura I. Escobar; Bai-Lin Wu; Seth L. Alper (Pflügers Archiv - European Journal of Physiology, 2016)

Parasitism Performance of Tetrastichus brontispae Ferriere over the Coconut Hispine Beetle, Brontispa longissima (Gestro) - K Liu; B L Fu; J R Lin; Y G Fu; Z Q Peng; Q A Jin; L D Tang (Neotropical Entomology, 2016)

Taxonomy of the order Mononegavirales: update 2016 - Claudio L. Afonso; Gaya K. Amarasinghe; Krisztián Bányai; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Nicolás Bejerman; Kim R. Blasdell; François-Xavier Briand; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; et al. (Archives of Virology, 2016)

Multiplexed Fluid Flow Device to Study Cellular Response to Tunable Shear Stress Gradients - Maggie A. Ostrowski; Eva Y. Huang; Vinay N. Surya; Charlotte Poplawski; Joseph M. Barakat; Gigi L. Lin; Gerald G. Fuller; Alexander R. Dunn (Annals of Biomedical Engineering, 2016)

Functional Genomic Analysis of the Impact of Camelina (Camelina sativa) Meal on Atlantic Salmon (Salmo salar) Distal Intestine Gene Expression and Physiology - Tyler D. Brown; Tiago S. Hori; Xi Xue; Chang Lin Ye; Derek M. Anderson; Matthew L. Rise (Marine Biotechnology, 2016)

Early detection of Mycobacterium tuberculosis complex in BACTEC MGIT cultures using nucleic acid amplification - S. Y. Lin; S. C. Hwang; Y. C. Yang; C. F. Wang; Y. H. Chen; T. C. Chen; P. L. Lu (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Estrogenic effects in the influents and effluents of the drinking water treatment plants - Yan-You Gou; Susana Lin; Danielle E. Que; Lemmuel L. Tayo; Ding-Yan Lin; Kuan-Chung Chen; Fu-An Chen; Pen-Chi Chiang; Gen-Shuh Wang; Yi-Chyuan Hsu; Kuo Pin Chuang; Chun-Yu Chuang; et al. (Environmental Science and Pollution Research, 2016)

Interpreting sedimentation dynamics at Longxi catchment in the Three Gorges Area, China, using Cs-137 activity, particle size and rainfall erosivity - Jin-zhang Gao; Yi Long; Xin-bao Zhang; Adrian L. Collins; Xiu-bin He; Yun-qi Zhang; Zhong-lin Shi (Journal of Mountain Science, 2016)

Strong inhibition of betanodavirus replication by ribavirin targeting RNA ‐dependent RNA polymerase - Y‐C Huang; T‐S Lin; C Peng; N‐L Chan; Y‐S Han (Journal of Fish Diseases, 2016)

A cell wall-bound anionic peroxidase, PtrPO21, is involved in lignin polymerization in Populus trichocarpa - Chien-Yuan Lin; Quanzi Li; Sermsawat Tunlaya-Anukit; Rui Shi; Ying-Hsuan Sun; Jack P. Wang; Jie Liu; Philip Loziuk; Charles W. Edmunds; Zachary D. Miller; Ilona Peszlen; David C. Muddiman; et al. (Tree Genetics & Genomes, 2016)

Changes in phosphorus use and losses in the food chain of China during 1950–2010 and forecasts for 2030 - Zhaohai Bai; Lin Ma; Wenqi Ma; Wei Qin; Gerard L. Velthof; Oene Oenema; Fusuo Zhang (Nutrient Cycling in Agroecosystems, 2016)

Bismuth(III) deferiprone effectively inhibits growth of Desulfovibrio desulfuricans ATCC 27774 - Larry L. Barton; Daniel A. Lyle; Nathaniel L. Ritz; Alex S. Granat; Ali N. Khurshid; Nada Kherbik; Robert Hider; Henry C. Lin (BioMetals, 2016)

Validation of self-reported comorbidity status of breast cancer patients with medical records: the California Breast Cancer Survivorship Consortium (CBCSC) - Cheryl Vigen; Marilyn L. Kwan; Esther M. John; Scarlett Lin Gomez; Theresa H. M. Keegan; Yani Lu; Salma Shariff-Marco; Kristine R. Monroe; Allison W. Kurian; Iona Cheng; Bette J. Caan; Valerie S. Lee; et al. (Cancer Causes & Control, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Taxonomic Study of the Genus Apalacris Walker (Orthoptera: Catantopidae) - Z M Zheng; L L Lin; Y Niu (Neotropical Entomology, 2016)

Epidemiology and characteristics of the dengue outbreak in Guangdong, Southern China, in 2014 - L. Huang; X. Luo; J. Shao; H. Yan; Y. Qiu; P. Ke; W. Zheng; B. Xu; W. Li; D. Sun; D. Cao; C. Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Drought tolerance as a driver of tropical forest assembly: resolving spatial signatures for multiple processes - M. K. Bartlett; Y. Zhang; J. Yang; N. Kreidler; S.‐W. Sun; L. Lin; Y.‐H. Hu; K.‐F. Cao; L. Sack (Ecology, 2016)
Spatial patterns in trait variation reflect underlying community assembly processes, allowing us to test hypotheses about their trait and environmental drivers by identifying the strongest correlates of characteristic spatial patterns. For 43 evergreen tree species (>1 cm dbh) in a 20‐ha seasonal tropical rainforest plot in Xishuangbanna, China, we compared the ability of drought‐tolerance traits, other physiological traits, and commonly measured functional traits to predict the spatial patterns expected from the assembly processes of habitat associations, niche‐overlap‐based competition, and hierarchical competition. We distinguished the neighborhood‐scale (0–20 m) patterns expected from competition from larger‐scale habitat associations with a wavelet method. Species’ drought tolerance and habitat variables related to soil water supply were strong drivers of habitat associations, and drought tolerance showed a significant spatial signal for influencing competition. Overall, the traits most strongly associated with habitat, as quantified using multivariate models, were leaf density, leaf turgor loss point (π tlp ; also known as the leaf wilting point), and stem hydraulic conductivity ( r 2 range for the best fit models = 0.27–0.36). At neighborhood scales, species spatial associations were positively correlated with similarity in π tlp , consistent with predictions for hierarchical competition. Although the correlation between π tlp and interspecific spatial associations was weak ( r 2

Histological analysis of somatic embryogenesis in pineapple: AcSERK1 and its expression validation under stress conditions - J. Ma; Y. H. He; Z. Y. Hu; S. Kanakala; W. T. Xu; J. X. Xia; C. H. Guo; S. Q. Lin; C. J. Chen; C. H. Wu; J. L. Zhang (Journal of Plant Biochemistry and Biotechnology, 2016)

Three N-Glycosylation Sites of Human Acetylcholinesterase Shares Similar Glycan Composition - Miranda L. Xu; Wilson K. W. Luk; Kei M. Lau; Cathy W. C. Bi; Anthony W. M. Cheng; Amy G. W. Gong; Huangquan Lin; Karl W. K. Tsim (Journal of Molecular Neuroscience, 2015)

Development and evaluation of a loop‐mediated isothermal amplification assay for the detection of channel catfish virus - G X Liu; L Lin; M Wang; X Q Liu (Journal of Fish Diseases, 2015)

Influence of Regional Difference in Bone Mineral Density on Hip Fracture Site in Elderly Females by Finite Element Analysis - Z. L. Lin; P. F. Li; Z. H. Pang; X. H. Zheng; F. Huang; H. H. Xu; Q. L. Li (Cell Biochemistry and Biophysics, 2015)

Roles of the Fibrous Superficial Zone in the Mechanical Behavior of TMJ Condylar Cartilage - Leonardo Ruggiero; Brandon K. Zimmerman; Miri Park; Lin Han; Liyun Wang; David L. Burris; X. Lucas Lu (Annals of Biomedical Engineering, 2015)

Some of the people, some of the time: field evidence for associations and dissociations between stress and drug use - Melody Furnari; David H. Epstein; Karran A. Phillips; Michelle L. Jobes; William J. Kowalczyk; Massoud Vahabzadeh; Jia-Ling Lin; Kenzie L. Preston (Psychopharmacology, 2015)

Two New Species of the Genus Criotettix Bolivar (Orthoptera: Tetrigidae), with a Key to the Species of the Genus from China - W A Deng; Z M Zheng; S Z Wei; M P Lin; L L Lin (Neotropical Entomology, 2015)

Rapid generation and analysis of expressed sequence tags to uncovering inflorescence secondary metabolism of Bougainvillea spectabilis ‘Speciosas’ by pyrosequencing - S. X. Xu; Q. Y. Huang; C. S. Lin; F. C. Lin; L. X. Lin; Q. Y. Shen (Euphytica, 2015)

The influence of shelf-sea fronts on winter monsoon over East China Sea - L.-Y. Oey; M.-C. Chang; S.-M. Huang; Y.-C. Lin; M.-A. Lee (Climate Dynamics, 2015)

Simulation of the records of the 27 March 2013 Nantou Taiwan earthquake using modified semi-empirical approach - A. Joshi; Chun-Hsiang Kuo; Piu Dhibar; Sandeep; M. L. Sharma; Kuo-Liang Wen; Che-Min Lin (Natural Hazards, 2015)

Crustal thickening and extension induced by the Great Sumatra–Andaman earthquake of 26 December 2004: revealed by the seismic moment tensor element Mrr - J.-Y. Lin; C.-L. Lo; W.-N. Wu; J.-C. Sibuet; S.-K. Hsu; Y.-Y. Wen (Marine Geophysical Research, 2015)

Ambient air concentrations of PCDD/Fs, coplanar PCBs, PBDD/Fs, and PBDEs and their impacts on vegetation and soil - Y.-C. Kuo; Y.-C. Chen; M.-Y. Lin; L.-H. Young; H.-T. Hsu; S.-H. Liou; T.-N. Wu; L.-C. Wang; P.-J. Tsai (International Journal of Environmental Science and Technology, 2015)

The suppression of brain activation in post-deployment military personnel with posttraumatic stress symptoms - Randall S. Scheibel; Nicholas J. Pastorek; Maya Troyanskaya; Jan E. Kennedy; Joel L. Steinberg; Mary R. Newsome; Xiaodi Lin; Harvey S. Levin (Brain Imaging and Behavior, 2015)

Enemies lost: parallel evolution in structural defense and tolerance to herbivory of invasive Jacobaea vulgaris - Tiantian Lin; Leonie Doorduin; Andries Temme; Thijs L. Pons; Gerda E. M. Lamers; Niels P. R. Anten; Klaas Vrieling (Biological Invasions, 2015)

Overexpression of AT14A confers tolerance to drought stress-induced oxidative damage in suspension cultured cells of Arabidopsis thaliana - Lin Wang; Jie He; Haidong Ding; Hui Liu; Bing Lü; Jiansheng Liang; L. Wang; J. He; H. D. Ding; H. Liu; B. Lü; J. S. Liang (Protoplasma, 2015)

Statins can increase the risk of herpes zoster infection in Asia - H.-H. Chen; C.-L. Lin; C.-J. Yeh; S.-Y. Yeh; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Parallel evolution in an invasive plant: effect of herbivores on competitive ability and regrowth of Jacobaea vulgaris - Tiantian Lin; Peter G. L. Klinkhamer; Klaas Vrieling (Ecology Letters, 2015)
A shift in the composition of the herbivore guild in the invasive range is expected to select for plants with a higher competitive ability, a lower regrowth capacity and a lower investment in defence. We show here that parallel evolution took place in three geographically distinct invasive regions that differed significantly in climatic conditions. This makes it most likely that indeed the shifts in herbivore guilds were causal to the evolutionary changes. We studied competitive ability and regrowth of invasive and native Jacobaea vulgaris using an intraspecific competition set‐up with and without herbivory. Without herbivores invasive genotypes have a higher competitive ability than native genotypes. The invasive genotypes were less preferred by the generalist Mamestra brassicae but more preferred by the specialist Tyria jacobaeae , consequently their competitive ability was significantly increased by the first and reduced by the latter. Invasive genotypes showed a lower regrowth ability in both herbivore treatments.

Stress hormone metabolites predict overwinter survival in yellow-bellied marmots - Tina W. Wey; Lawrence Lin; Marilyn L. Patton; Daniel T. Blumstein (acta ethologica, 2015)

Infections of nervous necrosis virus in wild and cage‐reared marine fish from S outh C hina S ea with unexpected wide host ranges - X D Liu; J N Huang; S P Weng; X Q Hu; W J Chen; Z D Qin; X X Dong; X L Liu; Y Zhou; M Asim; W M Wang; J G He; et al. (Journal of Fish Diseases, 2015)
The concerns about the impact of the nervous necrosis virus ( NNV ) infections in wild fish have been raised. This paper presents the results of quarterly surveys of NNV in wild and cage‐reared marine fish from South China Sea. Samples of 892 wild fish belonging to 69 species and 381 cage‐reared fish belonging to 11 species were collected and were detected by seminested PCR and nested PCR . In the case of seminested PCR , the positive signal was detected in 3.0% and 3.1% samples of wild and cage‐reared fish, respectively. However, by nested RT ‐ PCR , the positive signal was observed in 42.3% and 63.0% samples of wild and cage‐reared fish, respectively. If the fish species were considered, the positive signal was detected in 21.7% and 72.7% species of wild and cage‐reared fish by seminested PCR assay, respectively. However, by nested RT ‐ PCR , the positive signal was observed in 65.2% and 100% species of wild and cage‐reared fish, respectively. The nucleotide sequences of the nested PCR products were determined. Phylogenetic tree showed that all the obtained viral isolates belonged to the red‐spotted grouper nervous necrosis virus ( RGNNV ) genotype. Thirty‐five species of the marine fish were the new hosts of NNV .

CD8 T cells and Mycobacterium tuberculosis infection - Philana Ling Lin; JoAnne L. Flynn (Seminars in Immunopathology, 2015)

Balanitis is a risk factor for herpes zoster - C.-Y. Hsu; C.-L. Lin; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Mass mortality associated with a viral‐induced anaemia in cage‐reared large yellow croaker, Larimichthys crocea (Richardson) - W J Xu; Z D Qin; H Shi; N Jiang; Y Zhou; X L Liu; J J Xie; G S Wang; W M Wang; M Asim; L B Zeng; L Lin (Journal of Fish Diseases, 2015)

Arsenic Accumulation in Panax notoginseng Monoculture and Intercropping with Pteris vittata - L. Y. Lin; X. L. Yan; X. Y. Liao; Y. X. Zhang; X. Ma (Water, Air, & Soil Pollution, 2015)

Characterization of a Novel Two-Component System in Burkholderia cenocepacia - Callie R. Merry; Michael Perkins; Lin Mu; Bridget K. Peterson; Rebecca W. Knackstedt; Christine L. Weingart (Current Microbiology, 2015)

Persistent organic pollutants in tropical coastal and offshore environment: part A—atmospheric polycyclic aromatic hydrocarbons - I.-C. Lai; C.-L. Lee; F.-C. Ko; J.-C. Lin; H.-C. Huang (International Journal of Environmental Science and Technology, 2015)

Anti-tuberculosis treatments and risk of hepatocellular carcinoma in tuberculosis patients with liver cirrhosis: a population-based case–control study - Y.-P. Lim; C.-L. Lin; D.-Z. Hung; Y.-N. Lin; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Clustering of Clinical and Environmental Escherichia coli O104 Isolates Using the DiversiLab™ Repetitive Sequence-Based PCR System - N. M. Herbold; L. M. Clotilde; K. M. Anderson; J. Kase; G. L. Hartman; S. Himathongkham; A. Lin; C. R. Lauzon (Current Microbiology, 2015)

ICE1 demethylation drives the range expansion of a plant invader through cold tolerance divergence - H. J. Xie; H. Li; D. Liu; W. M. Dai; J. Y. He; S. Lin; H. Duan; L. L. Liu; S. G. Chen; X. L. Song; B. E. Valverde; S. Qiang (Molecular Ecology, 2015)
Cold tolerance adaption is a crucial determinant for the establishment and expansion of invasive alien plants into new cold environments; however, its evolutionary mechanism is poorly understood. Crofton weed ( Ageratina adenophora ), a highly invasive alien plant, is continuously spreading across subtropical areas in China, north‐eastward from the first colonized south‐western tropical regions, through cold tolerance evolution. Close relations between the cold tolerance levels of 34 populations, represented by 147 accessions, and the latitude, extreme lowest temperature, coldest month average temperature, and invasion period have provided direct insight into its cold tolerance divergence. A comparative study of the CBF pathway, associated with the cold tolerance enhancement of cold‐susceptible CBF 1 ‐transgenic plant, among four geographically distinct crofton weed populations revealed that the CBF pathway plays a key role in the observed cold tolerance divergence. Four epialleles of the cold response regulator ICE 1 ranged from 66 to 50 methylated cytosines, representing a 4.4% to 3.3% methylation rate and significantly corresponding to the lowest to highest cold tolerance levels among these different populations. The significant negative relation between the transcription levels of the primary CBF pathway members, except for CBF 2 , and the methylation levels among the four populations firstly demonstrates that the demethylation‐upregulated transcription level of CBF pathway is responsible for this evolution. These facts, combined with the cold tolerance variation and methylation found among three native and two other introduced populations, indicate that the ICE 1‐ demethylated upregulation of cold tolerance may be the underlying evolutionary mechanism allowing crofton weed to expand northward in China.

Genome and physiology of the ascomycete filamentous fungus X eromyces bisporus , the most xerophilic organism isolated to date - Su‐lin L. Leong; Henrik Lantz; Olga V. Pettersson; Jens C. Frisvad; Ulf Thrane; Hermann J. Heipieper; Jan Dijksterhuis; Manfred Grabherr; Mats Pettersson; Christian Tellgren‐Roth; Johan Schnürer (Environmental Microbiology, 2015)
Summary X eromyces bisporus can grow on sugary substrates down to 0.61, an extremely low water activity. Its genome size is approximately 22 Mb . Gene clusters encoding for secondary metabolites were conspicuously absent; secondary metabolites were not detected experimentally. Thus, in its ‘dry’ but nutrient‐rich environment, X . bisporus appears to have relinquished abilities for combative interactions. Elements to sense/signal osmotic stress, e.g. HogA pathway, were present in X . bisporus . However, transcriptomes at optimal (∼ 0.89) versus low a w (0.68) revealed differential expression of only a few stress‐related genes; among these, certain (not all) steps for glycerol synthesis were upregulated. X eromyces bisporus increased glycerol production during hypo‐ and hyper‐osmotic stress, and much of its wet weight comprised water and rinsable solutes; leaked solutes may form a protective slime. X eromyces bisporus and other food‐borne moulds increased membrane fatty acid saturation as water activity decreased. Such modifications did not appear to be transcriptionally regulated in X . bisporus ; however, genes modulating sterols, phospholipids and the cell wall were differentially expressed. X eromyces bisporus was previously proposed to be a ‘chaophile’, preferring solutes that disorder biomolecular structures. Both X . bisporus and the closely related xerophile, X erochrysium xerophilum , with low membrane unsaturation indices, could represent a phylogenetic cluster of ‘chaophiles’.

Chelator-enhanced phytoextraction of copper and zinc by sunflower, Chinese cabbage, cattails and reeds - T. Y. Yeh; C. L. Lin; C. F. Lin; C. C. Chen (International Journal of Environmental Science and Technology, 2015)

Helicobacter pylori infection and the risk of acute coronary syndrome: a nationwide retrospective cohort study - C.-Y. Lai; T.-Y. Yang; C.-L. Lin; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Migratory history of African longfinned eel Anguilla mossambica from Maningory River, Madagascar: discovery of a unique pattern in otolith Sr:Ca ratios - Yu-Jia Lin; Brian M. Jessop; Olaf L. F. Weyl; Yoshiyuki Iizuka; Shih-Huan Lin; Wann-Nian Tzeng (Environmental Biology of Fishes, 2015)

Description of a New Species of the Genus Macromotettixoides Zheng (Orthoptera: Tetrigoidea: Metrodorinae) from China - W A Deng; C-L Lei; Z M Zheng; X D Li; L L Lin; M P Lin (Neotropical Entomology, 2014)

AdeRS combination codes differentiate the response to efflux pump inhibitors in tigecycline-resistant isolates of extensively drug-resistant Acinetobacter baumannii - J.-R. Sun; C.-L. Perng; J.-C. Lin; Y.-S. Yang; M.-C. Chan; T.-Y. Chang; F.-M. Lin; T.-S. Chiueh (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Oxidative stress of maize roots caused by a combination of both salt stress and manganese deprivation - H.Q. Zhao; L. Wang; J. Hong; X.Y. Zhao; X.H. Yu; L. Sheng; C.Z. Hang; Y. Zhao; A.A. Lin; W.H. Si; F.S. Hong (Cereal Research Communications, 2014)

Molecular Aspects of Anti-Atherosclerotic Effects of Short Peptides - V. Kh. Khavinson; N. S. Lin’kova; E. V. Evlashkina; A. O. Durnova; K. L. Kozlov; O. E. Gutop (Bulletin of Experimental Biology and Medicine, 2014)

Association between herpes zoster and end stage renal disease entrance in chronic kidney disease patients: a population-based cohort study - S.-Y. Lin; J.-H. Liu; H.-C. Yeh; C.-L. Lin; I.-J. Tsai; P.-C. Chen; F.-C. Sung; Y.-F. Yang; C.-C. Huang; D. E. Morisky; Y.-J. Chang; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

On the origin of water-soluble organic tracer compounds in fine aerosols in two cities: the case of Los Angeles and Barcelona - M. Alier; M. Dall Osto; Y.-H. Lin; J. D. Surratt; R. Tauler; J. O. Grimalt; B. L. van Drooge (Environmental Science and Pollution Research, 2014)

The association between chronic osteomyelitis and increased risk of diabetes mellitus: a population-based cohort study - S.-Y. Lin; C.-L. Lin; C.-H. Tseng; I.-K. Wang; S.-M. Wang; C.-C. Huang; Y.-J. Chang; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Increased risk of pulmonary tuberculosis among patients with appendectomy in Taiwan - S.-W. Lai; C.-L. Lin; K.-F. Liao; S.-M. Tsai (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Evaluation of seedling resistance of rice germplasm resources to sheath blight (Rhizoctonia solani) - B. Chen; L.-W. Li; Y.-J. Lin; Z.-H. Wang; G.-D. Lu (Cereal Research Communications, 2014)

Molecular characterization of a new member of the 16SrV group of phytoplasma associated with Bischofia polycarpa (Levl.) Airy Shaw witches’ -broom disease in China by a multiple gene-based analysis - F. Lai; C. S. Song; Z. G. Ren; C. L. Lin; Q. C. Xu; Y. Li; C. G. Piao; S. S. Yu; M. W. Guo; G. Z. Tian (Australasian Plant Pathology, 2014)

A Review of the Genus Pielomastax Chang (Orthoptera: Eumastacoidea) from China with Description of a New Species - L L Lin; Z M Zheng; R Yang; S Q Xu (Neotropical Entomology, 2014)

Molecular characterization of domestic and exotic potato virus S isolates and a global analysis of genomic sequences - Y.-H. Lin; J. A. Abad; C. J. Maroon-Lango; K. L. Perry; H. R. Pappu (Archives of Virology, 2014)

Development of a selective and differential medium for capsulated L actococcus garvieae - C‐I Chang; C‐F Lee; J‐M Tsai; C‐C Wu; L‐H Chen; S‐C Chen; K‐J Lin (Journal of Fish Diseases, 2014)
A selective and differential medium termed ‘ LG agar’ was developed for the isolation and presumptive identification of L actococcus garvieae that results in black colonies with red halos. In this study, all 14 strains of L . garvieae and only 9 of the 148 strains representing 38 other species were able to grow on the LG agar. The nine viable strains on LG agar plates (including E nterococcus faecalis , E nterococcus faecium , L actococcus lactis , V ibrio fluvialis , V ibrio furnissii , V ibrio mimicus and V ibrio salmonicida ) were further differentiated from L . garvieae by various colours or colony features. Colonies isolated from the mixing culture and the infected giant sea perch using LG agar plates were all positively identified as L . garvieae by conventional tests and 16 S r DNA sequencing. Furthermore, LG agar discriminated capsulated strains of L . garvieae , which were believed to be correlated with pathogens of fish and shellfish, from non‐capsulated ones by colony appearances. The specificity and differentiating ability of LG agar suggest that this medium displays considerable potential for primary isolation and presumptive identification of L . garvieae from pathological and environmental samples.

Eutrophication as a driver of r ‐selection traits in a freshwater fish - M. Lin; M. Chevalier; S. Lek; L. Zhang; R. E. Gozlan; J. Liu; T. Zhang; S. Ye; W. Li; Z. Li (Journal of Fish Biology, 2014)
This study tested whether eutrophication could influence life‐history traits of a cyprinid, Chanodichthys erythropterus , in 10 Chinese lakes. Using the von Bertalanffy growth model, the asymptotic length ( L ∞ ) and the growth performance index ( I GRO ) were significantly affected by eutrophication. The gonado‐somatic index ( I G ) and relative fecundity ( F R ) were significantly lower in mesotrophic lakes than in eutrophic and hypertrophic lakes. These results indicate that increasing eutrophication affects the life‐history tactics of a freshwater fish.

Clinical characteristics and outcomes of patients with pleural infections due to Stenotrophomonas maltophilia at a medical center in Taiwan, 2004–2012 - M.-R. Lee; H.-C. Wang; C.-Y. Yang; C.-K. Lin; H.-Y. Kuo; J.-C. Ko; W.-H. Sheng; L.-N. Lee; C.-J. Yu; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Clinically Relevant Reperfusion in Acute Ischemic Stroke: MTT Performs Better than Tmax and TTP - Andria L. Ford; Hongyu An; Linglong Kong; Hongtu Zhu; Katie D. Vo; William J. Powers; Weili Lin; Jin-Moo Lee (Translational Stroke Research, 2014)

Effects of Dietary Selenium Deficiency on mRNA Levels of Twenty-One Selenoprotein Genes in the Liver of Layer Chicken - C. P. Liu; J. Fu; S. L. Lin; X. S. Wang; S. Li (Biological Trace Element Research, 2014)

Association between polymorphisms in the csrRS two-component regulatory system and invasive group A streptococcal infection - J.-N. Lin; L.-L. Chang; C.-H. Lai; H.-H. Lin; Y.-H. Chen (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Effects of Parkinson’s disease on optic flow perception for heading direction during navigation - Cheng-Chieh Lin; Robert C. Wagenaar; Daniel Young; Elliot L. Saltzman; Xiaolin Ren; Sandy Neargarder; Alice Cronin-Golomb (Experimental Brain Research, 2014)

Detection of human JCPyV and BKPyV in diffuse large B-cell lymphoma of the GI tract - C. E. Tseng; C. M. Yeh; C. Y. Fang; J. Shay; P. L. Chen; M. C. Lin; D. Chang; M. Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

An ecological function and services approach to total maximum daily load (TMDL) prioritization - Robert K. Hall; David Guiliano; Sherman Swanson; Michael J. Philbin; John Lin; Joan L. Aron; Robin J. Schafer; Daniel T. Heggem (Environmental Monitoring and Assessment, 2014)

Blockade of the renin–angiotensin system inhibits growth of colorectal cancer liver metastases in the regenerating liver - Shir Lin Koh; E. I. Ager; P. L. N. Costa; C. Malcontenti-Wilson; V. Muralidharan; C. Christophi (Clinical & Experimental Metastasis, 2014)

Sympatric Asian felid phylogeography reveals a major Indochinese–Sundaic divergence - Shu‐Jin Luo; Yue Zhang; Warren E. Johnson; Lin Miao; Paolo Martelli; Agostinho Antunes; James L. D. Smith; Stephen J. O'Brien (Molecular Ecology, 2014)
The dynamic geological and climatological history of Southeast Asia has spawned a complex array of ecosystems and 12 of the 37 known cat species, making it the most felid‐rich region in the world. To examine the evolutionary histories of these poorly studied fauna, we compared phylogeography of six species (leopard cat Prionailurus bengalensis , fishing cat P. viverrinus , Asiatic golden cat Pardofelis temminckii , marbled cat P. marmorata , tiger Panthera tigris and leopard P. pardus ) by sequencing over 5 kb of DNA each from 445 specimens at multiple loci of mt DNA , Y and X chromosomes. All species except the leopard displayed significant phylogenetic partitions between Indochina and Sundaland, with the central Thai–Malay Peninsula serving as the biogeographic boundary. Concordant mt DNA and nuclear DNA genealogies revealed deep Indochinese–Sundaic divergences around 2 MYA in both P. bengalensis and P. marmorata comparable to previously described interspecific distances within Felidae. The divergence coincided with serial sea level rises during the late Pliocene and early Pleistocene, and was probably reinforced by repeated isolation events associated with environmental changes throughout the Pleistocene. Indochinese–Sundaic differentiations within P. tigris and P. temminckii were more recent at 72–108 and 250–1570 kya, respectively. Overall, these results illuminate unexpected, deep vicariance events in Southeast Asian felids and provide compelling evidence of species‐level distinction between the Indochinese and Sundaic populations in the leopard cat and marbled cat. Broader sampling and further molecular and morphometric analyses of these species will be instrumental in defining conservation units and effectively preserving Southeast Asian biodiversity.

Lasting neurobehavioral abnormalities in rats after neonatal activation of serotonin 1A and 1B receptors: possible mechanisms for serotonin dysfunction in autistic spectrum disorders - Nidhi Khatri; Kimberly L. Simpson; Rick C. S. Lin; Ian A. Paul (Psychopharmacology, 2014)

Using the VIKOR method to evaluate the design of a water quality monitoring network in a watershed - C.-L. Chang; Y.-T. Lin (International Journal of Environmental Science and Technology, 2014)

Association analysis of 9,560 prostate cancer cases from the International Consortium of Prostate Cancer Genetics confirms the role of reported prostate cancer associated SNPs for familial disease - Craig C. Teerlink; Stephen N. Thibodeau; Shannon K. McDonnell; Daniel J. Schaid; Antje Rinckleb; Christiane Maier; Walther Vogel; Geraldine Cancel-Tassin; Christophe Egrot; Olivier Cussenot; William D. Foulkes; Graham G. Giles; et al. (Human Genetics, 2014)

Fatty Acid Methyl Esters and Solutol HS 15 Confer Neuroprotection after Focal and Global Cerebral Ischemia - Hung Wen Lin; Isabel Saul; Victoria L. Gresia; Jake T. Neumann; Kunjan R. Dave; Miguel A. Perez-Pinzon (Translational Stroke Research, 2014)

Unraveling the complex genetic model for cystic fibrosis: pleiotropic effects of modifier genes on early cystic fibrosis-related morbidities - Weili Li; David Soave; Melissa R. Miller; Katherine Keenan; Fan Lin; Jiafen Gong; Theodore Chiang; Anne L. Stephenson; Peter Durie; Johanna Rommens; Lei Sun; Lisa J. Strug (Human Genetics, 2014)

Trends in the susceptibility of methicillin-resistant Staphylococcus aureus to nine antimicrobial agents, including ceftobiprole, nemonoxacin, and tyrothricin: results from the Tigecycline In Vitro Surveillance in Taiwan (TIST) study, 2006–2010 - Y.-H. Chen; C.-Y. Liu; W.-C. Ko; C.-H. Liao; P.-L. Lu; C.-H. Huang; C.-T. Lu; Y.-C. Chuang; S.-M. Tsao; Y.-S. Chen; Y.-C. Liu; W.-Y. Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Investigating the adaptation of muscle oxygenation to resistance training for elders and young men using near-infrared spectroscopy - Tai-You Lin; Linda L. Lin; Ting-Chuan Ho; Jia-Jin J. Chen (European Journal of Applied Physiology, 2014)

Evaluating the protective efficacy of antigen combinations against P hotobacterium damselae ssp. piscicida infections in cobia, Rachycentron canadum L. - L‐P Ho; C‐J Chang; H‐C Liu; H‐L Yang; J H‐Y Lin (Journal of Fish Diseases, 2014)
Cobia, Rachycentron canadum L., is a very important aquatic fish that faces the risk of infection with the bacterial pathogen P hotobacterium damselae ssp. piscicida , and there are few protective approaches available that use multiple antigens. In the present study, potent bivalent antigens from P . damselae ssp. piscicida showed more efficient protection than did single antigens used in isolation. In preparations of three antigens that included recombinant heat shock protein 60 ( rHSP 60), recombinant α‐enolase ( rENOLASE ) and recombinant glyceraldehyde‐3‐phosphate dehydrogenase ( rGAPDH ), we analysed the doses that elicited the best immune responses and found that this occurred at a total of 30 μg of antigen per fish. Subsequently, vaccination of fish with rHSP 60, rENOLASE and rGAPDH achieved 46.9, 52 and 25% relative per cent survival (RPS), respectively. In addition, bivalent subunit vaccines – combination I ( rHSP 60 + rENOLASE ), combination II ( rENOLASE + rGAPDH ) and combination III ( rHSP 60 + rGAPDH ) – were administered and the RPS in these groups (65.6, 64.0 and 48.4%, respectively), was higher than that achieved with single‐antigen administration. Finally, in combination IV , the trivalent vaccine rHSP 60 + rENOLASE + rGAPDH , the RPS was 1.6%. Taken together, our results suggest that combinations of two antigens may achieve a better efficiency than monovalent or trivalent antigens, and this may provide new insights into pathogen prevention strategies.

White spot syndrome virus epizootic in cultured P acific white shrimp L itopenaeus vannamei (Boone) in T aiwan - L Cheng; W‐H Lin; P‐C Wang; M‐A Tsai; J‐P Hsu; S‐C Chen (Journal of Fish Diseases, 2013)
White spot syndrome virus ( WSSV ) has caused significant losses in shrimp farms worldwide. Between 2004 and 2006, Pacific white shrimp L itopenaeus vannamei (Boone) were collected from 220 farms in T aiwan to determine the prevalence and impact of WSSV infection on the shrimp farm industry. Polymerase chain reaction ( PCR ) analysis detected WSSV in shrimp from 26% of farms. Juvenile shrimp farms had the highest infection levels (38%; 19/50 farms) and brooder shrimp farms had the lowest (5%; one of 20 farms). The average extent of infection at each farm was as follows for WSSV ‐positive farms: post‐larvae farms, 71%; juvenile farms, 61%; subadult farms, 62%; adult farms, 49%; and brooder farms, 40%. Characteristic white spots, hypertrophied nuclei and basophilic viral inclusion bodies were found in the epithelia of gills and tail fans, appendages, cephalothorax and hepatopancreas, and virions of WSSV were observed. Of shrimp that had WSSV lesions, 100% had lesions on the cephalothorax, 96% in gills and tail fans, 91% on appendages and 17% in the hepatopancreas. WSSV was also detected in copepoda and crustaceans from the shrimp farms. Sequence comparison using the pms146 gene fragment of WSSV showed that isolates from the farms had 99.7–100% nucleotide sequence identity with four strains in the G en B ank database – China ( AF332093 ), T aiwan ( AF440570 and U50923 ) and Thailand ( AF369029 ). This is the first broad study of WSSV infection in L . vannamei in T aiwan.

Haematopoietic necrosis of cultured Prussian carp, C arassius gibelio ( B loch), associated with C yprinid herpesvirus 2 - Y Z Luo; L Lin; Y Liu; Z X Wu; Z M Gu; L J Li; J F Yuan (Journal of Fish Diseases, 2013)

Potential use of chitosan nanoparticles for oral delivery of DNA vaccine in black seabream Acanthopagrus schlegelii Bleeker to protect from Vibrio parahaemolyticus - L Li; S‐L Lin; L Deng; Z‐G Liu (Journal of Fish Diseases, 2013)
To develop an effective and easy‐to‐administer vaccine against vibriosis of fish, the chitosan nanoparticles‐loaded DNA vaccine against Vibrio parahaemolyticus was studied. A DNA vaccine was constructed using the outer membrane protein K ( ompK ) gene of V. parahaemolyticus strain (OS4) and pEGFP ‐N 2 , a eukaryotic expression vector, and the construct was named pEGFP ‐N 2 ‐OMPK ( pDNA ). The pDNA was encapsulated in chitosan particles (chitosan/ pDNA ). The effective diameter, mean diameter and polydispersity of the particles were 284.4 nm, 218.9 nm and 0.160, respectively. Scanning electron microscopy showed that the particles are dispersed as individual nanoparticles with spherical shape of around 200 nm and are homogeneously distributed. Encapsulation efficiency and loading percentage of nanoparticles were 91.5% and 2.08%, respectively. Reverse transcription–polymerase chain reaction (RT‐PCR) showed that RNA‐containing information of the ompK gene existed in mid‐intestine, liver, kidney and muscle 3 weeks after oral administration in black seabream Acanthopagrus schlegelii Bleeker. Expression of the reporter gene, green fluorescent protein ( GFP ), was observed in the above‐mentioned tissues by fluorescence microscopy. Expression of the ompK gene within 3 weeks evoked an immune response. Black seabream was protected from V. parahaemolyticus (OS4), with 72.3% relative percentage survival (RPS) 3 weeks post‐vaccination with chitosan/ pDNA . The direct agglutination test indicated that oral administration with chitosan/ pDNA induced an antibody immune response in fish against V. parahaemolyticus (OS4). Data obtained, here and in other related studies, suggest that chitosan nanoparticles are promising carriers for an oral pDNA vaccine.

Isolation and molecular analysis of genes Stpk-V2 and Stpk-V3 homologous to powdery mildew resistance gene Stpk-V in a Dasypyrum villosum accession and its derivatives - Z. S. Lin; Y. L. Zhang; M. J. Wang; J. R. Li; K. Wang; X. Chen; Q. F. Xu; X. S. Zhang; X. G. Ye (Journal of Applied Genetics, 2013)

Cardiac glutaminolysis: a maladaptive cancer metabolism pathway in the right ventricle in pulmonary hypertension - Lin Piao; Yong-Hu Fang; Kishan Parikh; John J. Ryan; Peter T. Toth; Stephen L. Archer (Journal of Molecular Medicine, 2013)

Preladenant, a selective adenosine A2A receptor antagonist, is not associated with QT/QTc prolongation - Z. Wang; F. Xuan; W. H. Lin; M. D. Troyer; A. Tendolkar; D. L. Cutler (European Journal of Clinical Pharmacology, 2013)

The California Breast Cancer Survivorship Consortium (CBCSC): prognostic factors associated with racial/ethnic differences in breast cancer survival - Anna H. Wu; Scarlett Lin Gomez; Cheryl Vigen; Marilyn L. Kwan; Theresa H. M. Keegan; Yani Lu; Salma Shariff-Marco; Kristine R. Monroe; Allison W. Kurian; Iona Cheng; Bette J. Caan; Valerie S. Lee; et al. (Cancer Causes & Control, 2013)

Generation of mice encoding a conditional allele of Nkx2.2 - Teresa L. Mastracci; Chyuan-Sheng Lin; Lori Sussel (Transgenic Research, 2013)

Nyamiviridae: Proposal for a new family in the order Mononegavirales - Jens H. Kuhn; Sadia Bekal; Yíngyún Caì; Anna N. Clawson; Leslie L. Domier; Marieke Herrel; Peter B. Jahrling; Hideki Kondo; Kris N. Lambert; Kathie A. Mihindukulasuriya; Norbert Nowotny; Sheli R. Radoshitzky; et al. (Archives of Virology, 2013)

High Sensitivity Micro-Elastometry: Applications in Blood Coagulopathy - Gongting Wu; Charles R. Krebs; Feng-Chang Lin; Alisa S. Wolberg; Amy L. Oldenburg (Annals of Biomedical Engineering, 2013)

Pregnancy Represses Induction of Efflux Transporters in Livers of Type I Diabetic Mice - Lauren M. Aleksunes; Jialin Xu; Eugenia Lin; Xia Wen; Michael J. Goedken; Angela L. Slitt (Pharmaceutical Research, 2013)

Core–shell magnetite-silica dithiocarbamate-derivatised particles achieve the Water Framework Directive quality criteria for mercury in surface waters - C. B. Lopes; P. Figueira; D. S. Tavares; Z. Lin; A. L. Daniel-da-Silva; A. C. Duarte; J. Rocha; T. Trindade; E. Pereira (Environmental Science and Pollution Research, 2013)

Effect of acute DHEA administration on free testosterone in middle-aged and young men following high-intensity interval training - Te-Chih Liu; Che-Hung Lin; Chih-Yang Huang; John L. Ivy; Chia-Hua Kuo (European Journal of Applied Physiology, 2013)

The use of procalcitonin in the diagnosis of bone and joint infection: a systemic review and meta-analysis - C.-J. Shen; M.-S. Wu; K.-H. Lin; W.-L. Lin; H.-C. Chen; J.-Y. Wu; M. C.-H. Lee; C.-C. Lee (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Characterization of a novel cell line from the caudal fin of koi carp Cyprinus carpio - S.‐L. Lin; Y.‐H. Cheng; C.‐M. Wen; S.‐N. Chen (Journal of Fish Biology, 2013)
A continuous cell line ( KF ‐101) derived from the caudal fin of the koi carp Cyprinus carpio was established and characterized. The KF ‐101 cell line multiplied abundantly in Leibovitz's L‐15 medium containing 10% foetal bovine serum at 25° C, and was subcultured for >90 passages over a period of 3 years. Immunocytochemistry revealed that the KF ‐101 cells contain keratin, junction proteins connexin‐43 and occludin, and ectodermal stem‐cell marker Pax‐6, but not vimentin. Furthermore, the KF ‐101 cells reacted with anti‐human DARPP ‐32 and anti‐human GATA ‐4 antibodies, and the labelling was regulated according to the cell cycle. The labels of the DARPP ‐32 and GATA ‐4 antibodies in the KF ‐101 cells were the suggested phosphatase‐1 inhibitor‐1 and GATA ‐3, respectively. In addition, the KF ‐101 cells were susceptible to koi herpesvirus but were resistant to eel herpesvirus, iridovirus, grouper nodavirus and chum salmon ( Oncorhynchus keta ) virus. The results indicate that the KF ‐101 cells are suitable materials for investigating biological and virological development.

Isolation of multilineage progenitors from mouse brain - Chiann-Chyi Chen; Hsing-I Huang; Cassandra L. Louis; Kao-Tien Lin; Yacov Ron (In Vitro Cellular & Developmental Biology - Animal, 2013)

Hepatic apoptosis can modulate liver fibrosis through TIMP1 pathway - Kewei Wang; Bingliang Lin; John J. Brems; Richard L. Gamelli (Apoptosis, 2013)

Prevalence of type-specific human papillomavirus and pap results in Chinese women: a multi-center, population-based cross-sectional study - En-Qi Wu; Bin Liu; Jian-Feng Cui; Wen Chen; Jian-Bing Wang; Liang Lu; Mayineur Niyazi; Chao Zhao; Sheng-Da Ren; Chang-Qing Li; Xiang-Zhen Gong; Jennifer S. Smith; et al. (Cancer Causes & Control, 2013)

Effect of Zinc Source on Performance, Zinc Status, Immune Response, and Rumen Fermentation of Lactating Cows - Run L. Wang; Jian G. Liang; Lin Lu; Li Y. Zhang; Su F. Li; Xu G. Luo (Biological Trace Element Research, 2013)

Pseudomonas aeruginosa isolates of distinct sub-genotypes exhibit similar potential of antimicrobial resistance by drugs exposure - Zhen-Hong Liu; Yan Xu; Li-Bo Duo; Yu Liu; Zhao-Zhen Xu; Jane L. Burns; Gui-Rong Liu; Bao-Feng Yang; Shu-Lin Liu (Antonie van Leeuwenhoek, 2013)

FOXO1-mediated upregulation of pyruvate dehydrogenase kinase-4 (PDK4) decreases glucose oxidation and impairs right ventricular function in pulmonary hypertension: therapeutic benefits of dichloroacetate - Lin Piao; Vaninder K. Sidhu; Yong-Hu Fang; John J. Ryan; Kishan S. Parikh; Zhigang Hong; Peter T. Toth; Erik Morrow; Shelby Kutty; Gary D. Lopaschuk; Stephen L. Archer (Journal of Molecular Medicine, 2013)

Sex identification in the Collared Scops Owl (Otus bakkamoena) with novel markers generated by random amplified polymorphic DNA - P. H. Wang; H. A. Hsu; M. C. Chao; F. T. Chan; L. M. Wang; P. I. Lin; H. S. Tsao; H. W. Yuan; C. C. Chen; S. T. Ding (Conservation Genetics Resources, 2013)

Allelopathic Exudates of Cogongrass (Imperata cylindrica): Implications for the Performance of Native Pine Savanna Plant Species in the Southeastern US - Donald L. Hagan; Shibu Jose; Chung-Ho Lin (Journal of Chemical Ecology, 2013)

Fabrication and Mechanical Evaluation of Anatomically-Inspired Quasilaminate Hydrogel Structures with Layer-Specific Formulations - Hubert Tseng; Maude L. Cuchiara; Christopher A. Durst; Michael P. Cuchiara; Chris J. Lin; Jennifer L. West; K. Jane Grande-Allen (Annals of Biomedical Engineering, 2013)

HOXB13 is a susceptibility gene for prostate cancer: results from the International Consortium for Prostate Cancer Genetics (ICPCG) - Jianfeng Xu; Ethan M. Lange; Lingyi Lu; Siqun L. Zheng; Zhong Wang; Stephen N. Thibodeau; Lisa A. Cannon-Albright; Craig C. Teerlink; Nicola J. Camp; Anna M. Johnson; Kimberly A. Zuhlke; Janet L. Stanford; et al. (Human Genetics, 2013)

Selenoprotein P and Yunnan Endemic Sudden Cardiac Death—an Ecological Study - Q. Li; X. Z. Li; T. Wang; L. W. Zhou; H. Q. Feng; L. Gao; J. R. Pei; C. Lin; C. X. Jiang (Biological Trace Element Research, 2013)

Analysis of carbamazepine serum by differential pulse voltammetry (DPV) and comparison with fluorescence polarization immunoassay (FPIA): an animal study - W. Y. Lin; M. L. Pan; H. Y. Wang; Y. O. Su; P. W. Huang (Medicinal Chemistry Research, 2012)

Role of Neurotrophins in the Development and Function of Neural Circuits That Regulate Energy Homeostasis - Samira Fargali; Masato Sadahiro; Cheng Jiang; Amy L. Frick; Tricia Indall; Valeria Cogliani; Jelle Welagen; Wei-Jye Lin; Stephen R. Salton (Journal of Molecular Neuroscience, 2012)

Relationships Between Nitrogen Transformation Rates and Gene Abundance in a Riparian Buffer Soil - Lin Wu; Deanna L. Osmond; Alexandria K. Graves; Michael R. Burchell; Owen W. Duckworth (Environmental Management, 2012)

Extracytoplasmic Stress Responses Induced by Antimicrobial Cationic Polyethylenimines - Blaine A. Lander; Kyle D. Checchi; Stephen A. Koplin; Virginia F. Smith; Tammy L. Domanski; Daniel D. Isaac; Shirley Lin (Current Microbiology, 2012)

Halohasta litorea gen. nov. sp. nov., and Halohasta litchfieldiae sp. nov., isolated from the Daliang aquaculture farm, China and from Deep Lake, Antarctica, respectively - Yun-Zhuang Mou; Xing-Xing Qiu; Mei-Lin Zhao; Heng-Lin Cui; Dickson Oh; Mike L. Dyall-Smith (Extremophiles, 2012)

Bromoform production from seawater treated with bromoperoxidase - Chia Yu Lin; Steven L. Manley (Limnology and Oceanography, 2012)
Bromoform (CHBr 3 ; 11–486 fmol L −1 h −1 ), dibromomethane (CH 2 Br 2 ; 0–9.4 fmol L −1 h −1 ), and low amounts of chloride‐substituted chlorobromomethanes were produced from southern California coastal surface seawater upon the addition of algal bromoperoxidase (BrPO) and hydrogen peroxide. Production was greater from water collected near shore than 16 km offshore, presumably reflecting the difference in the reactive dissolved organic matter (DOM react ) concentrations. In the spring, there was an increase in phytoplankton abundance, and CHBr 3 production from BrPO incubations was greater, presumably due to increased DOM react . In the winter, CH 2 Br 2 production was enhanced, although still lower than CHBr 3 , suggesting a qualitative change in DOM composition due to terrestrial runoff. During the month of the highest precipitation, CHBr 3 and CH 2 Br 2 production was enhanced in samples obtained from the mouth of an urban river, suggesting a higher concentration of DOM react of terrestrial origins. DOM was fractionated by ultrafiltration and subject to the BrPO incubation. The higher molecular weight fractions contained a higher concentration of DOM that was susceptible to BrPO bromination, yielding polybromomethanes. Polybromomethane and iodomethane production associated with phytoplankton blooms results from the reaction between the surrounding DOM, and hypobromous acid (HOBr) and hypoiodous acid released from extracellular (apoplastic) BrPO. The reaction of HOBr and DOM (biological bleaching) could represent a significant DOM degradation pathway. Cell‐free BrPO, derived from dead cells, could remain catalytically active in seawater and produce low amounts of polyhalomethanes prior to biological degradation.

Role of obesity in a randomized placebo-controlled trial of difluoromethylornithine (DFMO) + sulindac for the prevention of sporadic colorectal adenomas - Jason A. Zell; Bruce S. Lin; Nikki Madson; Christine E. McLaren; Eugene W. Gerner; Frank L. Meyskens (Cancer Causes & Control, 2012)

Functional redundancy of the two 5-hydroxylases in monolignol biosynthesis of Populus trichocarpa: LC–MS/MS based protein quantification and metabolic flux analysis - Jack P. Wang; Christopher M. Shuford; Quanzi Li; Jina Song; Ying-Chung Lin; Ying-Hsuan Sun; Hsi-Chuan Chen; Cranos M. Williams; David C. Muddiman; Ronald R. Sederoff; Vincent L. Chiang (Planta, 2012)

Productive leaf functional traits of Chinese savanna species - Jiao-Lin Zhang; L. Poorter; Kun-Fang Cao (Plant Ecology, 2012)

The Niujiaotang Cd-rich zinc deposit, Duyun, Guizhou province, southwest China: ore genesis and mechanisms of cadmium concentration - Lin Ye; Nigel J. Cook; Tiegeng Liu; Cristiana L. Ciobanu; Wei Gao; Yulong Yang (Mineralium Deposita, 2012)

Characterization of carbapenem-nonsusceptible Klebsiella pneumoniae bloodstream isolates at a Taiwanese hospital: clinical impacts of lowered breakpoints for carbapenems - N. Y. Lee; J. J. Wu; S. H. Lin; W. C. Ko; L. H. Tsai; J. J. Yan (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Validation of prostate cancer risk-related loci identified from genome-wide association studies using family-based association analysis: evidence from the International Consortium for Prostate Cancer Genetics (ICPCG) - Guangfu Jin; Lingyi Lu; Kathleen A. Cooney; Anna M. Ray; Kimberly A. Zuhlke; Ethan M. Lange; Lisa A. Cannon-Albright; Nicola J. Camp; Craig C. Teerlink; Liesel M. FitzGerald; Janet L. Stanford; Kathleen E. Wiley; et al. (Human Genetics, 2012)

Regional variation in otolith Sr:Ca ratios of African longfinned eel Anguilla mossambica and mottled eel Anguilla marmorata : a challenge to the classic tool for reconstructing migratory histories of fishes - Y.‐J. Lin; B. M. Jessop; O. L. F. Weyl; Y. Iizuka; S.‐H. Lin; W.‐N. Tzeng; C.‐L. Sun (Journal of Fish Biology, 2012)
Otolith Sr:Ca ratios of the African longfinned eel Anguilla mossambica and giant mottled eel Anguilla marmorata from nine freshwater sites in four rivers of South Africa were analysed to reconstruct their migratory life histories between freshwater and saltwater habitats. For A. mossambica , the Sr:Ca ratios in the otolith edge differed significantly among rivers and had large effect sizes, but did not differ among sites within a river. Otolith Sr:Ca ratios did not differ among rivers for A. marmorata . When rivers were pooled, the edge Sr:Ca ratios of A. mossambica were not significantly different from those of A. marmorata . According to the river‐specific critical Sr:Ca ratio distinguishing freshwater from saltwater residence, most A. mossambica and A. marmorata had saltwater habitat experience after settlement in fresh water. This was primarily during their elver stage or early in the yellow eel stage. During the middle and late yellow eel stage, freshwater residency was preferred and only sporadic visits were made to saltwater habitats. The data also suggest that regional variations in otolith Sr:Ca ratios affect the critical Sr:Ca value and are a challenge for the reconstruction of migratory life histories that should be explicitly considered to avoid bias and uncertainty.

Immunoaffinity chromatography purification and ultra-high-performance liquid chromatography-tandem mass spectrometry determination of four β-agonists in beef - Q.-B. Lin; X.-T. Zhao; H. Song; Y.-L. Pan (Food Additives & Contaminants: Part A, 2012)

Defining the Ischemic Penumbra Using Hyperacute Neuroimaging: Deriving Quantitative Ischemic Thresholds - Andria L. Ford; Hongyu An; Katie D. Vo; Weili Lin; Jin-Moo Lee (Translational Stroke Research, 2012)

Gastrin inhibits a novel, pathological colon cancer signaling pathway involving EGR1, AE2, and P-ERK - Ling-Jun Song; Rui-Jun Liu; Zhi Zeng; Seth L. Alper; Heng-Jing Cui; Yang Lu; Lin Zheng; Zhao-Wen Yan; Guo-Hui Fu (Journal of Molecular Medicine, 2012)

Enhancing a Cancer Prevention and Control Curriculum Through Interactive Group Discussions - L. P. Forsythe; S. M. Gadalla; J. G. Hamilton; B. M. Heckman-Stoddard; E. E. Kent; G. Y. Lai; S. W. Lin; P. Luhn; J. M. Faupel-Badger (Journal of Cancer Education, 2012)

Acute effects of plyometric jumping and intermittent running on serum bone markers in young males - Che-Fu Lin; Tsang-hai Huang; Kuo-Cheng Tu; Linda L. Lin; Yi-Hsuan Tu; Rong-Sen Yang (European Journal of Applied Physiology, 2012)

Oxygen Metabolism in Ischemic Stroke Using Magnetic Resonance Imaging - Hongyu An; Qingwei Liu; Yasheng Chen; Katie D. Vo; Andria L. Ford; Jin-Moo Lee; Weili Lin (Translational Stroke Research, 2012)

Regional economic impact analysis of earthquakes in northern Taiwan and its implications for disaster reduction policies - H. C. Lin; Y. L. Kuo; D. Shaw; M. C. Chang; T. M. Kao (Natural Hazards, 2012)

Seasonal Variation and Health Risk Assessment of Polycyclic Aromatic Hydrocarbons in Miaoli City, Taiwan - C. C. Wu; T. S. Lin; T. T. Yang; H. W. Hsu; C. L. Chang; C. H. Huang; W. Y. Lin (Bulletin of Environmental Contamination and Toxicology, 2012)

Climate Change Effects on Hydrology and Ecology of Wetlands in the Mid-Atlantic Highlands - Jonathan L. Pitchford; Chenjie Wu; LianShin Lin; J. Todd Petty; Richard Thomas; Walter E. Veselka; Danny Welsch; Nicolas Zegre; James T. Anderson (Wetlands, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Genetic diversity of ‘Cadidatus Liberibacter solanacearum’ strains in the United States and Mexico revealed by simple sequence repeat markers - Hong Lin; Md Sajedul Islam; Yang Bai; Amin Wen; Suque Lan; Neil C. Gudmestad; Edwin L. Civerolo (European Journal of Plant Pathology, 2012)

Bait worm packaging as a potential vector of invasive species - Christina L. Haska; Charles Yarish; George Kraemer; Noreen Blaschik; Robert Whitlatch; Huan Zhang; Senjie Lin (Biological Invasions, 2012)

Waking with the hypothalamus - Helmut L. Haas; Jian-Sheng Lin (Pflügers Archiv - European Journal of Physiology, 2012)

Therapeutic inhibition of fatty acid oxidation in right ventricular hypertrophy: exploiting Randle’s cycle - Yong-Hu Fang; Lin Piao; Zhigang Hong; Peter T. Toth; Glenn Marsboom; Peter Bache-Wiig; Jalees Rehman; Stephen L. Archer (Journal of Molecular Medicine, 2012)

Arsenic content, fractionation, and ecological risk in the surface sediments of lake - S. L. Wang; C. Y. Lin; X. Z. Cao; X. Zhong (International Journal of Environmental Science and Technology, 2012)

Liposomes Containing (-)-Gossypol-Enriched Cottonseed Oil Suppress Bcl-2 and Bcl-xL Expression in Breast Cancer Cells - Hong Li; Longzhu Piao; Pingping Xu; Weiping Ye; Saiyi Zhong; Shu-Hong Lin; Samuel K. Kulp; Yicheng Mao; Youngah Cho; L. James Lee; Robert J. Lee; Young C. Lin (Pharmaceutical Research, 2011)

Attribute-Based Design Space: Materials-Science-Based Quality-By-Design for Operational Flexibility and Process Portability - James N. Michaels; Holly Bonsignore; Buffy L. Hudson-Curtis; Steven Laurenz; Hung-Ren Homer Lin; Thomas Mathai; Girish Pande; Ashlesh Sheth; Omar Sprockel (Journal of Pharmaceutical Innovation, 2011)

Biodegradation of Cypermethrin by a newly isolated actinomycetes HU-S-01 from wastewater sludge - Q. S. Lin; S. H. Chen; M. Y. Hu; M. R. Ul Haq; L. Yang; H. Li (International Journal of Environmental Science and Technology, 2011)

The effect of the expression of virulence-associated DEAD-box RNA helicase mRNA on the imbalance of Th1-Th2 cytokines in the CSF of patients with Cryptococcus neoformans meningitis - L. Jiang; N. Lin; Z. Cheng; B. Yang; Q. Ou (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Gold Nanoparticle Penetration and Reduced Metabolism in Human Skin by Toluene - Hagar I. Labouta; David C. Liu; Lynlee L. Lin; Margaret K. Butler; Jeffrey E. Grice; Anthony P. Raphael; Tobias Kraus; Labiba K. El-Khordagui; H. Peter Soyer; Michael S. Roberts; Marc Schneider; Tarl W. Prow (Pharmaceutical Research, 2011)

Time-Correlated Single Photon Counting For Simultaneous Monitoring Of Zinc Oxide Nanoparticles And NAD(P)H In Intact And Barrier-Disrupted Volunteer Skin - Lynlee L. Lin; Jeffrey E. Grice; Margaret K. Butler; Andrei V. Zvyagin; Wolfgang Becker; Thomas A. Robertson; H. Peter Soyer; Michael S. Roberts; Tarl W. Prow (Pharmaceutical Research, 2011)

Three new species of Lentinus from northern Thailand - Samantha C. Karunarathna; Zhu L. Yang; Rui-Lin Zhao; Else C. Vellinga; A. H. Bahkali; Ekachai Chukeatirote; Kevin D. Hyde (Mycological Progress, 2011)

Practical considerations for the rapid screening for pesticides using ambient pressure desorption ionisation with high-resolution mass spectrometry - S.E. Edison; L.A. Lin; L. Parrales (Food Additives & Contaminants: Part A, 2011)

Multi-Decadal Changes in Tundra Environments and Ecosystems: Synthesis of the International Polar Year-Back to the Future Project (IPY-BTF) - Terry V. Callaghan; Craig E. Tweedie; Jonas Åkerman; Christopher Andrews; Johan Bergstedt; Malcolm G. Butler; Torben R. Christensen; Dorothy Cooley; Ulrika Dahlberg; Ryan K. Danby; Fred J. A. Daniёls; Johannes G. de Molenaar; et al. (Ambio, 2011)

A nested case–control study of low birthweight among cosmetologists - Michele L. Herdt-Losavio; Shao Lin; Charlotte M. Druschel; Syni-An Hwang; Matthew P. Mauer; G. Anders Carlson (International Archives of Occupational and Environmental Health, 2011)

Diagnostic performance of an enzyme-linked immunospot assay for interferon-γ in skeletal tuberculosis - C.-C. Lai; C.-K. Tan; W.-L. Liu; S.-H. Lin; Y.-T. Huang; C.-H. Liao; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Clinical significance of nontuberculous mycobacteria isolates in elderly Taiwanese patients - C.-C. Lai; C. K. Tan; S. H. Lin; W. L. Liu; C. H. Liao; Y. T. Huang; P. R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

A novel statistical method for classifying habitat generalists and specialists - Robin L. Chazdon; Anne Chao; Robert K. Colwell; Shang-Yi Lin; Natalia Norden; Susan G. Letcher; David B. Clark; Bryan Finegan; J. Pablo Arroyo (Ecology, 2011)
We develop a novel statistical approach for classifying generalists and specialists in two distinct habitats. Using a multinomial model based on estimated species relative abundance in two habitats, our method minimizes bias due to differences in sampling intensities between two habitat types as well as bias due to insufficient sampling within each habitat. The method permits a robust statistical classification of habitat specialists and generalists, without excluding rare species a priori. Based on a user‐defined specialization threshold, the model classifies species into one of four groups: (1) generalist; (2) habitat A specialist; (3) habitat B specialist; and (4) too rare to classify with confidence. We illustrate our multinomial classification method using two contrasting data sets: (1) bird abundance in woodland and heath habitats in southeastern Australia and (2) tree abundance in second‐growth (SG) and old‐growth (OG) rain forests in the Caribbean lowlands of northeastern Costa Rica. We evaluate the multinomial model in detail for the tree data set. Our results for birds were highly concordant with a previous nonstatistical classification, but our method classified a higher fraction (57.7%) of bird species with statistical confidence. Based on a conservative specialization threshold and adjustment for multiple comparisons, 64.4% of tree species in the full sample were too rare to classify with confidence. Among the species classified, OG specialists constituted the largest class (40.6%), followed by generalist tree species (36.7%) and SG specialists (22.7%). The multinomial model was more sensitive than indicator value analysis or abundance‐based phi coefficient indices in detecting habitat specialists and also detects generalists statistically. Classification of specialists and generalists based on rarefied subsamples was highly consistent with classification based on the full sample, even for sampling percentages as low as 20%. Major advantages of the new method are (1) its ability to distinguish habitat generalists (species with no significant habitat affinity) from species that are simply too rare to classify and (2) applicability to a single representative sample or a single pooled set of representative samples from each of two habitat types. The method as currently developed can be applied to no more than two habitats at a time.

Quantitative trait loci for temperature-sensitive resistance to Puccinia striiformis f. sp. tritici in wheat cultivar Flinor - J. Feng; L. L. Zuo; Z. Y. Zhang; R. M. Lin; Y. Y. Cao; S. C. Xu (Euphytica, 2011)

The California Neighborhoods Data System: a new resource for examining the impact of neighborhood characteristics on cancer incidence and outcomes in populations - Scarlett Lin Gomez; Sally L. Glaser; Laura A. McClure; Sarah J. Shema; Melissa Kealey; Theresa H. M. Keegan; William A. Satariano (Cancer Causes & Control, 2011)

Investigation of the Interaction Between the Ser447Term Polymorphism of Lipoprotein Lipase and the Stroke-Related Risk Factors in Ischemic Stroke - Yumei Yang; Danhua Du; Peng Gao; Xuan Zhang; Ning Wu; Feng Wang; Zhenqi Wang; Lin Ye; Jiang Wu; Ian L. Megson; Jun Wei (Translational Stroke Research, 2011)

A Protocol for Characterizing the Impact of Collateral Flow after Distal Middle Cerebral Artery Occlusion - Richard Anthony DeFazio; Sean Levy; Carmen L. Morales; Rebecca V. Levy; Hung W. Lin; Tatjana Abaffy; Kunjan R. Dave; Brant D. Watson; Miguel A. Perez-Pinzon; Victoria Ohanna (Translational Stroke Research, 2011)

Manganese Superoxide Dismutase Deficiency Exacerbates Ischemic Brain Damage Under Hyperglycemic Conditions by Altering Autophagy - Suresh L. Mehta; Yanling Lin; Wenge Chen; Fengshan Yu; Luyi Cao; Qingping He; Pak H. Chan; P. Andy Li (Translational Stroke Research, 2011)

Papillary thyroid cancer incidence rates vary significantly by birthplace in Asian American women - Pamela L. Horn-Ross; Laura A. McClure; Ellen T. Chang; Christina A. Clarke; Theresa H. M. Keegan; Rudolph P. Rull; Thu Quach; Scarlett Lin Gomez (Cancer Causes & Control, 2011)

Genomic sequence of an avian paramyxovirus type 1 strain isolated from Muscovy duck (Cairina moschata) in China - S.-H. Shi; Yu Huang; S.-J. Cui; L.-F. Cheng; G.-H. Fu; X. Li; Z. Chen; C.-X. Peng; F. Lin; J.-S. Lin; Jing-Liang Su (Archives of Virology, 2011)

Algal Growth Control Within Natural Water Purification Systems: Macrophyte Light Shading Effects - T. Y. Yeh; T. Y. Ke; Y. L. Lin (Water, Air, & Soil Pollution, 2011)

Adaptation or preadaptation: why are keelback snakes (Tropidonophis mairii) less vulnerable to invasive cane toads (Bufo marinus) than are other Australian snakes? - John Llewelyn; Ben L. Phillips; Greg P. Brown; Lin Schwarzkopf; Ross A. Alford; Richard Shine (Evolutionary Ecology, 2011)

The detection of “Candidatus Mycoplasma haemobos” in cattle and buffalo in China - Q. L. Su; H. Q. Song; R. Q. Lin; Z. G. Yuan; J. F. Yang; G. H. Zhao; W. Y. Huang; Xing Quan Zhu (Tropical Animal Health and Production, 2010)

Genetic polymorphisms of the DNA repair geneMPG may be associated with susceptibility to rheumatoid arthritis - S. Y. Chen; L. Wan; C. M. Huang; Y. C. Huang; J. J. C. Sheu; Y. J. Lin; S. P. Liu; Y. C. Lan; C. H. Lai; C. W. Lin; C. H. Tsai; F. J. Tsai (Journal of Applied Genetics, 2010)

Effect of Dietary Supplementation with Copper Sulfate or Tribasic Copper Chloride on the Growth Performance, Liver Copper Concentrations of Broilers Fed in Floor Pens, and Stabilities of Vitamin E and Phytase in Feeds - Lin Lu; Run L. Wang; Zheng J. Zhang; Fred A. Steward; Xugang Luo; Bin Liu (Biological Trace Element Research, 2010)

Sex-specific genetic architecture of human fatness in Chinese: the SAPPHIRe Study - Y.-F. Chiu; L.-M. Chuang; H.-Y. Kao; K.-C. Shih; M.-W. Lin; W.-J. Lee; T. Quertermous; J. D. Curb; I. Chen; B. L. Rodriguez; C. A. Hsiung (Human Genetics, 2010)

Declining drug resistance of Mycobacterium tuberculosis isolates from elderly patients in Taiwan, 2000–2008 - W.-L. Liu; C.-C. Lai; C.-K. Tan; S.-H. Lin; Y.-T. Huang; C.-H. Liao; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Mycorrhizal specificity, preference, and plasticity of six slipper orchids from South Western China - Li Yuan; Zhu L. Yang; Shu-Yun Li; Hong Hu; Jia-Lin Huang (Mycorrhiza, 2010)

Mitochondrial metabolic adaptation in right ventricular hypertrophy and failure - Lin Piao; Glenn Marsboom; Stephen L. Archer (Journal of Molecular Medicine, 2010)

Ecological Restoration of Polluted Plain Rivers Within the Haihe River Basin in China - W. Wang; X. Q. Tang; S. L. Huang; S. H. Zhang; C. Lin; D. W. Liu; H. J. Che; Q. Yang; Miklas Scholz (Water, Air, & Soil Pollution, 2010)

Using hyperspectral remote sensing to estimate chlorophyll‐ a and phycocyanin in a mesotrophic reservoir - Lin Li; Rebecca E. Sengpiel; Denise L. Pascual; Lenore P. Tedesco; Jeffrey S. Wilson; Emmanuel Soyeux (International Journal of Remote Sensing, 2010)

Planning for Implementation of Riparian Buffers in the Feitsui Reservoir Watershed - Chia-Ling Chang; Tsung-Hung Hsu; Yunn-Jiin Wang; Jen-Yang Lin; Shaw L. Yu (Water Resources Management, 2010)

Genetic analysis and characterization of a new maize association mapping panel for quantitative trait loci dissection - Xiaohong Yang; Jianbing Yan; Trushar Shah; Marilyn L. Warburton; Qing Li; Lin Li; Yufeng Gao; Yuchao Chai; Zhiyuan Fu; Yi Zhou; Shutu Xu; Guanghong Bai; et al. (Theoretical and Applied Genetics, 2010)

Determining the subjective effects of TFMPP in human males - Reem K. Jan; Joanne C. Lin; HeeSeung Lee; Janie L. Sheridan; Rob R. Kydd; Ian J. Kirk; Bruce R. Russell (Psychopharmacology, 2010)

Clinical and microbiological characteristics of community-acquired thoracic empyema or complicated parapneumonic effusion caused by Klebsiella pneumoniae in Taiwan - Y.-T. Lin; T.-L. Chen; L. K. Siu; S.-F. Hsu; C.-P. Fung (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Hypoxia increases Sca-1/CD44 co-expression in murine mesenchymal stem cells and enhances their adipogenic differentiation potential - M. G. Valorani; A. Germani; W. R. Otto; L. Harper; A. Biddle; C. P. Khoo; W. R. Lin; M. I. Hawa; P. Tropel; M. P. Patrizi; P. Pozzilli; M. R. Alison (Cell and Tissue Research, 2010)

Combined Method for Reduction of High Frequency Interferences in Surface Electroenterogram (EEnG) - Y. Ye-Lin; J. Garcia-Casado; G. Prats-Boluda; J. L. Martinez-de-Juan (Annals of Biomedical Engineering, 2010)

Optimization of product line design for environmentally conscious technologies in notebook industry - K. H. Lin; L. H. Shih; S. C. Lee (International Journal of Environmental Science and Technology, 2010)

Genetic variation in sex-steroid receptors and synthesizing enzymes and colorectal cancer risk in women - Jennifer Lin; Robert Y. L. Zee; Kuang-Yu Liu; Shumin M. Zhang; I-Min Lee; JoAnn E. Manson; Edward Giovannucci; Julie E. Buring; Nancy R. Cook (Cancer Causes & Control, 2010)

Antibacterial effect of electrolysed acid water on the nasal discharge from patients with chronic rhinosinusitis - R.-S. Jiang; S.-H. Wu; K.-L. Liang; J.-F. Lin; M.-C. Su; W.-K. Chen; F.-J. Lu (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Clinical and genotypic characteristics of extensively drug-resistant and multidrug-resistant tuberculosis - C. C. Lai; C. K. Tan; S. H. Lin; C. H. Liao; Y. T. Huang; C. H. Chou; H. L. Hsu; C. Y. Wang; H. I. Lin; P. R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Comparison of approaches for efficient gene silencing induced by microRNA-based short hairpin RNA and indicator gene expression - Z. X. Shan; Q. X. Lin; C. Y. Deng; Z. L. Zhou; H. H. Tan; Y. H. Fu; X. H. Li; J. N. Zhu; L. P. Mai; S. J. Kuang; S. G. Lin; X. Y. Yu (Molecular Biology Reports, 2010)

In vitro activities of doripenem and other carbapenems against clinically important bacteria isolated in intensive care units: nationwide data from the SMART Programme - S.-S. Jean; P.-R. Hsueh; W.-S. Lee; H.-T. Chang; M.-Y. Chou; I.-S. Chen; J.-H. Wang; C.-F. Lin; J.-M. Shyr; W.-C. Ko; J.-J. Wu; Y.-C. Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

A storm event-based approach to TMDL development - Tsung-Hung Hsu; Jen-Yang Lin; Tsu-Chuan Lee; Harry X. Zhang; Shaw L. Yu (Environmental Monitoring and Assessment, 2010)

Longitudinal associations of blood markers of insulin and glucose metabolism and cancer mortality in the third National Health and Nutrition Examination Survey - Niyati Parekh; Yong Lin; Richard B. Hayes; Jeanine B. Albu; Grace L. Lu-Yao (Cancer Causes & Control, 2010)

Immunoglobulin heavy chain diversity in Pteropid bats: evidence for a diverse and highly specific antigen binding repertoire - Michelle L. Baker; Mary Tachedjian; Lin-Fa Wang (Immunogenetics, 2010)

Locomotor performance in an invasive species: cane toads from the invasion front have greater endurance, but not speed, compared to conspecifics from a long-colonised area - John Llewelyn; Benjamin L. Phillips; Ross A. Alford; Lin Schwarzkopf; Richard Shine (Oecologia, 2010)

Rejecting strictly allopatric speciation on a continental island: prolonged postdivergence gene flow between Taiwan ( Leucodioptron taewanus , Passeriformes Timaliidae) and Chinese ( L. canorum canorum ) hwameis - JING-WEN LI; CAROL K. L. YEUNG; PI-WEN TSAI; RONG-CHIEN LIN; CHIA-FEN YEH; CHENG-TE YAO; LIANXIAN HAN; LE MANH HUNG; PING DING; QISHAN WANG; SHOU-HSIEN LI (Molecular Ecology, 2010)

Establishment, characterization, virus susceptibility and transfection of cell lines from cobia, Rachycentron canadum (L.), brain and fin - T‐C Cheng; Y‐S Lai; I‐Y Lin; C‐P Wu; S‐L Chang; T‐I Chen; M‐S Su (Journal of Fish Diseases, 2010)
Establishment and characterization of two cobia, Rachycentron canadum, cell lines derived from cobia brain (CB) and cobia fin (CF) are described. Caudal fin and brain from juvenile cobia were dissociated for 30 and 10 min, respectively, in phosphate‐buffered saline containing 0.25% trypsin at 25 °C. The optimal culture condition for both dissociated cells (primary cell culture) was at 28 °C in Leibovitz‐15 medium containing 10% foetal bovine serum. The cells have been sub‐cultured at a ratio of 1:2 for more than 160 passages over a period of 3 years. Origin of the cultured cells was verified by comparison of their sequences of mitochondrial cytochrome oxidase subunit I genes ( cox I ) with the cox 1 sequence from cobia muscle tissue. The cell lines showed polyploidy. No mycoplasma contamination was detected. Susceptibility to grouper iridovirus was observed for the CB cell line but not the CF cell line. Both cell lines expressed green fluorescent protein after being transfected with green fluorescent reporter gene driven by the cytomegalovirus promoter.

Seroprevalence of Toxoplasma gondii infection in breeding sows in Western Fujian Province, China - C. Q. Huang; Y. Y. Lin; A. L. Dai; X. H. Li; X. Y. Yang; Z. G. Yuan; X. Q. Zhu (Tropical Animal Health and Production, 2010)

The inhibition of pyruvate dehydrogenase kinase improves impaired cardiac function and electrical remodeling in two models of right ventricular hypertrophy: resuscitating the hibernating right ventricle - Lin Piao; Yong-Hu Fang; Virgilio J. J. Cadete; Christian Wietholt; Dalia Urboniene; Peter T. Toth; Glenn Marsboom; Hannah J. Zhang; Idith Haber; Jalees Rehman; Gary D. Lopaschuk; Stephen L. Archer (Journal of Molecular Medicine, 2010)

Effect of the climate shift around mid 1970s on the relationship between wintertime Ural blocking circulation and East Asian climate - Lin Wang; Wen Chen; Wen Zhou; Johnny C. L. Chan; David Barriopedro; Ronghui Huang (International Journal of Climatology, 2010)
Blocking variability over the Ural Mountain region in the boreal winter and its relationship with the East Asian winter climate is investigated. The climate shift around mid 1970s has been shown to exert a significant influence on the blocking pattern. In contrast with the years before 1976/1977, the Ural blocking signal after 1976/1977 is found to propagate less into the stratosphere and more eastward in the troposphere to East Asia, which therefore exerts more influence on the East Asian winter climate. This enhanced Ural blocking–East Asian climate relationship amplifies the impact of Ural blocking on East Asia and, with the background of decreasing Ural blocking, contributes to the higher frequency of warm winters in this region. Further analyses suggest that the NAM‐related stratospheric polar vortex strength and its modulation on the propagation of atmospheric stationary waves can account for this change, with the key area being located in the North Atlantic region. Copyright © 2009 Royal Meteorological Society

Cocaine craving and use during daily life - Kenzie L. Preston; Massoud Vahabzadeh; John Schmittner; Jia-Ling Lin; David A. Gorelick; David H. Epstein (Psychopharmacology, 2009)

Modulation of prostate cancer cell gene expression by cell-to-cell contact with bone marrow stromal cells or osteoblasts - Shuming Zhang; Jun Wang; Mehmet A. Bilen; Sue-Hwa Lin; Samuel I. Stupp; Robert L. Satcher (Clinical & Experimental Metastasis, 2009)

Application and development of a decision-support system for assessing water shortage and allocation with climate change - Tzu-Ming Liu; C. P. Tung; K. Y. Ke; L. H. Chuang; C. Y. Lin (Paddy and Water Environment, 2009)

Do otolith annular structures correspond to the first freshwater entry for yellow European eels Anguilla anguilla in the Baltic countries? - Y.‐J. Lin; J.‐C. Shiao; L. Ložys; M. Plikšs; A. Minde; Y. Iizuka; I. Rašals; W.‐N. Tzeng (Journal of Fish Biology, 2009)
To examine the relationship between freshwater entry and otolith annular structures, a total of 113 naturally recruited European eels Anguilla anguilla from Lithuania and Latvia that entered fresh water at least once were collected. In some individuals (8·3–11·3%), the first freshwater entry coincided with a dark check that was distinctly different from neighbouring annuli. In most individuals (81·7–84·9%), the first freshwater entry occurred on rings and increments indistinguishable from other annuli. For the remaining individuals (3·8–10%), the first freshwater entry did not correspond to any otolith ring, band or annulus. According to recent evidence, the observed high correspondence between the first freshwater entry and otolith annuli was more likely due to the movement into fresh water during winter when the annulus was deposited, rather than stress resulting from habitat change. Consequently, the age estimation based on otoliths might be less influenced by this habitat change during the yellow eel stage.

Emissions of 2,2,4-Trimethyl-1,3-Pentanediol Monoisobutyrate (TMPD-MIB) from Latex Paint: A Critical Review - RICHARD L. CORSI; CHI-CHI LIN (Critical Reviews in Environmental Science and Technology, 2009)

Transpositional activation of mPing in an asymmetric nuclear somatic cell hybrid of rice and Zizania latifolia was accompanied by massive element loss - X. H. Shan; X. F. Ou; Z. L. Liu; Y. Z. Dong; X. Y. Lin; X. W. Li; B. Liu (Theoretical and Applied Genetics, 2009)

Application of integrated GIS and multimedia modeling on NPS pollution evaluation - C. E. Lin; C. M. Kao; Y. C. Lai; W. L. Shan; C. Y. Wu (Environmental Monitoring and Assessment, 2009)

Molecular characterization of two potato virus S isolates from late-blight-resistant genotypes of potato (Solanum tuberosum) - Y. H. Lin; K. L. Druffel; J. Whitworth; M. J. Pavek; Hanu R. Pappu (Archives of Virology, 2009)

Identification of three immunodominant regions on leukotoxin protein of Fusobacterium necrophorum - D. B. Sun; R. Wu; G. L. Li; J. S. Zheng; X. P. Liu; Y. C. Lin; D. H. Guo (Veterinary Research Communications, 2009)

Effects of grape xylem sap and cell wall constituents on in vitro growth, biofilm formation and cellular aggregation of Xylella fastidiosa - Davis W. Cheng; Hong Lin; M. Andrew Walker; Drake C. Stenger; Edwin L. Civerolo (European Journal of Plant Pathology, 2009)

Reproductive isolation between two sympatric simultaneous hermaphroditic shrimp, Lysmata wurdemanni and L. boggessi - Dong Zhang; Junda Lin; Jörg D. Hardege; Andrew L. Rhyne (Marine Biology Research, 2009)

A Two-Step Infinite α-Cuts Fuzzy Linear Programming Method in Determination of Optimal Allocation Strategies in Agricultural Irrigation Systems - H. W. Lu; G. H. Huang; Y. P. Lin; L. He (Water Resources Management, 2009)

Effect of polymorphism in the leukemia inhibitory factor gene on litter size in Large White pigs - H. C. Lin; G. F. Liu; A. G. Wang; L. J. Kong; X. F. Wang; J. L. Fu (Molecular Biology Reports, 2009)

Nationwide surveillance of antimicrobial resistance among Haemophilus influenzae and Streptococcus pneumoniae in intensive care units in Taiwan - S.-S. Jean; P.-R. Hsueh; W.-S. Lee; H.-T. Chang; M.-Y. Chou; I.-S. Chen; J.-H. Wang; C.-F. Lin; J.-M. Shyr; W.-C. Ko; J.-J. Wu; Y.-C. Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Variability of total and available copper concentrations in relation to land use and soil properties in Yangtze River Delta of China - Xiuying Zhang; Fenfang Lin; Yugen Jiang; Ke Wang; X. L. Feng (Environmental Monitoring and Assessment, 2009)

Study on the Relationship Between Meteorological Conditions and Acid Rain in Mid-Eastern Fujian - C. C. Lin; J. X. Liu; Y. Y. Cai; B. L. Li; Z. L. Wang; B. B. Chen (Bulletin of Environmental Contamination and Toxicology, 2009)

Relationship between cardiopulmonary mortality and cancer risk and quantitative exposure to polycyclic aromatic hydrocarbons, fluorides, and dust in two prebake aluminum smelters - Melissa C. Friesen; Geza Benke; Anthony Del Monaco; Martine Dennekamp; Lin Fritschi; Nick de Klerk; Jan L. Hoving; Ewan MacFarlane; Malcolm R. Sim (Cancer Causes & Control, 2009)

Identification of soil heavy metal sources from anthropogenic activities and pollution assessment of Fuyang County, China - X. Y. Zhang; F. F. Lin; Mike T. F. Wong; X. L. Feng; K. Wang (Environmental Monitoring and Assessment, 2009)

The Impact of Iodine Excess on Thyroid Hormone Biosynthesis and Metabolism in Rats - K. Wang; Y. N. Sun; J. Y. Liu; L. Zhang; Y. Ye; L. X. Lin; Y. Q. Yan; Z. P. Chen (Biological Trace Element Research, 2009)

Acute effects of localized muscle fatigue on postural control and patterns of recovery during upright stance: influence of fatigue location and age - Dingding Lin; Maury A. Nussbaum; Hyang Seol; Navrag B. Singh; Michael L. Madigan; Laura A. Wojcik (European Journal of Applied Physiology, 2009)

Impact of socioeconomic status on cancer incidence and stage at diagnosis: selected findings from the surveillance, epidemiology, and end results: National Longitudinal Mortality Study - Limin X. Clegg; Marsha E. Reichman; Barry A. Miller; Benjamin F. Hankey; Gopal K. Singh; Yi Dan Lin; Marc T. Goodman; Charles F. Lynch; Stephen M. Schwartz; Vivien W. Chen; Leslie Bernstein; Scarlett L. Gomez; et al. (Cancer Causes & Control, 2009)

Acid sensing ion channel (ASIC) inhibitors exhibit anxiolytic-like activity in preclinical pharmacological models - Jason M. Dwyer; Stacey J. Sukoff Rizzo; Sarah J. Neal; Qian Lin; Flora Jow; Robert L. Arias; Sharon Rosenzweig-Lipson; John Dunlop; Chad E. Beyer (Psychopharmacology, 2009)

A quick and efficient approach for gene silencing by using triple putative microRNA-based short hairpin RNAs - Z. X. Shan; Q. X. Lin; M. Yang; C. Y. Deng; S. J. Kuang; Z. L. Zhou; D. Z. Xiao; X. Y. Liu; S. G. Lin; X. Y. Yu (Molecular and Cellular Biochemistry, 2009)

Synthesis and evaluation of lanthanide ion DOTA–tetraamide complexes bearing peripheral hydroxyl groups - Azhar Pasha; Mai Lin; Gyula Tircsó; Cynthia L. Rostollan; Mark Woods; Garry E. Kiefer; A. Dean Sherry; Xiankai Sun (JBIC Journal of Biological Inorganic Chemistry, 2009)

Nationwide surveillance of antimicrobial resistance among Enterobacteriaceae in intensive care units in Taiwan - S.-S. Jean; P.-R. Hsueh; W.-S. Lee; H.-T. Chang; M.-Y. Chou; I.-S. Chen; J.-H. Wang; C.-F. Lin; J.-M. Shyr; W.-C. Ko; J.-J. Wu; Y.-C. Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

The impact of chemical lateral boundary conditions on CMAQ predictions of tropospheric ozone over the continental United States - Youhua Tang; Pius Lee; Marina Tsidulko; Ho-Chun Huang; Jeffery T. McQueen; Geoffrey J. DiMego; Louisa K. Emmons; Robert B. Pierce; Anne M. Thompson; Hsin-Mu Lin; Daiwen Kang; Daniel Tong; et al. (Environmental Fluid Mechanics, 2009)

Group A streptococcal infection caused by emm1 strains among children in southern Taiwan - H.-C. Lin; S.-M. Wang; Y.-L. Lin; Y.-S. Lin; J.-J. Wu; W.-J. Chuang; M. T. Lin; C.-C. Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Mapping chromosomal regions affecting flowering time in a spring wheat RIL population - F. Lin; S. L. Xue; D. G. Tian; C. J. Li; Y. Cao; Z. Z. Zhang; C. Q. Zhang; Z. Q. Ma (Euphytica, 2008)

Identification of wheat line YW243 on comprehensive resistance to several diseases by pathogens and molecular markers - H. Xie; Z. Lin; Z. Zhang; L. Du; Z. Xin; Y. Ma; X. Ye; X. Chen (Cereal Research Communications, 2008)

A role for planar cell polarity signaling in angiogenesis - Pasquale Cirone; Shengda Lin; Hilary L. Griesbach; Yi Zhang; Diane C. Slusarski; Craig M. Crews (Angiogenesis, 2008)

Drastic post‐LGM expansion and lack of historical genetic structure of a subtropical fig‐pollinating wasp ( Ceratosolen sp. 1) of Ficus septica in Taiwan - RONG‐CHIEN LIN; CAROL K‐L. YEUNG; SHOU‐HSIEN LI (Molecular Ecology, 2008)
The climatic oscillations of the last glacial period have had profound influences on the demography and levels of genetic diversity of extant species. Molecular evidence of glacial effects on temperate species has been well documented, whereas little is known regarding that on subtropical species. Here we present analyses based on partial sequences of the mitochondrial cytochrome c oxidase subunit I ( COI ) gene (1052 bp) and genotypes at 15 microsatellite loci to investigate the historical demography, population structure and ongoing gene flow of an undescribed fig‐pollinating wasp ( Ceratosolen sp. 1) of Ficus septica in subtropical Taiwan. Reconstructed historical demography based on the coalescent tree of COI sequences suggests that C . sp. 1 has undergone a drastic population expansion which was tightly coupled with climatic changes since the last glacial maximum (LGM). The magnitude of the population size change was approximately 500‐fold, indicating that the population of this wasp and its host was likely highly compressed during the last glacial period. The lack of significant population differentiation ( F ST F ST values) may be due to rapid postglacial expansion facilitated by long‐distance dispersal, although a low frequency of first‐generation migrants was detected. Our results clearly demonstrate how recent climatic changes since the LGM and dispersal ability have jointly shaped the genetic composition of a subtropical fig‐pollinating wasp.

Contrasting patterns of morphological and neutral genetic divergence among geographically proximate populations of sockeye salmon Oncorhynchus nerka in Lake Aleknagik, Alaska - J. Lin; E. Ziegler; T. P. Quinn; L. Hauser (Journal of Fish Biology, 2008)
Levels of differentiation in morphological traits (age at maturity, body length at age, egg mass and body depth) and spawning time were examined in sockeye salmon Oncorhynchus nerka from three geographically proximate but physically distinct creeks in Lake Aleknagik, Alaska. Happy Creek fish had significantly greater values for most measured morphological traits, and Eagle Creek fish spawned significantly later than fish in the other creeks. Phenotypic differentiation between creeks, measured as P ST , was then compared with microsatellite marker differentiation between creeks, measured as F ST . No correlations were apparent between P ST and F ST values, and P ST values were generally significantly larger than zero ( P ST = 0·0018–0·31) whereas F ST values were not ( F ST =−0·0004 to 0·0016). The insignificant pair‐wise F ST values between creek samples indicated that gene flow occurs between creeks, assuming the creek populations have reached migration–drift equilibrium. However, the strong homing behaviour of sockeye salmon precludes a scenario in which fish from the three creeks constitute a single population that segregates by body size. Rather, significant phenotypic differentiation suggests that strong divergent selection occurs on the phenotypic traits despite the homogenizing effects of gene flow.

The development of extremely dry surface air due to vertical exchanges under the exit region of a jet streak - Michael L. Kaplan; C. Huang; Y.-L. Lin; J. J. Charney (Meteorology and Atmospheric Physics, 2008)

Global decomposition experiment shows soil animal impacts on decomposition are climate‐dependent - DIANA H. WALL; MARK A. BRADFORD; MARK G. ST. JOHN; JOHN A. TROFYMOW; VALERIE BEHAN‐PELLETIER; DAVID E. BIGNELL; J. MARK DANGERFIELD; WILLIAM J. PARTON; JOSEF RUSEK; WINFRIED VOIGT; VOLKMAR WOLTERS; HOLLEY ZADEH GARDEL; et al. (Global Change Biology, 2008)
Climate and litter quality are primary drivers of terrestrial decomposition and, based on evidence from multisite experiments at regional and global scales, are universally factored into global decomposition models. In contrast, soil animals are considered key regulators of decomposition at local scales but their role at larger scales is unresolved. Soil animals are consequently excluded from global models of organic mineralization processes. Incomplete assessment of the roles of soil animals stems from the difficulties of manipulating invertebrate animals experimentally across large geographic gradients. This is compounded by deficient or inconsistent taxonomy. We report a global decomposition experiment to assess the importance of soil animals in C mineralization, in which a common grass litter substrate was exposed to natural decomposition in either control or reduced animal treatments across 30 sites distributed from 43°S to 68°N on six continents. Animals in the mesofaunal size range were recovered from the litter by Tullgren extraction and identified to common specifications, mostly at the ordinal level. The design of the trials enabled faunal contribution to be evaluated against abiotic parameters between sites. Soil animals increase decomposition rates in temperate and wet tropical climates, but have neutral effects where temperature or moisture constrain biological activity. Our findings highlight that faunal influences on decomposition are dependent on prevailing climatic conditions. We conclude that (1) inclusion of soil animals will improve the predictive capabilities of region‐ or biome‐scale decomposition models, (2) soil animal influences on decomposition are important at the regional scale when attempting to predict global change scenarios, and (3) the statistical relationship between decomposition rates and climate, at the global scale, is robust against changes in soil faunal abundance and diversity.

Utility of Microsatellite Markers and Amplified Fragment Length Polymorphism in the Study of Potentially Ochratoxigenic Black Aspergilli - Alexandre Esteban; Su-lin L. Leong; Ailsa D. Hocking; M. Lourdes Abarca; F. Javier Cabañes; Nai Tran-Dinh (Current Microbiology, 2008)

Cloning and infection response of tumour‐necrosis factor alpha in large yellow croaker Pseudosciaena crocea (Richardson) - F. J. Xie; Z. P. Zhang; P Lin; S. H Wang; Z. H Zou; Y. L. Wang (Journal of Fish Biology, 2008)
In this article, reverse transcriptase polymerase chain reaction (RT‐PCR) and real‐time PCR were used to clone the tumour‐necrosis factor alpha (TNF‐α) gene of the large yellow croaker Pseudosciaena crocea (Richardson) and to analyse its response to bacterial infection. The full‐length cDNA of TNF‐α contained a 5′‐untranslated region (5′‐UTR) of 68 bp, followed by an open reading frame (ORF) of 759 bp and a 3′‐UTR of 512 bp. The ORF was capable of encoding 252 amino acids with an estimated molecular mass of 28 kDa. In the 3′‐UTR, there were two putative endotoxin‐responsive motifs and five mRNA instability motifs. The deduced peptide had a transmembrane domain and a TNF‐α family signature. Multiple sequence alignments indicated that P. crocea TNF‐α shares relatively high similarity with both teleost and mammalian TNF‐α. Phylogenetic analysis showed that teleost TNF‐α was located independently in a different branch compared with mammalian TNF‐α. Real‐time PCR analysis demonstrated that the expression of TNF‐α in the head kidney of the P. crocea injected with Vibrio parahaemolyticus was most significantly higher than that of the control group at 2 and 4 days. In blood, at 2 days post‐injection, TNF‐α expression was significantly higher than that of the control group, while at 4 days post‐injection, it was most significantly higher than that of the control group.

The influence of mesoscale mountains on vortex tracks: shallow-water modeling study - C.-Y. Huang; Y.-L. Lin (Meteorology and Atmospheric Physics, 2008)

Note: Anti-viral activity ofAilanthus altissima crude extract onRice stripe virus in rice suspension cells - J. G. Yang; Y. G. Dang; G. Y. Li; L. J. Guo; W. T. Wang; Q. W. Tan; Q. Y. Lin; Z. J. Wu; L. H. Xie (Phytoparasitica, 2008)

Selective Contrast Enhancement of Individual Alzheimer’s Disease Amyloid Plaques Using a Polyamine and Gd-DOTA Conjugated Antibody Fragment Against Fibrillar Aβ42 for Magnetic Resonance Molecular Imaging - Muthu Ramakrishnan; Thomas M. Wengenack; Karunya K. Kandimalla; Geoffry L. Curran; Emily J. Gilles; Marina Ramirez-Alvarado; Joseph Lin; Michael Garwood; Clifford R. Jack Jr.; Joseph F. Poduslo (Pharmaceutical Research, 2008)

DC-SIGN and L-SIGN: the SIGNs for infection - Ui-Soon Khoo; Kelvin Y. K. Chan; Vera S. F. Chan; C. L. Steve Lin (Journal of Molecular Medicine, 2008)

Characterization of novel microsatellite loci in the great leaf-nosed bat, Hipposideros armiger and cross-amplification in other related species - T. T. Guo; P. Y. Hua; L. K. Lin; S. Y. Zhang (Conservation Genetics, 2008)

Loss of apical monocilia on collecting duct principal cells impairs ATP secretion across the apical cell surface and ATP-dependent and flow-induced calcium signals - Michael B. Hovater; Dragos Olteanu; Elizabeth L. Hanson; Nai-Lin Cheng; Brian Siroky; Attila Fintha; Peter Komlosi; Wen Liu; Lisa M. Satlin; P. Darwin Bell; Bradley K. Yoder; Erik M. Schwiebert (Purinergic Signalling, 2008)

5-Hydroxymethyl-2-furfural, a clinical trials agent for sickle cell anemia, and its mono/di-glucosides from classically processed steamed Rehmanniae Radix - An-Shen Lin; Keduo Qian; Yoshihide Usami; Li Lin; Hideji Itokawa; Charleson Hsu; Susan L. Morris-Natschke; Kuo-Hsiung Lee (Journal of Natural Medicines, 2008)

Ethmoid sinus mycology of chronic rhinosinusitis - R. S. Jiang; K. L. Liang; J. Y. Shiao; J. F. Lin; M. C. Su; C. H. Hsin; F. J. Lu (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Multiple-Point Simulations Constrained by Continuous Auxiliary Data - Tatiana L. Chugunova; Lin Y. Hu (Mathematical Geosciences, 2008)

Using FANP approach on selection of competitive priorities based on cleaner production implementation: a case study in PCB manufacturer, Taiwan - M. L. Tseng; Y. H. Lin; A. S. F. Chiu; J. C. H. Liao (Clean Technologies and Environmental Policy, 2008)

Cigarette smoking and prostate cancer-specific mortality following diagnosis in middle-aged men - Zhihong Gong; Ilir Agalliu; Daniel W. Lin; Janet L. Stanford; Alan R. Kristal (Cancer Causes & Control, 2008)

Automatic relative radiometric normalization using iteratively weighted least square regression - L. Zhang; L. Yang; H. Lin; Mingsheng Liao (International Journal of Remote Sensing, 2008)

Growth differences between naturally recruited and stocked European eel Anguilla anguilla from different habitats in Lithuania - Y.‐J. Lin; L. Ložys; J.‐C. Shiao; Y. Iizuka; W.‐N. Tzeng (Journal of Fish Biology, 2007)
European eels Anguilla anguilla from freshwater lakes in Lithuania had slower growth rates and lower backcalculated total lengths ( L T ) than those from lagoons and coastal waters, but no significant differences were found among fish with different migratory histories or between naturally recruited and stocked fish except a higher L T at age of stocked European eels at ages 5 to 8 years. The asymptotic L T did not differ among habitats or migratory histories, but the stocked eels in the lakes had smaller K (coefficient from the von Bertalanffy growth function) than did the both naturally recruited and stocked eels in the lagoon and coastal waters. The growth rate of European eels in Lithuania might be influenced mainly by different habitats rather than different migratory histories and stocking. The lower L T at age of naturally recruited fish at ages 5–8 years compared to stocked fish might result from the extra energy costs entailed in migration from the Atlantic and across the Baltic Sea.

Experiences of water transfer from the agricultural to the non-agricultural sector in Taiwan - C. C. Huang; M. H. Tsai; W. T. Lin; Y. F. Ho; C. H. Tan; Y. L. Sung (Paddy and Water Environment, 2007)

Fracture network characteristics of a deep borehole in the Table Mountain Group (TMG), South Africa - L. Lin; H. Jia; Y. Xu (Hydrogeology Journal, 2007)

Activation of p53 by Dishevelled independent of Wnt or planar polarity pathways - Vivianne W. Ding; Li-Ping Lin; Andrew L. Chiang; Frank McCormick (Journal of Molecular Medicine, 2007)

Prostate cancer mortality in relation to screening by prostate-specific antigen testing and digital rectal examination: a population-based study in middle-aged men - Ilir Agalliu; Noel S. Weiss; Daniel W. Lin; Janet L. Stanford (Cancer Causes & Control, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Rapid Evolution, Genetic Variations, and Functional Association of the Human Spermatogenesis-Related Gene NYD-SP12 - Qü Zhang; Feng Zhang; Xiao-hua Chen; Yin-qiu Wang; Wei-qi Wang; Alice A. Lin; Luca L. Cavalli-Sforza; Li Jin; Ran Huo; Jia-hao Sha; Zheng Li; Bing Su (Journal of Molecular Evolution, 2007)

Image processing of FORMOSAT‐2 data for monitoring the South Asia tsunami - C.‐C. Liu; J.‐G. Liu; C.‐W. Lin; A.‐M. Wu; S.‐H. Liu; C.‐L. Shieh (International Journal of Remote Sensing, 2007)

Ganoderma lucidum polysaccharide peptide reduced the production of proinflammatory cytokines in activated rheumatoid synovial fibroblast - Y. W. Ho; J. S. L. Yeung; P. K. Y. Chiu; W. M. Tang; Z. B. Lin; R. Y. K. Man; C. S. Lau (Molecular and Cellular Biochemistry, 2007)

Quantitative traits for the tail suspension test: automation, optimization, and BXD RI mapping - Heena V. Lad; Lin Liu; José L. Payá-Cano; Cathy Fernandes; Leonard C. Schalkwyk (Mammalian Genome, 2007)

Role of iNOS-derived reactive nitrogen species and resultant nitrative stress in leukocytes-induced cardiomyocyte apoptosis after myocardial ischemia/reperfusion - Xiao-Liang Wang; Hui-Rong Liu; Lin Tao; Feng Liang; Li Yan; Rong-Rui Zhao; Bernard L. Lopez; Theodore A. Christopher; Xin-Liang Ma (Apoptosis, 2007)

High expression of capsid protein of red‐spotted grouper nervous necrosis virus in an avian cell line requires viral RNA2 non‐coding regions - J N Huang; L Lin; S P Weng; J G He (Journal of Fish Diseases, 2007)

Endosperm-specific hypomethylation, and meiotic inheritance and variation of DNA methylation level and pattern in sorghum (Sorghum bicolor L.) inter-strain hybrids - M. S. Zhang; H. Y. Yan; N. Zhao; X. Y. Lin; J. S. Pang; K. Z. Xu; L. X. Liu; B. Liu (Theoretical and Applied Genetics, 2007)

Phosphorus Load Reduction Goals for Feitsui Reservoir Watershed, Taiwan - Wen-Shang Chou; Tsu-Chuan Lee; Jen-Yang Lin; Shaw L. Yu (Environmental Monitoring and Assessment, 2007)

A numerical study of the influence of urban expansion on monthly climate in dry autumn over the Pearl River Delta, China - W. S. Lin; C.-H. Sui; L. M. Yang; X. M. Wang; R. R. Deng; S. J. Fan; C. S. Wu; A. Y. Wang; S. K. Fong; H. Lin (Theoretical and Applied Climatology, 2007)

Apoptosis-dependent and -independent mechanisms mediate the phagocytic recognition/clearance of the HL60-A1 transfectants with prolonged survival - C.-L. Chou; L.-L. Chiang; C.-T. Yu; H.-C. Chen; K.-Y. Lee; S.-M. Lin; C.-D. Huang; W.-T. Liu; P.-C. Chou; C.-H. Wang; H.-C. Lin; H.-P. Kuo; et al. (Inflammation Research, 2007)

Quality of race, Hispanic ethnicity, and immigrant status in population-based cancer registry data: implications for health disparity studies - Limin X. Clegg; Marsha E. Reichman; Benjamin F. Hankey; Barry A. Miller; Yi D. Lin; Norman J. Johnson; Stephen M. Schwartz; Leslie Bernstein; Vivien W. Chen; Marc T. Goodman; Scarlett L. Gomez; John J. Graff; et al. (Cancer Causes & Control, 2007)

Mitochondrial DNA phylogeography of Glyptothorax fokiensis and Glyptothorax hainanensis in Asia - X.‐L. Chen; T.‐Y. Chiang; H.‐D. Lin; H.‐S. Zheng; K.‐T. Shao; Q. Zhang; K.‐C. Hsu (Journal of Fish Biology, 2007)
Whole mitochondrial DNA cytochrome b sequences in 62 fish from 13 locations in Southeast China identified two major clades corresponding to two allopatric taxa, Glyptothorax fokiensis fokiensis and Glyptothorax fokiensis hainanensis . Reciprocal monophyly and a molecular clock separation between these two taxa of 2·3 million years indicate these taxa should be elevated to species. Mismatch distributions and Fu’s F S statistic suggest that both G. fokiensis and G. hainanensis have experienced recent population expansions. Analysis of molecular variance indicates that most of the genetic variation resides among populations within both species, with Φ ST = 0·645 for G. fokiensis and 0·801 for G. hainanensis , suggesting restricted gene flow among populations. Significant correlations between the geographic and the genetic distances provide support for the importance of geographic isolations between populations. Nested clade analysis also confirms low levels of genetic exchanges between the two major groups and between populations within each group. The phylogeographical pattern among populations of Glyptothorax in East Asia can be attributed to historical fragmentations, demographic expansions and occasional long‐distance dispersals stimulated by tectonic activity and Ice Age climate changes.

The contents and forms of solid-phase species of radioactive strontium and cesium in Taiwan soils - S. W. Chang Chien; M. C. Wang; C. L. Chiu; Yu-Ming Lin; Shu-Ying Lai (Environmental Monitoring and Assessment, 2007)

Isolation of Endophytic Actinomycetes from Different Cultivars of Tomato and their Activities Against Ralstonia solanacearum in Vitro - H. M. Tan; L. X. Cao; Z. F. He; G. J. Su; B. Lin; S. N. Zhou (World Journal of Microbiology and Biotechnology, 2006)

Characterizing the severe turbulence environments associated with commercial aviation accidents. A real-time turbulence model (RTTM) designed for the operational prediction of hazardous aviation turbulence environments - M. L. Kaplan; J. J. Charney; K. T. Waight; K. M. Lux; J. D. Cetola; A. W. Huffman; A. J. Riordan; S. D. Slusser; M. T. Kiefer; P. S. Suffern; Y.-L. Lin (Meteorology and Atmospheric Physics, 2006)

Mechanical Response of a Calcified Plaque Model to Fluid Shear Force - Tiantian C. Lin; Yin Tintut; Althea Lyman; Wendy Mack; Linda L. Demer; Tzung K. Hsiai (Annals of Biomedical Engineering, 2006)

Phenotypic characterization of Bbs4 null mice reveals age-dependent penetrance and variable expressivity - Erica R. Eichers; Muhammad M. Abd-El-Barr; Richard Paylor; Richard Alan Lewis; Weimin Bi; Xiaodi Lin; Thomas P. Meehan; David W. Stockton; Samuel M. Wu; Elizabeth Lindsay; Monica J. Justice; Philip L. Beales; et al. (Human Genetics, 2006)

Novel polymorphic microsatellites for studying genetic diversity of red Asian arowanas - G. H. Yue; Z. Y. Zhu; G. Lin; L. C. Lo; F. Feng (Conservation Genetics, 2006)

Computational Simulations of the Human Magneto- and Electroenterogram - A. S. Lin; M. L. Buist; L. K. Cheng; N. P. Smith; A. J. Pullan (Annals of Biomedical Engineering, 2006)

Copper‐dependent iron transport in coastal and oceanic diatoms - Maria T. Maldonado; Andrew E. Allen; Joanne S. Chong; Kevin Lin; Dan Leus; Nataliya Karpenko; Shannon L. Harris (Limnology and Oceanography, 2006)
We investigated the presence of plasmalemma‐bound copper‐containing oxidases associated with the inducible iron (Fe) transport system in two diatoms of the genus Thalassiosira . Under Fe‐limiting conditions, Thalassiosira oceanica , an oceanic isolate, was able to enzymatically oxidize inorganic Fe(II) extracellularly. This oxidase activity was dependent on copper (Cu) availability and diminished by exposure to a multi‐Cu oxidase (MCO) inhibitor. The rates of Fe uptake from ferrioxamine B by Fe‐limited T. oceanica were also dependent on Cu availability in the growth media. The effects of Cu limitation on Fe(II) oxidation and Fe uptake from ferrioxamine B were partially reversed after a short exposure to a Cu addition, indicating that the putative oxidases contain Cu. Limited physiological experiments were also performed with the coastal diatom Thalassiosira pseudonana and provided some evidence for putative Cu‐containing oxidases in the high‐affinity Fe transport system of this isolate. To support these preliminary physiological data, we searched the newly available T. pseudonan a genome for a multi‐Cu‐containing oxidase gene and, using real‐time polymerase chain reaction (PCR), quantified its expression under various Fe and Cu levels. We identified a putative MCO gene with predicted transmembrane domains and found that transcription levels of this gene were significantly elevated in Fe‐limited cells relative to Fe‐replete cells. These data collectively suggest that putative MCOs are part of the inducible Fe transport system of Fe‐limited diatoms, which act to oxidize Fe(II) following reductive dissociation of Fe(III) from strong organic complexes.

Genome-based PCR Primers for Specific and Sensitive Detection and Quantification of Xylella fastidiosa - Marta Francis; Hong Lin; Juan Cabrera-La Rosa; Harshavardhan Doddapaneni; Edwin L. Civerolo (European Journal of Plant Pathology, 2006)

Isolation and Characterization of Two Phenol-Degrading Yeast Strains from Marine Sediment - Z. Hu; Y. R. Wu; B. K. Lin; K. Maskaoui; D. H. Zhuang; T. L. Zheng (Bulletin of Environmental Contamination and Toxicology, 2006)

Potential Volatile Organic Compound Exposure from Dry Process Photocopiers in Operation-Idle Mode - D.-J. Hsu; H.-L. Huang; H.-Y. Lin; T.-S. Lin (Bulletin of Environmental Contamination and Toxicology, 2006)

Enhancement of chemosensitivity toward peplomycin by calpastatin-stabilized NF-κB p65 in esophageal carcinoma cells: possible involvement of Fas/Fas-L synergism - T.-L. Liu; H. Shimada; T. Ochiai; T. Shiratori; S.-E. Lin; M. Kitagawa; K. Harigaya; M. Maki; M. Oka; T. Abe; M. Takiguchi; T. Hiwasa (Apoptosis, 2006)

Enhanced viability of a nervous necrosis virus‐infected stable cell line over‐expressing a fusion product of the zfBcl‐x L and green fluorescent protein genes - S‐P Chen; H‐L Yang; H‐Y Lin; M‐C Chen; J‐L Wu; J‐R Hong (Journal of Fish Diseases, 2006)
Nervous necrosis virus (NNV) infection induces host cell apoptosis by an ill‐understood process. We utilized a fusion between enhanced green fluorescent protein (EGFP) and the zfBcl‐x L gene in GL‐av cells to select for zfBcl‐x L stable cell lines and to assess the effectiveness of the anti‐apoptotic protein Bcl‐x L in circumventing NNV‐induced cell death. Stable EGFP and EGFP‐Bcl‐x L ‐expressing clones were obtained at high purity within 2.5–3 months. In the latter, the EGFP‐Bcl‐x L fusion protein (approximately 58.2 kDa, as ascertained by Western blot) was predominantly targeted to mitochondria. We assayed for apoptosis in red‐spotted grouper NNV Tainan no. 1 (RGNNV TN1)‐infected cells with terminal deoxynucleotidyl transferase (TdT)‐mediated end labelling (TUNEL) of DNA at different virus doses. NNV infection of NNV Bcl‐x L GL‐av cell line revealed a protective effect, with a decrease in TUNEL‐positive cells of 7%, 8% and 31.8% at 24, 48 and 72 h, respectively. In addition, RGNNV infection of the Bcl‐x L GL‐av cell line revealed a protective effect, with an enhanced viability of 3%, 40% and 73% at 24, 48, and 72 h, respectively. We conclude that NNV‐induced apoptotic cell death can be lessened in transgenic grouper fish cells.

Ancient paddy soils from the Neolithic age in China’s Yangtze River Delta - Z. H. Cao; J. L. Ding; Z. Y. Hu; H. Knicker; I. Kögel-Knabner; L. Z. Yang; R. Yin; X. G. Lin; Y. H. Dong (The Science of Nature, 2006)

Seismo-Geochemical Variations in SW Taiwan: Multi-Parameter Automatic Gas Monitoring Results - T. F. Yang; C.-C. Fu; V. Walia; C.-H. Chen; L. L. Chyi; T.-K. Liu; S.-R. Song; M. Lee; C.-W. Lin; C.-C. Lin (Pure and Applied Geophysics, 2006)

Detection and characterisation of a second potyvirus from Thunberg fritillary in China - J. Chen; H.-Y. Zheng; Y.-H. Shi; M. J. Adams; C.-B. Wei; L. Lin; J.-P. Chen (Archives of Virology, 2006)

Reference Values for Exposure to PAH Contaminants: Comparison of Fish from Ohio and Mid-Atlantic Streams - Susan M. Cormier; Edith L. C. Lin (Ecotoxicology, 2006)

Protoplast electrofusion between common wheat (Triticum aestivum L.) and Italian ryegrass (Lolium multiflorum Lam.) and regeneration of mature cybrids - T. M. Ge; X. H. Lin; F. L. Qin; S. W. Yu; Y. J. Yu (In Vitro Cellular & Developmental Biology - Plant, 2006)

The Complete Mitochondrial Genome Sequence and Characterization of Single-Nucleotide Polymorphisms in the Control Region of the Asian Seabass (Lates calcarifer) - G. Lin; L. C. Lo; Z. Y. Zhu; F. Feng; R. Chou; G. H. Yue (Marine Biotechnology, 2006)

Implicit solvent simulation models for biomembranes - Grace Brannigan; Lawrence C.-L. Lin; Frank L. H. Brown (European Biophysics Journal, 2006)

Use of a fluorescent membrane probe to identify zooxanthellae in hospite among dissociated endoderm cell culture from coral - C.-S. Chen; H.-P. Lin; C.-C. Yeh; L.-S. Fang (Protoplasma, 2005)

Nucleotide sequence and mRNA expression analysis of β-actin gene in the orange-spotted grouper Epinephelus coioides - W. M. Zhang; Y. Zhang; L. H. Zhang; S. G. Wang; T. Y. Zhu; D. Lin; G. Z. Ma (Fish Physiology and Biochemistry, 2005)

Potential Exposure to VOCs Caused by Dry Process Photocopiers: Results From a Chamber Study - D.-J. Hsu; H.-L. Huang; C.-H. Chien; T.-S. Lin (Bulletin of Environmental Contamination and Toxicology, 2005)

Genetic and physical mapping of Pi36(t), a novel rice blast resistance gene located on rice chromosome 8 - X. Q. Liu; L. Wang; S. Chen; F. Lin; Q. H. Pan (Molecular Genetics and Genomics, 2005)

Molecular Evolution of CXCR1, a G Protein-Coupled Receptor Involved in Signal Transduction of Neutrophils - Ying Liu; Su Yang; Alice A. Lin; Luca L. Cavalli-Sforza; Bing Su (Journal of Molecular Evolution, 2005)

Infectious bursal disease virus recovery from Vero cells transfected with RNA transcripts is enhanced by expression of the structural proteins in trans - M. A. Peters; T. L. Lin; C. C. Wu (Archives of Virology, 2005)

Characterisation of the welsh onion isolate of Shallot yellow stripe virus from China - J. Chen; C.-B. Wei; H.-Y. Zheng; Y.-H. Shi; M. J. Adams; L. Lin; Q.-Y. Zhang; S.-J. Wang; J.-P. Chen (Archives of Virology, 2005)

Isolation and characterization of actinomycetes antagonistic to pathogenic Vibrio spp. from nearshore marine sediments - J. L. You; L. X. Cao; G. F. Liu; S. N. Zhou; H. M. Tan; Y. C. Lin (World Journal of Microbiology and Biotechnology, 2005)

A new potyvirus from Thunberg fritillary (Fritillaria thunbergii Miq.) in Zhejiang, China - C.-B. Wei; J. Chen; Q.-Y. Zhang; Y.-H. Shi; L. Lin; H.-Y. Zheng; M. J. Adams; J.-P. Chen (Archives of Virology, 2005)

Thallium in Whole Blood Samples from College Students in Taiwan - T.-S. Lin; C.-L. Chang (Bulletin of Environmental Contamination and Toxicology, 2005)

Characterizing the severe turbulence environments associated with commercial aviation accidents. Part 1: A 44-case study synoptic observational analyses - M. L. Kaplan; A. W. Huffman; K. M. Lux; J. J. Charney; A. J. Riordan; Y.-L. Lin (Meteorology and Atmospheric Physics, 2005)

Characterizing the severe turbulence environments associated with commercial aviation accidents. Part 2: Hydrostatic mesoscale numerical simulations of supergradient wind flow and streamwise ageostrophic frontogenesis - M. L. Kaplan; A. W. Huffman; K. M. Lux; J. D. Cetola; J. J. Charney; A. J. Riordan; Y.-L. Lin; K. T. Waight (Meteorology and Atmospheric Physics, 2005)

Orographic effects on a conditionally unstable flow over an idealized three-dimensional mesoscale mountain - S.-H. Chen; Y.-L. Lin (Meteorology and Atmospheric Physics, 2005)

Histology and histochemical enzyme‐staining patterns of major immune organs in Epinephelus malabaricus - H.‐T. Lin; H.‐Y. Lin; H.‐L. Yang (Journal of Fish Biology, 2005)
The histological architecture of major immune organs in the Malabar grouper Epinephelus malabaricus was investigated. The novel characteristics such as melanomacrophage centres (MMCs) appeared in the thymus and lymphopoietic tissue formed as foci in the head kidney. Leukocyte distribution in organs was identified by enzyme histochemistry. β‐glucuronidase (BG) reactive cells in the cortex region of the thymus were botryoidally aggregated. Both acid phosphatase (AcP) and BG reactive cells concentrated within the specialized lymphopoietic foci in the head kidney, suggesting that the foci might be functional. Primitive histological characters of immunity were observed in the spleen. Although leukocyte aggregation was demonstrated in the spleen, additional enzyme histochemistry indicated that the aggregate might not be the equivalent of white pulp found in other vertebrates. The histological evidence did not support intestinal involvement in the immune system: there was no demonstrable gut associated lymphoid tissue. The limited distribution in the cortex and medulla boundary and the condensed format of the lymphocytes suggests a functional role for the MMC in the thymus of E. malabaricus . The MMC appearance in the thymus of a teleost was unusual.

Trace Elements in Cultured Tilapia (Oreochromis mossambicus): Results from a Farm in Southern Taiwan - T.-S. Lin; C.-S. Lin; C.-L. Chang (Bulletin of Environmental Contamination and Toxicology, 2005)

Further molecular characterisation of potyviruses infecting aroid plants for medicinal use in China - Y.-H. Shi; X.-Y. Hong; J. Chen; M. J. Adams; H.-Y. Zheng; L. Lin; B.-X. Qin; J.-P. Chen (Archives of Virology, 2005)

Infectious bursal disease virus polyprotein expression arrests growth and mitogenic stimulation of B lymphocytes - M. A. Peters; T. L. Lin; C. C. Wu (Archives of Virology, 2004)

Mapping QTL associated with resistance to Fusarium head blight in the Nanda2419נWangshuibai population. I. TypeII resistance - F. Lin; Z. X. Kong; H. L. Zhu; S. L. Xue; J. Z. Wu; D. G. Tian; J. B. Wei; C. Q. Zhang; Z. Q. Ma (Theoretical and Applied Genetics, 2004)

Whole Blood Vanadium in Taiwanese College Students - T.-S. Lin; C.-L. Chang; F.-M. Shen (Bulletin of Environmental Contamination and Toxicology, 2004)

Electron Transfer Dynamics in Rhodobacter sphaeroides Reaction Center Mutants with a Modified Ligand for the Monomer Bacteriochlorophyll on the Active Side - Evaldas Katilius; Jennie L. Babendure; Su Lin; Neal W. Woodbury (Photosynthesis Research, 2004)

Study on construction of cDNA libraries from rat normal liver and regeneration liver with smart technique - Lin Jun-Tang; Wang Cong-Rui; Jogenananda Pramanik; Zhang Hui-Yong; Feng Hui-Gen; Yang Bao-Sheng; L. I. Yu-Chang; Xu Cun-Shuan (Indian Journal of Clinical Biochemistry, 2004)

Acute Toxicity Assessment of 20 Herbicides to the Green Alga Scenedesmus quadricauda (Turp.) Breb. - J. Ma; F. Lin; S. Wang; L. Xu (Bulletin of Environmental Contamination and Toxicology, 2004)

A new potyvirus from tuberose ( Polianthes tuberosa ) in China - L. Lin; H.-Y. Zheng; J. Chen; J.-P. Chen; Q.-Y. Zhang; M.-F. Zhao; J. F. Antoniw; M. J. Adams (Archives of Virology, 2004)

Kinetic Studies on the Effects of Organophosphorus Pesticides on the Growth of Microcystis aeruginosa and Uptake of the Phosphorus Forms - P.-J. Zhou; H. Shen; J. Lin; L.-R. Song; Y.-D. Liu; Z.-B. Wu (Bulletin of Environmental Contamination and Toxicology, 2004)

Kinetic Studies on the Combined Effects of Lanthanum and Cerium on the Growth of Microcystis aeruginosa and their Accumulation by M. aeruginosa - P.-J. Zhou; J. Lin; H. Shen; T. Li; L.-R. Song; Y.-W. Shen; Y.-D. Liu (Bulletin of Environmental Contamination and Toxicology, 2004)

Pilot point temperature regulation for thermal lesion control during ultrasound thermal therapy - H. -L. Liu; Y. -Y. Chen; J. -Y. Yen; W. -L. Lin (Medical & Biological Engineering & Computing, 2004)

Elevated Exposure to Nitrogen Dioxide During Food Preparation: Results from a Cooking Laboratory - T.-S. Lin; Y.-L. Huang (Bulletin of Environmental Contamination and Toxicology, 2004)

Detection and classification of allexiviruses from garlic in China - J. Chen; H.-Y. Zheng; J. F. Antoniw; M. J. Adams; J.-P. Chen; L. Lin (Archives of Virology, 2004)

An operational heat/health warning system in shanghai - Jianguo Tan; L. S. Kalkstein; Jiaxin Huang; Songbai Lin; Hebao Yin; Demin Shao (International Journal of Biometeorology, 2004)

A novel missense mutation in the paired domain of PAX9 causes non-syndromic oligodontia - Dolrudee Jumlongras; Jenn-Yih Lin; Anas Chapra; Christine E. Seidman; Jonathan G. Seidman; Richard L. Maas; Bjorn R. Olsen (Human Genetics, 2004)

A virus related to Soybean mosaic virus from Pinellia ternata in China and its comparison with local soybean SMV isolates - J. Chen; H.-Y. Zheng; L. Lin; M. J. Adams; J. F. Antoniw; M.-F. Zhao; Y.-F. Shang; J.-P. Chen (Archives of Virology, 2004)

Causes of spatial patterns of dead trees in forest fragments in Illinois - Y. Lin; Melissa L. Hulting; Carol K. Augspurger (Plant Ecology, 2004)

Excavating Y-chromosome haplotype strata in Anatolia - Cengiz Cinnioglu; Roy King; Toomas Kivisild; Ersi Kalfoglu; Sevil Atasoy; Gianpiero L. Cavalleri; Anita S. Lillie; Charles C. Roseman; Alice A. Lin; Kristina Prince; Peter J. Oefner; Peidong Shen; et al. (Human Genetics, 2004)

Development of a Fragment Constant Method for Estimating the Mixture Toxicity - Z. Lin; L. Wang; P. Shi; D. Zhao; K. Yin (Archives of Environmental Contamination and Toxicology, 2004)

Application of a ?Big-Tree? model to regional climate modeling: a sensitivity study - X.-M. Zeng; M. Zhao; R.-C. Yu; N.-S. Lin; Y.-Q. Zheng; L.-J. Zhang; R.-J. Zhang (Theoretical and Applied Climatology, 2003)

QSARs for Predicting the Toxicity of Mixtures Containing Polar Narcotic Chemicals - Z. Lin; K. Yin; C. Wu; L. Wang; H. Yu (Bulletin of Environmental Contamination and Toxicology, 2003)

Occurrence and sequences of Lily mottle virus and Lily symptomless virus in plants grown from imported bulbs in Zhejiang province, China - H.-Y. Zheng; J. Chen; M.-F. Zhao; L. Lin; J.-P. Chen; J. F. Antoniw; M. J. Adams (Archives of Virology, 2003)

Cloning and characterization of leaf cDNAs that are differentially expressed between wheat hybrids and their parents - L. M. Wu; Z. F. Ni; F. R. Meng; Z. Lin; Q. X. Sun (Molecular Genetics and Genomics, 2003)

Surfactant proteinA and B genetic variants predispose to idiopathic pulmonary fibrosis - Moises Selman; Hung-Mo Lin; Martha Montao; Audrey L. Jenkins; Andrea Estrada; Zhenwu Lin; Guirong Wang; Susan L. DiAngelo; Xiaoxuan Guo; Todd M. Umstead; C. Max Lang; Annie Pardo; et al. (Human Genetics, 2003)

Small-angle X-ray scattering measurement of the internal microstructure of natural zircon crystals - A. P. Radlinski; J. Claou-Long; A. L. Hinde; E. Z. Radlinska; J.-S. Lin (Physics and Chemistry of Minerals, 2003)

Toxicity of 21 Herbicides to the Green Alga Scenedesmus quadricauda - J. Ma; F. Lin; S. Wang; L. Xu (Bulletin of Environmental Contamination and Toxicology, 2003)

Gene content and organization of an 85-kb DNA segment from the genome of the phytopathogenic mollicute Spiroplasma kunkelii - Y. Zhao; R. W. Hammond; R. Jomantiene; E. L. Dally; I.-M. Lee; H. Jia; H. Wu; S. Lin; P. Zhang; S. Kenton; F. Z. Najar; A. Hua; et al. (Molecular Genetics and Genomics, 2003)

General Toxicity Prediction Approach for Mixtures Containing Polar Narcotic Chemicals - Z. Lin; C. Wu; P. Shi; L. Wang; S. Gao (Bulletin of Environmental Contamination and Toxicology, 2003)

Detection ofBurkholderia pseudomallei in rice fields with PCR-based technique - C. M. Kao; S. C. Chen; Y. S. Chen; H. M. Lin; Y. L. Chen (Folia Microbiologica, 2003)

Photodegradation of Diesel Oil in Aqueous Solutions - P. Zhong; L. R. Kong; Z. F. Lin; G. M. Liu (Bulletin of Environmental Contamination and Toxicology, 2003)

Polychlorinated Biphenyls in Taiwanese Primipara Human Milk and Associated Factors - H.-R. Chao; S.-L. Wang; L.-Y. Lin; H.-Y. Yu; Y.-K. Lu; W.-L. Chou; Y.-L. Guo; L. W. Chang (Bulletin of Environmental Contamination and Toxicology, 2003)

Biotic communities of freshwater marshes and mangroves in relation to saltwater incursions: implications for wetland regulation - Hsing-Juh Lin; Kwang-Tsao Shao; Wen-Liang Chiou; Can-Jen W Maa; Hwey-Lian Hsieh; Wen-Lung Wu; Lucia L. Severinghaus; Yu-Tzu Wang (Biodiversity and Conservation, 2003)

Cancer incidence patterns in Koreans in the US and in Kangwha, South Korea - Scarlett Lin Gomez; Gem M. Le; Christina A. Clarke; Sally L. Glaser; Anne-Marie France; Dee W. West (Cancer Causes & Control, 2003)

Human infection by a swine influenza A (H1N1) virus in Switzerland - V. Gregory; M. Bennett; Y. Thomas; L. Kaiser; W. Wunderli; H. Matter; A. Hay; Y. P. Lin (Archives of Virology, 2003)

Trace Metals in Candle Smoke - T.-S. Lin; F.-M. Shen; J.-L. Chen; M.-H. Yang (Bulletin of Environmental Contamination and Toxicology, 2003)

Hibiscus protocatechuic acid inhibits lipopolysaccharide-induced rat hepatic damage - Lin W.-L.; Hsieh Y.-J.; Chou F.-P.; Wang C.-J.; Cheng M.-T.; Tseng T.-H. (Archives of Toxicology, 2003)

Effect of rice-glycerol complex medium on the production of lovastatin byMonascus ruber - Y. N. Chang; Y. C. Lin; C. C. Lee; B. L. Liu; Y. M. Tzeng (Folia Microbiologica, 2002)

Lactococcus garvieae , a cause of disease in grey mullet, Mugil cephalus L., in Taiwan - S‐C Chen; L‐L Liaw; H‐Y Su; S‐C Ko; C‐Y Wu; H‐C Chaung; Y‐H Tsai; K‐L Yang; Y‐C Chen; T‐H Chen; G‐R Lin; S‐Y Cheng; et al. (Journal of Fish Diseases, 2002)

Biological Monitoring of Environment Exposure to Safrole and the Taiwanese Betel Quid Chewing - M. J. W. Chang; C. Y. Ko; R. F. Lin; L. L. Hsieh (Archives of Environmental Contamination and Toxicology, 2002)

Specific detection ofPythium aphanidermatum from hydroponic nutrient solution by booster PCR with DNA primers developed from mitochondrial DNA - P. H. Wang; L. M. Boo; Y. S. Lin; Y. Yeh (Phytoparasitica, 2002)

Residential Water Supply as a Likely Cause of Community-Acquired Legionnaires' Disease in an Immunocompromised Host - Chen Y-S.; Lin W-R.; Liu Y-C.; Chang C-L.; Gan V-L.; Huang W-K.; Huang T-S.; Wann S-R.; Lin H-H.; Lee S.; Huang C-K.; Chin C.; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

Allelic and locus heterogeneity in autosomal recessive gelatinous drop-like corneal dystrophy - Zhaoxia Ren; Pei-Yu Lin; Gordon K. Klintworth; Fumino Iwata; Francis L. Munier; Daniel F. Schorderet; Leila El Matri; Veena Theendakara; Surendra Basti; Madhukar Reddy; Fielding J. Hejtmancik (Human Genetics, 2002)

Identification of QTLs for early blight (Alternaria solani) resistance in tomato using backcross populations of a Lycopersicon esculentum × L. hirsutum cross - M. Foolad; L. Zhang; A. A. Khan; D. Niño-Liu; G. Lin (Theoretical and Applied Genetics, 2002)

Leaf respiration is differentially affected by leaf vs. stand‐level night‐time warming - Kevin L. Griffin; Matthew Turnbull; Ramesh Murthy; Guanghui Lin; John Adams; Blake Farnsworth; Tilak Mahato; Guerric Bazin; Mark Potasnak; Joe A. Berry (Global Change Biology, 2002)
Plant respiration is an important physiological process in the global carbon cycle serving as a major carbon flux from the biosphere to the atmosphere. Respiration is sensitive to temperature providing a link between environmental variability, climate change and the global carbon cycle. We measured leaf respiration in Populus deltoides after manipulating the air temperature surrounding part of a single leaf, and compared this to the temperature response of the same leaves after manipulating the temperature of the stand. The short‐term temperature response of respiration (Q 10 – change in the respiration rate with a 10 °C increase in leaf temperature) was 1.7 when the leaf temperature was manipulated, but 2.1 when the stand‐level temperature was changed. As a result, total night‐time carbon release during the five‐day experiment was 21% lower when using the Q 10 estimates from the tradition leaf manipulation compared to the stand‐level manipulation. We conclude that the temperature response of leaf respiration is related to whole plant carbon and energy demands, and that appropriate experimental procedures are required in examining respiratory CO 2 release under variable temperature conditions.

Genetic dissection of a genomic region for a quantitative trait locus, Hd3, into two loci, Hd3a and Hd3b, controlling heading date in rice - L. Monna; H. Lin; S. Kojima; T. Sasaki; M. Yano (Theoretical and Applied Genetics, 2002)

Raman spectra of hydrous γ -Mg 2 SiO 4 at various pressures and temperatures - L. Liu; C.-C. Lin; T. P. Mernagh; T. Inoue (Physics and Chemistry of Minerals, 2002)

Validity of in Vitro Tests on Aqueous Spray Pumps as Surrogates for Nasal Deposition - Julie D. Suman; Beth L. Laube; Ta-chun Lin; Guillaume Brouet; Richard Dalby (Pharmaceutical Research, 2002)

Evolutionary and taxonomic implications of conserved structural motifs between picornaviruses and insect picorna-like viruses - L. Liljas; J. Tate; T. Lin; P. Christian; J. E. Johnson (Archives of Virology, 2002)

Protection against translocating Salmonella typhimurium infection in mice by feeding the immuno-enhancing probiotic Lactobacillus rhamnosus strain HN001 - Harsharnjit S. Gill; Quan Shu; Hai Lin; Kay J. Rutherfurd; Martin L. Cross (Medical Microbiology and Immunology, 2001)

Nutritive quality and morphological development under partial shade of some forage species with agroforestry potential - C. H. Lin; M. L. McGraw; M. F. George; H. E. Garrett (Agroforestry Systems, 2001)

Development of the Fragment Constant Method for Estimating the Partition Coefficients of Nonionic Organic Mixtures - Z. Lin, H. Yu, S. Gao, J. Cheng, L. Wa (Archives of Environmental Contamination and Toxicology, 2001)

RS-100642-198, a novel sodium channel blocker, provides differential neuroprotection against hypoxia/hypoglycemia, veratridine or glutamate-mediated neurotoxicity in primary cultures of rat cerebellar neurons - Jitendra R. Dave; Yu Lin; Haresh S. Ved; Michael L. Koenig; Larry Clapp; John Hunter; Frank C. Tortella (Neurotoxicity Research, 2001)

Toward the mapping of physiological and agronomic characters on a rice function map: QTL analysis and comparison between QTLs and expressed sequence tags - K. Ishimaru; M. Yano; N. Aoki; K. Ono; T. Hirose; S. Y. Lin; L. Monna; T. Sasaki; R. Ohsugi (Theoretical and Applied Genetics, 2001)

Molecular epidemiology of enterovirus 71 in Taiwan - P.-Y. Chu; K.-H. Lin; K.-P. Hwang; L.-C. Chou; C.-F. Wang; S.-R. Shih; J.-R. Wang; Y. Shimada; H. Ishiko (Archives of Virology, 2001)

Statistical optimization of gastric floating system for oral controlled delivery of calcium - Shoufeng Li; Senshang Lin; Yie W. Chien; Bruce P. Daggy; Haresh L. Mirchandani (AAPS PharmSciTech, 2001)

Antibody responses to respiratory coronavirus infections of cattle during shipping fever pathogenesis - X. Q. Lin; K. L. O’Reilly; J. Storz; C. W. Purdy; R. W. Loan (Archives of Virology, 2000)

Sampling efficiency of a modified closed-face cassette sampler for airborne toluene diisocyanate determination - I.-F. Mao; M.-L. Chen; Y.-C. Lin (International Archives of Occupational and Environmental Health, 2000)

Mesoscale simulations of dynamical factors discriminating between a tornado outbreak and non-event over the southeast US Part III: 6 hour precursors - J. M. Egentowich; M. L. Kaplan; Y.-L. Lin; A. J. Riordan (Meteorology and Atmospheric Physics, 2000)

Mesoscale simulations of dynamical factors discriminating between a tornado outbreak and non-event over the southeast US Part II: 48-6 hour precursors - J. M. Egentowich; M. L. Kaplan; Y.-L. Lin; A. J. Riordan (Meteorology and Atmospheric Physics, 2000)

Mesoscale simulations of dynamical factors discriminating between a tornado outbreak and non-event over the southeast US Part I: 84-48 hour precursors - J. M. Egentowich; M. L. Kaplan; Y.-L. Lin; A. J. Riordan (Meteorology and Atmospheric Physics, 2000)

Raman spectroscopic study of hydroxyl-clinohumite at various pressures and temperatures - C.-C. Lin; L.-G. Liu; T. P. Mernagh; T. Irifune (Physics and Chemistry of Minerals, 2000)

Entrainment of Intestinal Slow Waves with Electrical Stimulation Using Intraluminal Electrodes - Xuemei Lin; J. Hayes; L. J. Peters; J. D. Z. Chen (Annals of Biomedical Engineering, 2000)

Central and peripheral tissue distribution of diclofenac after subcutaneous injection in the rat - R. F. Grace; S. R. Edwards; L. E. Mather; Y. Lin; I. Power (Inflammopharmacology, 2000)

Melanocortin 1 receptor variation in the domestic dog - J.M. Newton; Alison L. Wilkie; Lin He; Siobhán A. Jordan; Danika L. Metallinos; Nigel G. Holmes; Ian J. Jackson; Gregory S. Barsh (Mammalian Genome, 2000)

Isolation and characterization of chitinase from a marine bacterium Vibrio sp. - S.N. Zhou; C.Y. Yang; Y.J. Lu; L. Huang; C.H. Cai; Y.C. Lin (World Journal of Microbiology and Biotechnology, 1999)

Flavonoids as inducers of extracellular proteins and exopolysaccharides of Sinorhizobium fredii - C. C. Lin; Y. C. Chen; S. C. Song; L. P. Lin (Biology and Fertility of Soils, 1999)

The spectrum of microsatellite loci on chromosomes 7 and 8 in Taiwan aboriginal populations: a comparative population genetic study - Chi-Chen Wei; Fu-Tien Chiang; Kuo-Sin Lin; L.-I. Lin (Human Genetics, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)

High-pressure Raman spectroscopic study of chondrodite - C.-C. Lin; L.-g. Liu; T. Irifune (Physics and Chemistry of Minerals, 1999)

Localizations of NS3 and E proteins in mouse brain infected with mutant strain of Japanese encephalitis virus - J. J. Wang; C. L. Liao; C. I. Yang; Y. L. Lin; C. T. Chiou; L. K. Chen (Archives of Virology, 1998)

Shade effects on forage crops with potential in temperate agroforestry practices - C. H. Lin; R. L. McGraw; M. F. George; H. E. Garrett (Agroforestry Systems, 1998)

Familial clustering of rheumatoid arthritis with other autoimmune diseases - Jing-Ping Lin; Joseph M. Cash; Sharon Z. Doyle; Sandra Peden; Keith Kanik; Chris I. Amos; S. J. Bale; Ronald L. Wilder (Human Genetics, 1998)

Prediction of Water Solubility and Toxicity of Substituted Indoles to Photobacterium phosphoreum Using Molecular Connectivity Indices and Quantum Chemical Parameters - J. Dai; B. Sun; A. Zhang; K. Lin; L. Wang (Bulletin of Environmental Contamination and Toxicology, 1998)

Induction of apoptosis and secondary necrosis by infectious pancreatic necrosis virus in fish embryonic cells - J‐R Hong; T‐L Lin; Y‐L Hsu; J‐L Wu (Journal of Fish Diseases, 1998)
Infectious pancreatic necrosis virus (IPNV) causes an acute, contagious disease in a number of economically important fish species (Pilcher & Fryer 1980). It is a member of the Birnaviridae (Brown 1986). In this study, the present authors first characterized the process of fish cell damage caused by IPNV infection in cultured cells, and found that it induced fragmentation of chromosomal DNA into oligonucleosomes and also caused nuclear fragmentation by secondary necrosis.

The Student Watershed Research Project (SWRP): collecting watershed data for use by resource management agencies - Deborah J. Lev; Stacy L. Renfro; D. Torrey Lindbo; Wes Jarrell; Jane Blair; Steve Andrews; Lin Howell (Urban Ecosystems, 1998)

Phylogenetic analysis of Methanobrevibacter isolated from feces of humans and other animals - Chuzhao Lin; T. L. Miller (Archives of Microbiology, 1998)

Maturation-dependent gene expression in a conditionally transformed liver progenitor cell line - A. S. Fiorino; A. M. Diehl; H. Z. Lin; I. R. Lemischka; L. M. Reid (In Vitro Cellular & Developmental Biology - Animal, 1998)

Metal-binding and active-site structure of di-zinc Streptomyces griseus aminopeptidase - Lung-Yu Lin; Hyun Ik Park; L.-J. Ming (JBIC Journal of Biological Inorganic Chemistry, 1997)

Analysis of QTL×environment interaction for yield components and plant height in rice - J.-Y. Zhuang; H.-X. Lin; J. Lu; H.-R. Qian; S. Hittalmani; N. Huang; K.-L. Zheng (Theoretical and Applied Genetics, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Stimulation of testicular function by exogenous testosterone in male protandrous black porgy, Acanthopagrus schlegeli - E.‐L. Lau; B.‐Y. Lin; F.‐Y. Lee; L.‐T. Sun; S. Dufour; C.‐F. Chang (Journal of Fish Biology, 1997)
When 4 mg of testosterone (T) per kg food was given to 1‐year‐old protandrous male black porgy Acanthopagrus schlegeli for 7 months, gonadosomatic index was significantly higher than when the dose was 0.5 mg kg −1 food. Both doses of T prolonged the spawning season, and increased the number of spermiating fish and milt volume. Sperm concentrations were similar in spermiating black porgy from the treated and control groups. Low levels of oestradiol‐17β were observed during the experimental period while elevated levels of plasma T were observed only in March in both control and T‐treated groups. Significantly higher levels of plasma 11‐ketotestosterone (11‐KT) were observed in the 0.5‐ and 4.0‐mg T‐treated groups during the spawning season as compared to the control group. The present data suggest that both 0.5‐ and 4·0‐mg T doses stimulate testicular weight, increase numbers of spermiating males and milt volume without affecting the sperm concentrations. Plasma 11‐KT concentrations were elevated during T treatment and closely correlated with testicular development and spermiation.

Human T-lymphotropic Virus Type II Infection inVietnamese Thalassemic Patients - M. T. Lin; B. T. Nguyen; T. V. Binh; T. V. Be; T. Y. Chiang; L. H. Tseng; Y. C. Yang; K. H. Lin; Y. -C. Chen (Archives of Virology, 1997)

Assignment of the ARAF1 to porcine Chromosome Xpll.2-p13 by fluorescence in situ hybridization - Hiroshi Yasue; L. Adams; A. Ozawa; M. Hanazono; N. Li; Z. H. Lin; H. Kusumoto (Mammalian Genome, 1997)

Classification of normal and abnormal electrogastrograms using multilayer feedforward neural networks - Z. Lin; J. Maris; L. Hermans; J. Vandewalle; J. D. Z. Chen (Medical & Biological Engineering & Computing, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

An additional 136 SSLP markers typed for the AXB and BXA recombinant inbred mouse strains - J. K. Naggert; K. L. Svenson; L. Lin; Y. -C. Cheah; P. M. Nishina; J. -L. Mu; T. R. Devereux; M. You; B. Paigen (Mammalian Genome, 1997)

Mutagenic Activity of Incense Smoke in Comparison to Formaldehyde and Acetaldehyde in Salmonella typhimurium TA102 - H. L. Chang; M. L. Kuo; J. M. Lin (Bulletin of Environmental Contamination and Toxicology, 1997)

Rapid detection of trisomy 21 by homologous gene quantitative PCR (HGQ-PCR) - Hsien-Hsiung Lee; Jan-Gowth Chang; Shuan-Pei Lin; Hsiang-Tai Chao; M.-L. Yang; Heung-Tat Ng (Human Genetics, 1997)

Identifying different types of de-differentiated microspores from indica-japonica F1 hybrids with subspecies-differentiating RFLP probes in rice - J. -H. Xie; M. -W. Gao; J. Lu; J. -Y. Zhuang; H. -X. Lin; H. -R. Qian; K. -L. Zheng (Theoretical and Applied Genetics, 1997)

Lipid peroxidation in rats administrated with mercuric chloride - Y. L. Huang; S. L. Cheng; T. H. Lin (Biological Trace Element Research, 1996)

Envelope gene sequences of human T-lymphotropic virus type I in Taiwan - M. T. Lin; Y. C. Chen; P. J. Chen; Y. C. Yang; J. L. Tang; J. M. Wu; S. E. Chuang; C. S. Yang (Archives of Virology, 1996)

N-Nitroso-N-(3-keto-1,2-butanediol)-3′-nitrotyramine - C. -J. Wang; H. -P. Huang; T. -H. Tseng; Y. -L. Lin; S. -J. Shiow (Archives of Toxicology, 1995)

A long lytic cycle in filamentous phage Cf1tv infectingXanthomonas campestris pv.citri - T. -T. Kuo; C. -C. Chiang; S. -Y. Chen; J. -H. Lin; J. -L. Kuo (Archives of Virology, 1994)

Leucine interference in the production of water-soluble red Monascus pigments - T. F. Lin; A. L. Demain (Archives of Microbiology, 1994)

Leucine interference in the production of water-soluble red Monascus pigments - T. F. Lin; A. L. Demain (Archives of Microbiology, 1994)

Trace elements in hair of blackfoot disease - T. C. Pan; T. H. Lin; C. L. Tseng; M. H. Yang; C. W. Huang (Biological Trace Element Research, 1993)

The skin, tongue, and brain as favorable organs for hog cholera diagnosis by immunofluorescence - I. C. Pan; T. S. Huang; C. H. Pan; Shenq-Yi Chern; Shu-Hwae Lee; Y. L. Lin; B. Y. Huang; C. C. Lin; N. J. Li; J. P. Lin; Y. H. Yang; S. Y. Chiu; et al. (Archives of Virology, 1993)

Characteristics of spontaneously produced and of virus-induced human LuKII cell interferons - Lulu A. Pickering; L. S. Lin; F. H. Sarkar (Archives of Virology, 1983)

Production, purification and characterization of rat interferon - L. S. Lin; S. L. Abreu (Archives of Virology, 1979)

Characterization of the size and charge heterogeneities of human leukocyte interferon populations - L. S. Lin; Marzenna Wiranowska-Stewart; T. Chudzio; W. E. Stewart (Archives of Virology, 1978)

Urinary excretion of paranitrophenol and alkyl phosphates following ingestion of methyl or ethyl parathion by human subjects - Donald P. Morgan; Herbert L. Hetzler; Edwin F. Slach; Lawrence I. Lin (Archives of Environmental Contamination and Toxicology, 1977)

Synthesis of RNA with relation to aging inRhizoctonia solani - F. L. Davies; F. K. Lin; David Gottlieb (Archives of Microbiology, 1974)